Exploitation of natural resources of the “dehesa” for meat production - Benito, J; Olea, L; Casco, J M G; Viguera, F J (ressources.ciheam.org)
“Exploitation des ressources naturelles de la “dehesa” pour la production de viande”. Dans les 20 dernières années, l'exploitation des ressources naturelles du “dehesa” (la région boisée de la Méditerranée) située au sud-ouest de la Péninsule Ibérique, a changé d'un système économique de subsistance (la production de bétail de famille, le bois de chauffage, le charbon de bois, la chasse, etc.) à un système intégré visant le bénéfice économique. La grande source de richesse du “dehesa” est basée la production annuelle généreuse de fruits (des glands de chêne) dans un écosystème caractérisé par un sol pauvre et une pluviométrie faible. En raison de la composition en lipides, avec d’hautes pourcentages d'acides gras mono-nonsaturés, les glands sont le régime d'alimentation parfait pour des animaux abattus aux hauts poids et orientés pour élaborer les produits de grande qualité. La large présence de forêt de Chêne au nord de l'Afrique, avec les mêmes caractéristiques que la forêt de “dehesa” ibérien, peut être une bonne raison pour mettre en oeuvre des programmes de collaboration entre des régions géographiques à potentiel comparable. Le but final de ces programmes doit être d améliorer le niveau de revenu de la population rurale et forestière.
Keywords: production de viande; Quercus; ressources naturelles; “dehesa”

Genetic diversity assessment and estimation of phylogenetic relationships among 26 Fagaceae species using ISSRs - Coutinho, João Paulo; Carvalho, Ana; Lima-Brito, José (Biochemical Systematics and Ecology, 2014)
The family Fagaceae includes several species and presents huge genetic variability. In the last two decades, several genetic studies about phylogenetics and genetic diversity of Fagaceae have emerged. ISSR markers were used to evaluate the genetic diversity of 26 species of Fagaceae belonging to the genera Castanea, Fagus and Quercus. Among several primers tested, 17 were selected for the evaluation of diversity and estimation of genetic relationships. A total of 371 ISSR markers were produced and each primer revealed high polymorphism. Specific ISSR markers for the Quercus infrageneric groups were amplified. ISSRs proved to be a reliable tool for the discrimination of the analyzed species per genus, infrageneric group and/or ecological origin.
Keywords: Fagaceae; Genetic variability; Inter-simple sequence repeats (ISSRs); Quercus

Insight into the photosynthetic apparatus in evergreen and deciduous European oaks during autumn senescence using OJIP fluorescence transient analysis - Holland, V; Koller, S; Brüggemann, W (Plant Biology, 2014)
Climate change is one of the major issues nowadays, and Mediterranean broadleaf species have been suggested to fill possible future gaps created by climate change in Central European forests. To provide a scientific-based foundation for such practical strategies, it is important to obtain a general idea about differences and similarities in the physiology of Central European and Mediterranean species. In the present study, we evaluated the onset of leaf senescence of a broad spectrum of oak species under the Central European climate in a common garden experiment. Degradation of the photosynthetic apparatus of evergreen (Quercus ilex, Q. suber), semi-evergreen (Q. × turneri, Q. × hispanica) and deciduous oaks (Q. robur, Q. cerris, Q. frainetto, Q. pubescens) was monitored as chlorophyll content and analysed chlorophyll fluorescence induction transients. In the deciduous species, a significant decline in chlorophyll content was observed during autumn/winter, with Q. pubescens showing the slowest decline. Analysis of fluorescence induction transients revealed a significant decline in quantum efficiency of the primary photochemistry and reaction centre density and later, a decrease in quantum efficiency of end acceptor reduction. Alterations in fluorescence parameters were compared to the decline in chlorophyll content, which occurred much more slowly than expected from the fluorescence data. The evergreen species showed no decline in chlorophyll content, nor different chlorophyll a fluorescence induction behaviour despite temperature falling below 0 °C. The hybrids showed intermediate behaviour between their parental evergreen and deciduous taxa.
Keywords: chlorophyll fluorescence; climate change; portable fluorimeter; Quercus; Senescence; SPAD

Seeding phenology influences wood mouse seed choices: the overlooked role of timing in the foraging decisions by seed-dispersing rodents - Sunyer, Pau; Espelta, Josep Maria; Bonal, Raul; Muñoz, Alberto (Behavioral Ecology and Sociobiology, 2014)
Scatter-hoarding rodents influence the population dynamics of plants by acting as seed predators and dispersers. Therefore, rodent foraging preferences for certain seed traits (species, size, condition) have been extensively studied. However, to what extent these preferences are fixed or they track the temporal changes on seed characteristics due to phenological differences has been seldom explored.We stud- ied the temporal variability in seed preferences by wood mouse (Apodemus sylvaticus), according to phenological changes in seed characteristics of two co-occurring oaks (Quercus ilex and Quercus pubescens). The phenology of acorn abundance and the acorn predation/dispersal patterns by rodents were monitored over an entire seeding season. Results revealed temporal changes in rodent preferences for acorns of the two oaks, matching their different seeding phe- nology (earlier in Q. pubescens and later in Q. ilex). On the other hand, whatever the species considered, rodents preferred larger and sound acorns along the entire season, although the dispersal of infested ones increased slightly during the peaks of acorn drop. The observed influence of seeding phenology on seed choices by rodents warns about inferring definite conclusions regarding their foraging behavior when arising from short-term experiments. Indeed, this study reveals that foraging preferences may be highly dynamic and context- dependent for some seed traits (e.g., species and condition), rather than fixed behavioral patterns. Plasticity in rodent for- aging choices may allowthem to successfully exploit different oaks with uncoupled seeding phenologies, while potentially favoring their coexistence.
Keywords: acorn; Apodemus sylvaticus; dispersal; Quercus; seed; seed traits

Acorn bread: A traditional food of the past in Sardinia (Italy) - Claudia, Pinna (Journal of Cultural Heritage, 2013)
Acorn bread, known as Pan’Ispeli in Sardinian, constituted a precious source of nutrition over the ages. Especially widespread in Ogliastra, it was made with somewhat unusual ingredients, including ash and clay, and is considered a unique food by many historians. So much so that the women of the town of Baunei took pride in their skill at making acorn bread and apparently sold it at a higher price than regular wheat flour bread. The laborious process of preparation of acorns for bread-making is said to have been a ceremony with religious connotations, to such an extent that the ingredients came only from plants and areas that were well known by the elders. It was a ritual passed down from generation to generation. Although acorn bread is no longer part of today's diet in Sardinia, it is still remembered by some of the elderly people of our island and is on occasion still made for village festivities.
Keywords: acorns; Bread; Clay; Coeliac disease sufferers; Quercus; Sardinia

Distribution of leaf characteristics in relation to orientation within the canopy of woody species - Escudero, Alfonso; Fernández, José; Cordero, Angel; Mediavilla, Sonia (Acta Oecologica, 2013)
Over the last few decades considerable effort has been devoted to research of leaf adaptations to environmental conditions. Many studies have reported strong differences in leaf mass per unit area (LMA) within a single tree depending on the photosynthetic photon flux density (PPFD) incident on different locations in the crown. There are fewer studies, however, of the effects of differences in the timing of light incidence during the day on different crown orientations. Leaves from isolated trees of Quercus suber and Quercus ilex in a cold Mediterranean climate were sampled to analyze differences in LMA and other leaf traits among different crown orientations. Gas-exchange rates, leaf water potentials, leaf temperatures and PPFD incident on leaf surfaces in different crown orientations were also measured throughout one entire summer day for each species. Mean daily PPFD values were similar for the leaves from the eastern and western sides of the canopy. On the western side, PPFD reached maximum values during the afternoon. Maximum leaf temperatures were approximately 10–20% higher on the west side, whereas minimum leaf water potentials were between 10 and 24% higher on the east side. Maximum transpiration rates were approximately 22% greater on the west, because of the greater leaf-to-air vapor pressure deficits (LAVPD). Mean individual leaf area was around 10% larger on the east than on the west side of the trees. In contrast, there were no significant differences in LMA between east and west sides of the crown. Contrary to our expectations, more severe water stress on the west side did not result in increases in LMA, although it was associated with lower individual leaf area. We conclude that increases in LMA measured by other authors along gradients of water stress would be due to differences in light intensity between dry and humid sites.
Keywords: Canopy orientation; leaf morphology; Leaf temperature; Quercus; water potential

Effect of the pig rearing system on the final volatile profile of Iberian dry-cured ham as detected by PTR-ToF-MS - Sánchez del Pulgar, J; Soukoulis, C; Carrapiso, A I; Cappellin, L; Granitto, P; Aprea, E; Romano, A; Gasperi, F; Biasioli, F (Meat Science, 2013)
The volatile compound proﬁle of dry-cured Iberian ham lean and subcutaneous fat from pigs fattened outdoors on acorn and pasture (Montanera) or on high-oleic concentrated feed (Campo) was investigated by proton transfer reaction time-of-ﬂight mass spectrometry. In addition to the usual proton transfer ionization the novel switchable reagent ions system was implemented which allows the use of different precursor ions (H3O+ , NO+ and O2 + ). The analysis of the lean and subcutaneous fat volatile compounds allowed a good sample discrimination according to the diet. Differences were evident for several classes of compounds: in particular, Montanera hams showed higher concentrations of aldehydes and ketones and lower concentrations of sulfur-containing compounds compared to Campo hams. The use of NO+ as precursor ion conﬁrmed the results obtained with H3O+ in terms of classiﬁcation capability and provides additional analytical insights.
Keywords: aldehydes; Aldehydes: analysis; Animal Feed; Animal Husbandry; Animal Husbandry: methods; Animals; diet; Dietary Fats; Dietary Fats: analysis; Dietary Fats: pharmacology; Dry cured ham; Ions; Ketones; Ketones: analysis; Mass spectrometry; Mass Spectrometry: methods; meat; Meat: analysis; Nuts; Oleic Acid; Oleic Acid: pharmacology; Poaceae; Proton transfer reaction mass spectrometry; Quercus; Rearing system; subcutaneous fat; Subcutaneous Fat: metabolism; Sulfur Compounds; Sulfur Compounds: analysis; Swine; Switchable reagent ions; Time of flight; Volatile Organic Compounds; Volatile Organic Compounds: analysis

Inferring shifts in tree species distribution using asymmetric distribution curves: a case study in the Iberian mountains - Urli, Morgane; Delzon, Sylvain; Eyermann, Audrey; Couallier, Vincent; GARCÍA-VALDÉS, Raúl; Zavala, Miguel Angel; Porté, Annabel J (Journal of Vegetation Science, 2013)
Questions The objectives of this study were to examine altitudinal shifts in tree species distributions over one decade to quantify the potential for tree migration. Location Spain. Methods We analysed presence–absence data using two successive surveys of the Spanish Forest Inventory in five Fagaceae tree species (two temperate: Fagus sylvatica and Quercus petraea, one sub-Mediterranean: Q. faginea and two Mediterranean: Q. suber and Q. ilex) in two mountain ranges (the Pyrenees and the Iberian system). Half of the fitted altitudinal distributions were skewed and required use of an asymmetric model for unbiased estimates of optimum altitude and changes in the probability of presence along the altitudinal gradient. For each species and mountain range, shifts were considered to have occurred when the difference in optimum altitude was significant or when differences in probability of occurrence between the two surveys demonstrated the occurrence of colonization or extirpation events. Results Overall, depending on species and mountain range, shifts in optimum altitude ranged between −34 m and +181 m. The altitudinal distribution of the Mediterranean species at the core of their latitudinal distribution range presented no sign of change. For the temperate and sub-Mediterranean Fagaceae species, the patterns demonstrated the existence of distribution changes over a 10-yr period. The largest, although not statistically significant, upward shift in optimum altitude was observed for Q. petraea in the Iberian system. More interestingly, its distribution indicated colonization events at higher altitudes. For Q. faginea in the Pyrenees, the shift in optimum altitude was the second largest and statistically significant, and was associated with large extirpation events at the lower altitudes. No evidence of shifts was observed for F. sylvatica. Conclusion This work demonstrates that changes in altitudinal distribution could occur over a 10-yr time period for tree species located at the southern limit of their distribution, such as some temperate and sub-Mediterranean oaks, whereas no movement was detected for Mediterranean oaks in the core of their distribution area.
Keywords: Altitudinal distribution; Fagus; FOREST; model; Optimum; Quercus

Influencia de la encina y el alcornoque sobre las variables físico-químicas del suelo y la regeneración del bosque - CORTÉS, A.; NAVARRO-CERRILLO, R. M.; ARA, M. A.; SÁNCHEZ, R.; GÓMEZ- APARICIO, L.; MARAÑON, T.; VILLAR, R. (VI Congreso Forestal Español, 2013)
El objetivo de este trabajo fue conocer el efecto o la “huella” de la vegetación arbórea sobre las características físico-químicas del suelo y la regeneración de dos especies de Quercus (Q. ilex, Q. suber). Para ello, se realizó un muestreo en dos parcelas de bosque mixto de encina y alcornoque en la Sierra de Córdoba (Trasierra). Las parcelas fueron de 60 x 60 m con una malla de 10 m, resultando 36 puntos de muestreo. En cada uno de los puntos de muestreo se tomaron muestras de suelo a dos profundidades (0-10 y 10-20 cm) y se analizaron las principales variables físico-químicas (textura, pH, N y C, disponibilidad de P, K, Ca y Mg). Además, en cada parcela se realizaron medidas de humedad del suelo y luz, así como la altura y el diámetro del tronco a 130 cm de todos los árboles de la parcela. Para evaluar el efecto del árbol sobre la regeneración, se sembraron semillas de encina y alcornoque y se midió la emergencia, el crecimiento y la supervivencia de las plántulas tras el primer verano. La influencia del árbol se midió en relación a la cantidad de desfronde caído a lo largo de un año. Los resultados mostraron un efecto del arbolado sobre variables físico-químicas del suelo. Así, en las zonas de mayor influencia la densidad aparente del suelo fue menor y la fertilidad del suelo mayor (mayor concentración de N, P, K y Ca). Sin embargo, a pesar de estos cambios en las características del suelo, no se encontró ninguna relación con la emergencia, el crecimiento o la supervivencia de plántulas tras el período estival. Aunque no es de descartar que en plantas de mayor edad, las características del suelo tengan una influencia significativa en el crecimiento y supervivencia, dado que durante el primer año, las plántulas de Quercus dependen fuertemente de las reservas de la semilla
The following values have no corresponding Zotero field: periodical: VI Congreso Forestal Español pub-location: Vitoria
Keywords: Alcornoque; encina; huella del árbol; nutrientes; Quercus; regeneración

Is the Interplay between Epigenetic Markers Related to the Acclimation of Cork Oak Plants to High Temperatures? - Correia, Barbara; Valledor, Luis; Meijón, Mónica; Rodriguez, José Luis; Dias, Maria Celeste; Santos, Conceição; Cañal, Maria Jesus; Rodriguez, Roberto; Pinto, Glória (PLoS ONE, 2013)
Trees necessarily experience changes in temperature, requiring efficient short-term strategies that become crucial in environmental change adaptability. DNA methylation and histone posttranslational modifications have been shown to play a key role in both epigenetic control and plant functional status under stress by controlling the functional state of chromatin and gene expression. Cork oak (Quercus suber L.) is a key stone of the Mediterranean region, growing at temperatures of 45°C. This species was subjected to a cumulative temperature increase from 25°C to 55°C under laboratory conditions in order to test the hypothesis that epigenetic code is related to heat stress tolerance. Electrolyte leakage increased after 35°C, but all plants survived to 55°C. DNA methylation and acetylated histone H3 (AcH3) levels were monitored by HPCE (high performance capillary electrophoresis), MS-RAPD (methylation-sensitive random-amplified polymorphic DNA) and Protein Gel Blot analysis and the spatial distribution of the modifications was assessed using a confocal microscope. DNA methylation analysed by HPCE revealed an increase at 55°C, while MS-RAPD results pointed to dynamic methylation-demethylation patterns over stress. Protein Gel Blot showed the abundance index of AcH3 decreasing from 25°C to 45°C. The immunohistochemical detection of 5-mC (5-methyl-2′-deoxycytidine) and AcH3 came upon the previous results. These results indicate that epigenetic mechanisms such as DNA methylation and histone H3 acetylation have opposite and particular dynamics that can be crucial for the stepwise establishment of this species into such high stress (55°C), allowing its acclimation and survival. This is the first report that assesses epigenetic regulation in order to investigate heat tolerance in forest trees.
The following values have no corresponding Zotero field: publisher: Public Library of Science accession-num: 23326451
Keywords: Acclimatization; Acclimatization: genetics; Acetylation; Blotting; CHROMATIN; CORK oak (citation; Deoxycytidine; Deoxycytidine: analogs & derivatives; Deoxycytidine: metabolism; DNA; DNA methylation; Electrolytes; Electrolytes: metabolism; Epigenesis; Gene expression; Genetic; Genetic Markers; Genome; Heat-Shock Response; Heat-Shock Response: genetics; Histones; Histones: metabolism; Physiological; Physiological: genetics; Plant; Plant Leaves; Plant Leaves: metabolism; Plant: genetics; POST-translational modification; Quercus; Quercus: genetics; Quercus: physiology; Random Amplified Polymorphic DNA Technique; Stress; tags); Temperature; TREES -- Research; Western

Life-cycle assessment of typical Portuguese cork oak woodlands. - González-García, Sara; Dias, Ana Cláudia; Arroja, Luis (The Science of the total environment, 2013)
Cork forest systems are responsible for making an important economic contribution to the Mediterranean region, especially Portugal where the cork oak woodlands or montados contain about 32% of the world's area. The environmental profile derived from reproduction cork production and extraction in two Portuguese regions (Tagus valley and Alentejo) representative of the Portuguese sector were assessed in detail using the Life-Cycle Assessment (LCA) methodology from a cradle-to-gate perspective. The production line was divided into four stages considering all the processes involved: stand establishment, stand management, cork stripping and field recovery. According to the environmental results, there were remarkable differences between the two production scenarios mainly due to the intensity and repetition of forest activities even though the cork yield was reported to be the same. The management system in the Alentejo region presented the worse environmental profile in almost all the impact categories under assessment, mainly due to the shorter cycle duration of the mechanical cleaning and pruning processes. Cork stripping was identified in both scenarios as the production stage with the highest contribution to the environmental profile due to the cleaning and pruning processes. A sensitivity assessment concerning the cork yield was performed since the average production yields in the Portuguese montados are lower than the ones used in this study. Thus, if the cork yield is reduced, the environmental profile in both scenarios gets worse since almost all the forest activities involved are the same.
Keywords: Environment; Environmental impact; Forestry; Forestry: methods; montado; Portugal; Quercus; Quercus suber L.; Reproduction cork; Trees

Physiological and Proteomic Analyses of Drought Stress Response in Holm Oak Provenances - Valero-Galvàn, José; González-Fernández, Raquel; Navarro-Cerrillo, Rafael Maria; Gil-Pelegrín, Eustaquio; Jorrín-Novo, Jesús V (Journal of Proteome Research, 2013)
Responses to drought stress by water withholding have been studied in 1 year old Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) seedlings from seven provenances from Andalusia (southern Spain). Several physiological parameters, including predawn xylem water potentials and relative water content in soil, roots, and leaves as well as maximum quantum efficiency and yield of PSII were evaluated for 28 days in both irrigated and nonirrigated seedlings. The leaf proteome map of the two provenances that show the extreme responses (Seville, GSE, is the most susceptible, while Almer??a, SSA, is the least susceptible) was obtained. Statistically significant variable spots among provenances and treatments were subjected to MALDI-TOF/TOF-MS/MS analysis for protein identification. In response to drought stress, ?12.4% of the reproducible spots varied significantly depending on the treatment and the population. These variable proteins were mainly chloroplastic and belonged to the metabolism and defense/stress functional categories. The 2-DE protein profile of nonirrigated seedlings was similar in both provenances. Physiological and proteomics data were generally in good agreement. The general trend was a decrease in protein abundance upon water withholding in both provenances, mainly in those involved in ATP synthesis and photosynthesis. This decrease, moreover, was most marked in the most susceptible population compared with the less susceptible one.
From Duplicate 2 (Physiological and Proteomic Analyses of Drought Stress Response in Holm Oak Provenances - Valero-Galván, José; González-Fernández, Raquel; Navarro-Cerrillo, Rafael Maria; Gil-Pelegrín, Eustaquio; Jorrín-Novo, Jesús V)
Keywords: Analysis of Variance; biomass; Chlorophyll ﬂuorescence; drought stress in Holm oak; Droughts; Electrophoresis; Gel; Gene Expression Regulation; Holm oak proteomics; Physiological; Physiological: genetics; Physiological: physiology; Plant; Plant Leaves; Plant Leaves: genetics; Plant Leaves: metabolism; Plant Proteins; Plant Proteins: metabolism; Plant: genetics; Plant: physiology; Proteomics; Proteomics: methods; Quercus; Quercus ilex; Quercus: genetics; Quercus: metabolism; Quercus: physiology; Seedling; Seedling: growth & development; Seedling: metabolism; Spain; Stress; Tandem mass spectrometry; Two-Dimensional; water potential

Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª Ma; Abdelly, Chedly; Jorrín-novo, Jesús (Plant Physiology and Biochemistry, 2013)
Phytophthora cinnamomi is one of the agents that trigger the decline syndrome in Quercus spp., this being a serious threat to Mediterranean Holm oak forest sustainability and reforestation programs. Quercus ilex responses to Phytophthora cinnamomi have been studied in one-year olds seedlings from two Andalucía provenances, assessing the physiological water status and photosynthesis-related parameters. Upon inoculation with mycelium a reduction in water content, chlorophyll fluorescence, stomatal conductance and gas exchange was observed along a 90 days post inoculation period in both provenances. The reduction was higher in the most susceptible (SSA) provenance, than in the most tolerant (PCO), being these typical plant responses to drought stress. Leaf protein profiles were analyzed in non-inoculated and inoculated seedlings from the two provenances by using a 2-DE coupled to MS proteomics strategy. Ninety seven proteins changing in abundance in response to the inoculation were successfully identified after MALDI–TOF–TOF analyses. The largest group of variable identified proteins were chloroplasts ones, and they were involved in the photosynthesis, Calvin cycle and carbohydrate metabolism. It was noted that a general tendency was a decrease in the protein abundance as a consequence of the inoculation, being it less accused in the least susceptible, the Northern provenance (PCO), than in the most susceptible, the Southern provenance (SSA). This trend is clearly manifested in photosynthesis, amino acid metabolism and stress/defence proteins. On the contrary, some proteins related to starch biosynthesis, glycolysis and stress related peroxiredoxin showed an increase upon inoculation. These changes in protein abundance were correlated to the estimated physiological parameters and have been frequently observed in plants subjected to drought stress.
From Duplicate 1 (Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª; Abdelly, Chedly; Jorrín-novo, Jesús)
Keywords: Gene Expression Regulation; Holm oak decline; Holm oak proteomics; Phytophthora; phytophthora cinnamomi; Phytophthora: physiology; Plant; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Plant: genetics; Plant: physiology; Proteomics; Proteomics: methods; Quercus; Quercus ilex; Quercus: microbiology

Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª Ma; Abdelly, Chedly; Jorrín-novo, Jesús (Plant Physiology and Biochemistry, 2013)
Phytophthora cinnamomi is one of the agents that trigger the decline syndrome in Quercus spp., this being a serious threat to Mediterranean Holm oak forest sustainability and reforestation programs. Quercus ilex responses to Phytophthora cinnamomi have been studied in one-year olds seedlings from two Andalucía provenances, assessing the physiological water status and photosynthesis-related parameters. Upon inoculation with mycelium a reduction in water content, chlorophyll fluorescence, stomatal conductance and gas exchange was observed along a 90 days post inoculation period in both provenances. The reduction was higher in the most susceptible (SSA) provenance, than in the most tolerant (PCO), being these typical plant responses to drought stress. Leaf protein profiles were analyzed in non-inoculated and inoculated seedlings from the two provenances by using a 2-DE coupled to MS proteomics strategy. Ninety seven proteins changing in abundance in response to the inoculation were successfully identified after MALDI–TOF–TOF analyses. The largest group of variable identified proteins were chloroplasts ones, and they were involved in the photosynthesis, Calvin cycle and carbohydrate metabolism. It was noted that a general tendency was a decrease in the protein abundance as a consequence of the inoculation, being it less accused in the least susceptible, the Northern provenance (PCO), than in the most susceptible, the Southern provenance (SSA). This trend is clearly manifested in photosynthesis, amino acid metabolism and stress/defence proteins. On the contrary, some proteins related to starch biosynthesis, glycolysis and stress related peroxiredoxin showed an increase upon inoculation. These changes in protein abundance were correlated to the estimated physiological parameters and have been frequently observed in plants subjected to drought stress.
From Duplicate 1 (Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª; Abdelly, Chedly; Jorrín-novo, Jesús)From Duplicate 1 (Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª; Abdelly, Chedly; Jorrín-novo, Jesús)The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS accession-num: 23962806
Keywords: Gene Expression Regulation; Holm oak decline; Holm oak proteomics; Phytophthora; phytophthora cinnamomi; Phytophthora: physiology; Plant; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Plant: genetics; Plant: physiology; Proteomics; Proteomics: methods; Quercus; Quercus ilex; Quercus: microbiology

Producción de desfronde en encinas y alcornoques. Influencia de las podas y de variables meteorológicas y ecológicas - ANDIVIA, E.; Alejano, R.; Vázquez-Piqué, J.; Fernández, M. (VI Congreso Forestal Español, 2013)
El desfronde es un proceso clave en el funcionamiento de los ecosistemas forestales. Este proceso tiene un marcado componente estacional y es muy sensible a los cambios en las condiciones ambientales, especialmente aquellas relacionadas con la precipitación, así como con el manejo de las masas. Por tanto, el conocimiento de cómo estas variables pueden afectar a los patrones de producción de desfronde es un factor importante para la conservación de dichos ecosistemas forestales, especialmente en el área mediterránea. Nuestro objetivo es conocer cómo distintas variables meteorológicas, ecológicas y de gestión afectan a la producción y estacionalidad del desfronde de encinas y alcornoques. Para ello se ha recogido el desfronde de forma periódica durante diversos años en tres parcelas, dos de encina y una de alcornoque, donde se ha monitorizado la evolución de las variables meteorológicas. Los árboles de una de estas parcelas fueron sometidos a distintas intensidades de poda, con el objetivo de evaluar el efecto de esta práctica tradicional en la producción de desfronde. Por último, en el caso del alcornoque, se ha analizado la variabilidad mensual en el aporte de nutrientes al suelo por el desfronde, así como la relación entre la distribución de nutrientes en el suelo y la variabilidad en el aporte de éstos por el desfronde. Palabras
The following values have no corresponding Zotero field: periodical: VI Congreso Forestal Español pub-location: Vitoria
Keywords: dehesas; fenología; nutrientes; Quercus; relaciones suelo-árbol

QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia (Plant Physiology and Biochemistry, 2013)
Abstract Cork oak is an economically important forest species showing a great tolerance to high temperatures and shortage of water. However, the mechanisms underlying this plasticity are still poorly understood. Among the stress regulators, transcription factors (TFs) are especially important since they can control a wide range of stress-inducible genes, which make them powerful targets for genetic engineering of stress tolerance. Here we evaluated the influence of increasing temperatures (up to 55 °C) or drought (18% field capacity, FC) on the expression profile of an R2R3-MYB transcription factor of cork oak, the QsMYB1. QsMYB1 was previously identified as being preferentially expressed in cork tissues and as having an associated alternative splicing mechanism, which results in two different transcripts (QsMYB1.1 and QsMYB1.2). Expression analysis by reverse transcription quantitative PCR (RT-qPCR) revealed that increasing temperatures led to a gradual down-regulation of QsMYB1 transcripts with more effect on QsMYB1.1 abundance. On the other hand, under drought condition, expression of QsMYB1 variants, mainly the QsMYB1.2, was transiently up-regulated shortly after the stress imposition. Recovery from each stress has also resulted in a differential response by both QsMYB1 transcripts. Several physiological and biochemical parameters (plant water status, chlorophyll fluorescence, lipid peroxidation and proline content) were determined in order to monitor the plant performance under stress and recovery. In conclusion, this report provides the first evidence that QsMYB1 TF may have a putative function in the regulatory network of cork oak response to heat and drought stresses and during plant recovery.
From Duplicate 1 (QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia)From Duplicate 1 (QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia)The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS accession-num: 24161757
Keywords: Abiotic stress; Adaptation; Cork oak; Droughts; Gene expression; Gene Expression Regulation; Genes; Hot Temperature; Physiological; Plant; Plant Bark; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Quercus; Quercus: genetics; Quercus: metabolism; R2R3-MYB; Recovery; RNA Splicing; Stress; Transcription Factors; Transcription Factors: genetics; Transcription Factors: metabolism; water

Tree species effects on nutrient cycling and soil biota: A feedback mechanism favouring species coexistence - Aponte, Cristina; García, Luis V.; Marañón, Teodoro (Forest Ecology and Management, 2013)
We synthesise a series of independent but integrated studies on the functioning of a mixed Mediterra- nean oak forest to demonstrate the tree–soil interactions underpinning a positive feedback process that sustains the coexistence of two oak species. The studies focused on the foliar functional traits, plant regeneration patterns, biogeochemical cycles, soil microbial biomass and ectomycorrhizal (ECM) fungal diversity associated with the co-dominant evergreen Quercus suber and deciduous Quercus canariensis in a Mediterranean forest in southern Spain. Foliar attributes differed between oak species, with Q. canariensis having higher nutrient content and lower carbon to nutrient ratios and leaf mass per area than Q. suber. These attributes reflected their distinct resource use strategies and adaptation to high and low resource-availability environ- ments, respectively. Leaf-fall nutrient concentrations were higher in Q. canariensis than in Q. suber and were correlated with concentrations in the fresh leaves. Leaf-fall nutrient concentrations influ- enced nutrient return, leaf-fall decay rate and the proportion of nutrients released from decomposing leaf-fall, all of which were higher for Q. canariensis than for Q. suber. This generated a differential net nutrient input into the soil that led to increased soil nutrient concentrations under the canopy of Q. canariensis as compared to Q. suber. The fraction of slowly decomposing leaf-fall that builds up soil organic matter was higher for Q. canariensis, further raising the nutrient and moisture retention of its soils. Differences between species in soil properties disappeared with increasing soil depth, which was consistent with the hypothesised leaf-fall-mediated effect. Tree-species-generated changes in soil properties had further impacts on soil organisms. Soil microbial biomass (Cmic) and nutrients (Nmic, Pmic) were higher under Q. canariensis than under Q. suber and were positively related to soil mois- ture content and substrate availability (particularly soil N). The composition of the ECM fungal com- munity shifted between the two oaks in response to changes in the soil properties, particularly soil Ca and pH. Lower ECM phylogenetic diversity and higher abundance of mycorrhizal species with sapro- phytic abilities were related to the greater soil fertility under Q. canariensis. Overall, the two oak spe- cies generated soil conditions that aligned with their resource-use strategies and would enhance their own competitive capabilities, potentially creating a positive feedback. The two Quercus created soil spatial heterogeneity that could enable their coexistence through spatial niche partitioning. This study demonstrates the critical role of aboveground-belowground interactions underpinning forest commu- nity composition. 
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Feedback processes; Microbial biomass; Mycorrhizal fungi; nutrient cycling; Plant–soil interactions; Quercus

The coexistence of acorns with different maturation patterns explains acorn production variability in cork oak. - Pons, Josep; Pausas, Juli G. (Oecologia, 2012)
In dry areas such as Mediterranean ecosystems, fluctuations in seed production are typically explained by resource (water) availability. However, acorn production in cork oak (Quercus suber) populations shows a very low relationship to weather. Because cork oak trees produce acorns with different maturation patterns (annual and biennial), we hypothesized that acorn production in coexisting individuals with a different dominant acorn maturation type should respond differently to climatic factors and that disaggregating the trees according to their acorn-maturation pattern should provide a more proximal relation to weather factors. We assessed acorn production variability in fragmented cork oak populations of the eastern Iberian Peninsula by counting the total number of acorns in 155 trees during an 8-year period. An initial assessment of acorn production variability in relation to weather parameters yielded very low explained variance (7%). However, after the trees were grouped according to their dominant acorn maturation pattern, weather parameters were found to account for 44% of the variability in acorn crops, with trees with annual acorns exhibiting mast fruiting in years with reduced spring frost and shorter summer droughts and trees with biennial acorns showing the opposite pattern. Thus, conditions that negatively affect annual production could be beneficial for biennial production (and vice versa). The results highlight the importance of the resource-matching hypothesis for explaining acorn production in Quercus suber and suggest that different seed maturation types within a population may allow the species to deal with highly variable weather conditions. They also emphasize the importance of understanding acorn maturation patterns for interpreting masting cycles.
The following values have no corresponding Zotero field: accession-num: 22246473
Keywords: biomass; Evergreen oaks; Fruit; Fruit: growth & development; Hypothesis; Masting; Mediterranean Region; Mediterranean woodlands; Quercus; Quercus suber; Quercus: growth & development; Weather

Cyclobotryoxide, a phytotoxic metabolite produced by the plurivorous pathogen Neofusicoccum australe. - Andolfi, Anna; Maddau, Lucia; Cimmino, Alessio; Linaldeddu, Benedetto T.; Franceschini, Antonio; Serra, Salvatorica; Basso, Sara; Melck, Dominique; Evidente, Antonio (Journal of natural products, 2012)
Two isolates of Neofusicoccum australe belonging to ITS haplotypes H4 and H1 and associated with grapevine cordon dieback and branch dieback of Phoenicean juniper, respectively, have been shown to produce in vitro structurally different secondary metabolites. From the strain BOT48 of N. australe (haplotype H4) a new cyclohexenone oxide, namely, cyclobotryoxide, was isolated together with 3-methylcatechol and tyrosol. Cyclobotryoxide was characterized as (1S,5R,6S)-5-hydroxy-3-methoxy-4-methyl-7-oxabicyclo[4.1.0]hept-3-en-2-one by spectroscopic, optical, and chemical methods. The strain BL24 (haplotype H1) produced tyrosol along with botryosphaerone D and (3S,4S)-3,4,8-trihydroxy-6-methoxy-3,4-dihydro-1(2H)-naphthalenone. The metabolites obtained from both strains were tested at four concentrations on leaves of grapevine cv. Cannonau, holm oak, and cork oak by the leaf puncture assay. Cyclobotryoxide proved to be the most phytotoxic compound. Tyrosol and cyclobotryoxide were also tested on detached grapevine leaves at concentrations of 0.25 and 0.5 mg/mL. Only cyclobotryoxide was found to be active in this bioassay.
The following values have no corresponding Zotero field: accession-num: 23046443
Keywords: Ascomycota; Ascomycota: chemistry; Bicyclo Compounds, Heterocyclic; Bicyclo Compounds, Heterocyclic: chemistry; Bicyclo Compounds, Heterocyclic: isolation & purif; Bicyclo Compounds, Heterocyclic: pharmacology; Catechols; Cyclohexanones; Cyclohexanones: chemistry; Cyclohexanones: isolation & purification; Cyclohexanones: pharmacology; Juniperus; Juniperus: microbiology; Molecular Structure; mycotoxins; Mycotoxins: chemistry; Mycotoxins: isolation & purification; Mycotoxins: pharmacology; Nuclear Magnetic Resonance, Biomolecular; Quercus; Quercus: drug effects; Stereoisomerism; Vitis; Vitis: drug effects

Direct and indirect landscape effects on Quercus ilex regeneration in heterogeneous environments. - Puerta-Piñero, Carolina; Pino, Joan; Gómez, José María (Oecologia, 2012)
Understanding how plant-animal interactions shape plant regeneration is traditionally examined at local scales. In contrast, landscape ecologists working at regional scales often have to infer the mechanisms underlying vegetation patterns. In this study, we empirically explored how landscape attributes (patch connectivity, size, shape, irradiance, slope, and elevation) influence biotic interactions in 1- and 2-year seedlings and saplings of Quercus ilex. We combined field data and GIS-based information under a set of five connectivity scenarios, presuming low, intermediate, and long-distance seed dispersal. Our study emphasizes that landscape, apart from its direct effects on plants, plays a key, albeit indirect, role in plant demography through its effects on seed dispersers and predators. Moreover, the effects of landscape on recruitment differed between plant life stages. One-year seedlings and saplings appear to depend more on plant-animal interactions, while 2-year seedlings depend more on irradiance. Differences in patch connectivity resulted in direct and indirect effects on biotic interactions, which, in turn, produced contrasting positive and negative effects on regeneration at different stages of the life cycle. While jays and wild boars seem crucial to all life stages and most of the connectivity scenarios, rodents and herbivores affected only 1-year seedlings and saplings, respectively, and only a few of the connectivity scenarios. By simultaneously including an ensemble of explanatory factors, our study emphasizes that regeneration depends on a set of key drivers, both abiotic (i.e. irradiance) and biotic (i.e. jays and wild boars), whose effects are greatly modulated by landscape traits.
Keywords: Animals; Ecosystem; irradiance; landscape connectivity; Life Cycle Stages; Mediterranean; Passeriformes; Plant Dispersal; Plant–animal interactions; Quercus; Quercus: growth & development; Recruitment; Seedling; Seedling: growth & development; Sus scrofa

Genomic organization and dynamics of repetitive DNA sequences in representatives of three Fagaceae genera - Alves, Sofia; Ribeiro, Teresa; Inácio, Vera; Rocheta, Margarida; Morais-Cecílio, Leonor (Genome, 2012)
Oaks, chestnuts, and beeches are economically important species of the Fagaceae. To understand the relationship between these members of this family, a deep knowledge of their genome composition and organization is needed. In this work, we have isolated and characterized several AFLP fragments obtained from Quercus rotundifolia Lam. through homology searches in available databases. Genomic polymorphisms involving some of these sequences were evaluated in two species of Quercus, one of Castanea, and one of Fagus with specific primers. Comparative FISH analysis with generated sequences was performed in interphase nuclei of the four species, and the co-immunolocalization of 5-methylcytosine was also studied. Some of the sequences isolated proved to be genus-specific, while others were present in all the genera. Retroelements, either gypsy-like of the Tat/Athila clade or copia-like, are well represented, and most are dispersed in euchromatic regions of these species with no DNA methylation associated, pointing to an interspersed arrangement of these retroelements with potential gene-rich regions. A particular gypsy-sequence is dispersed in oaks and chestnut nuclei, but its confinement to chromocenters in beech evidences genome restructuring events during evolution of Fagaceae. Several sequences generated in this study proved to be good tools to comparatively study Fagaceae genome organization.
doi: 10.1139/g2012-020doi: 10.1139/g2012-020The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: AFLP; Castanea; euchromatin; Fagaceae; Fagus; Quercus; retroelements

Implementation of a module for risk of ozone impacts assessment to vegetation in the Integrated Assessment Modelling system for the Iberian Peninsula. Evaluation for wheat and Holm oak. - de Andrés, Juan Manuel; Borge, Rafael; de la Paz, David; Lumbreras, Julio; Rodríguez, Encarnación (Environmental pollution (Barking, Essex : 1987), 2012)
A module to estimate risks of ozone damage to vegetation has been implemented in the Integrated Assessment Modelling system for the Iberian Peninsula. It was applied to compute three different indexes for wheat and Holm oak; daylight AOT40 (cumulative ozone concentration over 40 ppb), cumulative ozone exposure index according to the Directive 2008/50/EC (AOT40-D) and POD(Y) (Phytotoxic Ozone Dose over a given threshold of Y nmol m(-2) s(-1)). The use of these indexes led to remarkable differences in spatial patterns of relative ozone risks on vegetation. Ozone critical levels were exceeded in most of the modelling domain and soil moisture content was found to have a significant impact on the results. According to the outputs of the model, daylight AOT40 constitutes a more conservative index than the AOT40-D. Additionally, flux-based estimations indicate high risk areas in Portugal for both wheat and Holm oak that are not identified by AOT-based methods.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 22398018
Keywords: Air Pollutants; Air Pollutants: analysis; Air Pollutants: toxicity; Chemical; CMAQ WRF; Critical level; Environmental Monitoring; Environmental Monitoring: methods; iberian peninsula; Models; Ozone; Ozone risk assessment; Ozone: analysis; Ozone: toxicity; Portugal; Quercus; Quercus: drug effects; Quercus: growth & development; Risk Assessment; Stomatal conductance; Triticum; Triticum: drug effects; Triticum: growth & development

Influence of aspect in soil and vegetation water dynamics in dry Mediterranean conditions: functional adjustment of evergreen and semi-deciduous growth forms - Gabarrón-Galeote, Miguel Angel; Ruiz-Sinoga, José Damián; Quesada, Miguel a (Ecohydrology, 2012)
This study was undertaken in a watershed at a dry Spanish Mediterranean location. The effects of the north-facing and southfacing aspects on atmospheric parameters, soil water contents (SWCs) and plant water balances were assessed during 18 months including two dry seasons and one wet season. The species studied were the evergreen sclerophyll Quercus suber and the semideciduous shrubs Cistus albidus, Cistus monspeliensis and Lavandula stoechas. Atmospheric parameters were similar in both exposures, but water content of the 30-cm uppermost soil layers was higher under canopy in the south-facing slope during the wet season. Water balances of both slopes were different, and this was related to the lower shrub abundance and the vegetation patchiness observed in the south-facing slope. Autumn plant recovery was faster in the north-facing hillslope and occurred ﬁrst in shrubs. During the whole study, Quercus suber displayed a hydrostable strategy maintaining an optimum water balance in both hillslopes. This was not the case of shrubs that avoided drought using a phenological adjustment and were more affected by aspect. Differences between tree and shrub water economies relied mainly on their respective root systems. The faster recovery of shrubs after the ﬁrst autumn rainfalls allows them to avoid competition with other functional groups for water and nutrients during some days. Leaf-drying curves distinguished the functional behaviour of the tree and the shrubs because stomatal closure occurred at higher relative water content in the former. The coexistence of both functional strategies ensures an efﬁcient use of water and nutritional resources
Keywords: accepted 18 february 2012; aspect; cistus; lavandula; Mediterranean; plant water balance; Quercus; received 23 may 2011; revised 12 december 2011; Soil moisture

Juvenile–adult tree associations in a continental Mediterranean ecosystem: no evidence for sustained and general facilitation at increased aridity - Granda, Elena; Escudero, Adrián; de la Cruz, Marcelino; Valladares, Fernando (Journal of Vegetation Science, 2012)
Question How do tree species identity, microhabitat and water availability affect inter- and intra-specific interactions between juvenile and adult woody plants? Location Continental Mediterranean forests in Alto Tajo Natural Park, Guadalajara, Spain. Methods A total of 2066 juveniles and adults of four co-occurring tree species were mapped in 17 plots. The frequency of juveniles at different microhabitats and water availability levels was analysed using log-linear models. We used nearest-neighbour contingency table analysis of spatial segregation and J-functions to describe the spatial patterns. Results We found a complex spatial pattern that varied according to species identity and microhabitat. Recruitment was more frequent in gaps for Quercus ilex, while the other three species recruited preferentially under shrubs or trees depending on the water availability level. Juveniles were not spatially associated to conspecific adults, experiencing segregation from them in many cases. Spatial associations, both positive and negative, were more common at higher water availability levels. Conclusions Our results do not agree with expectations from the stress-gradient hypothesis, suggesting that positive interactions do not increase in importance with increasing aridity in the study ecosystem. Regeneration patterns are species-specific and depend on microhabitat characteristics and dispersal strategies. In general, juveniles do not look for conspecific adult protection. This work contributes to the understanding of species co-existence, proving the importance of considering a multispecies approach at several plots to overcome limitations of simple pair-wise comparisons in a limited number of sites.
Keywords: faginea; Juniperus thurifera; patterns; Pinus nigra; Quercus; Quercus faginea; Quercus ilex; Regeneration; spatial; spatial patterns; Stress-gradient hypothesis; water; Water availability

Molecular characterization of Quercus suber MYB1, a transcription factor up-regulated in cork tissues - Almeida, Tânia; Menéndez, Esther; Capote, Tiago; Ribeiro, Teresa; Santos, Conceição; Gonçalves, Sónia (Journal of Plant Physiology, 2012)
The molecular processes associated with cork development in Quercus suber L. are poorly understood. A previous molecular approach identiﬁed a list of genes potentially important for cork formation and differentiation, providing a new basis for further molecular studies. This report is the ﬁrst molecular characterization of one of these candidate genes, QsMYB1, coding for an R2R3-MYB transcription factor. The R2R3-MYB gene sub-family has been described as being involved in the phenylpropanoid and lignin pathways, both involved in cork biosynthesis. The results showed that the expression of QsMYB1 is putatively mediated by an alternative splicing (AS) mechanism that originates two different transcripts (QsMYB1.1 and QsMYB1.2), differing only in the 5 -untranslated region, due to retention of the ﬁrst intron in one of the variants. Moreover, within the retained intron, a simple sequence repeat (SSR) was identiﬁed. The upstream regulatory region of QsMYB1 was extended by a genome walking approach, which allowed the identiﬁcation of the putative gene promoter region. The relative expression pattern of QsMYB1 transcripts determined by reverse transcription quantitative polymerase chain reaction (RTqPCR) revealed that both transcripts were up-regulated in cork tissues; the detected expression was several times higher in newly formed cork harvested from trees producing virgin, second or reproduction cork when compared with wood. Moreover, the expression analysis of QsMYB1 in several Q. suber organs showed very low expression in young branches and roots, whereas in leaves, immature acorns or male ﬂowers, no expression was detected. These preliminary results suggest that QsMYB1 may be related to secondary growth and, in particular, with the cork biosynthesis process with a possible alternative splicing mechanism associated with its regulatory function.
The following values have no corresponding Zotero field: accession-num: 23218545
Keywords: Alternative Splicing; Amino Acid Sequence; Cork biosynthesis; Cork oak; Gene Expression Regulation; Genes; Lipids; Lipids: biosynthesis; Molecular Sequence Data; phellogen; Plant; Plant Bark; Plant Bark: genetics; Plant Bark: metabolism; Plant Growth Regulators; Plant Growth Regulators: biosynthesis; Plant Proteins; Plant Proteins: chemistry; Plant Proteins: metabolism; Quercus; Quercus: genetics; Quercus: metabolism; R2R3-MYB; RNA; Transcription Factors; Transcription Factors: chemistry; Transcription Factors: metabolism; Up-Regulation

Morphological and phenological shoot plasticity in a Mediterranean evergreen oak facing long-term increased drought. - Limousin, Jean-Marc; Rambal, Serge; OURCIVAL, JEAN-MARC; Rodriguez-Calcerrada, Jesus; Pérez-Ramos, Ignacio M.; Rodríguez-Cortina, Raquel; Misson, Laurent; Joffre, Richard (Oecologia, 2012)
Mediterranean trees must adjust their canopy leaf area to the unpredictable timing and severity of summer drought. The impact of increased drought on the canopy dynamics of the evergreen Quercus ilex was studied by measuring shoot growth, leaf production, litterfall, leafing phenology and leaf demography in a mature forest stand submitted to partial throughfall exclusion for 7 years. The leaf area index rapidly declined in the throughfall-exclusion plot and was 19% lower than in the control plot after 7 years of treatment. Consequently, leaf litterfall was significantly lower in the dry treatment. Such a decline in leaf area occurred through a change in branch allometry with a decreased number of ramifications produced and a reduction of the leaf area supported per unit sapwood area of the shoot (LA/SA). The leafing phenology was slightly delayed and the median leaf life span was slightly longer in the dry treatment. The canopy dynamics in both treatments were driven by water availability with a 1-year lag: leaf shedding and production were reduced following dry years; in contrast, leaf turnover was increased following wet years. The drought-induced decrease in leaf area, resulting from both plasticity in shoot development and slower leaf turnover, appeared to be a hydraulic adjustment to limit canopy transpiration and maintain leaf-specific hydraulic conductivity under drier conditions.
The following values have no corresponding Zotero field: accession-num: 22159896
Keywords: allometry; Dehydration; Droughts; France; leaf area; leaf demography; litterfall; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: physiology; Plant Shoots; Plant Shoots: growth & development; Quercus; Quercus: physiology; shoot growth; Trees

Morphological and phenological shoot plasticity in a Mediterranean evergreen oak facing long-term increased drought. - Limousin, Jean-Marc; Rambal, Serge; OURCIVAL, JEAN-MARC; Rodriguez-Calcerrada, Jesus; Pérez-Ramos, Ignacio M; Rodríguez-Cortina, Raquel; Misson, Laurent; Joffre, Richard (Oecologia, 2012)
Mediterranean trees must adjust their canopy leaf area to the unpredictable timing and severity of summer drought. The impact of increased drought on the canopy dynamics of the evergreen Quercus ilex was studied by measuring shoot growth, leaf production, litterfall, leafing phenology and leaf demography in a mature forest stand submitted to partial throughfall exclusion for 7 years. The leaf area index rapidly declined in the throughfall-exclusion plot and was 19% lower than in the control plot after 7 years of treatment. Consequently, leaf litterfall was significantly lower in the dry treatment. Such a decline in leaf area occurred through a change in branch allometry with a decreased number of ramifications produced and a reduction of the leaf area supported per unit sapwood area of the shoot (LA/SA). The leafing phenology was slightly delayed and the median leaf life span was slightly longer in the dry treatment. The canopy dynamics in both treatments were driven by water availability with a 1-year lag: leaf shedding and production were reduced following dry years; in contrast, leaf turnover was increased following wet years. The drought-induced decrease in leaf area, resulting from both plasticity in shoot development and slower leaf turnover, appeared to be a hydraulic adjustment to limit canopy transpiration and maintain leaf-specific hydraulic conductivity under drier conditions.
Keywords: allometry; Dehydration; Droughts; France; leaf area; leaf demography; litterfall; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: physiology; Plant Shoots; Plant Shoots: growth & development; Quercus; Quercus: physiology; shoot growth; Trees

Proteomic analysis of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) pollen. - Valero Galván, José; Valledor, Luis; González Fernandez, Raquel; Navarro Cerrillo, Rafael M; Jorrín-Novo, Jesús V (Journal of proteomics, 2012)
This paper presents an analysis of Holm oak pollen proteome, together with an evaluation of the potentiality that a proteomic approach may have in the provenance variability assessment. Proteins were extracted from pollen of four Holm oak provenances, and they were analyzed by gel-based (1- and 2-DE in combination with MALDI-TOF/TOF) and gel-free (nLC-LTQ Orbitrap MS) approaches. A comparison of 1- and 2-DE protein profiles of the four provenances revealed significant differences, both qualitative and quantitative, in abundance (18 bands and 16 spots, respectively). Multivariate statistical analysis carried out on bands and spots clearly showed distinct associations between provenances, which highlight their geographical origins. A total of 100 spots selected from the 402 spots observed on 2-DE gels were identified by MALDI-TOF/TOF. Moreover, a complementary gel-free shotgun approach was performed by nLC-LTQ Orbitrap MS. The identified proteins were classified according to biological processes, and most proteins in both approaches were related to metabolism and defense/stress processes. The nLC-LTQ Orbitrap MS analysis allowed us the identification of proteins belonging to the cell wall and division, transport and translation categories. Besides providing the first reference map of Holm oak pollen, our results confirm previous studies based on morphological observations and acorn proteomic analysis. Moreover, our data support the valuable use of proteomic techniques as phylogenetic tool in plant studies.
Keywords: Electrophoresis, Gel, Two-Dimensional; Electrophoresis, Gel, Two-Dimensional: methods; Electrophoresis, Polyacrylamide Gel; phylogeny; Plant Proteins; Plant Proteins: analysis; pollen; Pollen: chemistry; Proteome; Proteome: analysis; Proteomics; Proteomics: methods; Quercus; Quercus: genetics; Quercus: metabolism; Spain; Spectrometry, Mass, Matrix-Assisted Laser Desorpti; Two-Dimensional Difference Gel Electrophoresis

Recurrent fires and environment shape the vegetation in Quercus suber L. woodlands and maquis. - Schaffhauser, Alice; Curt, Thomas; Véla, Errol; Tatoni, Thierry (Comptes rendus biologies, 2012)
The effects of fire recurrence on vegetation patterns in Quercus suber L. and Erica-Cistus communities in Mediterranean fire-prone ecosystems of south-eastern France were examined on stands belonging to 5 fire classes, corresponding to different numbers of fires (from 0 to 4) and time intervals between fires since 1959. A common pool of species was identified among the plots, which was typical of both open and closed maquis. Fire recurrence reduced the abundance of trees and herbs, whereas it increased the abundance of small shrubs. Richness differed significantly between the most contrasting classes of fire recurrence, with maximal values found in control plots and minimal values in plots that had burned recurrently and recently. Equitability indices did not vary significantly, in contrast to Shannon's diversity index which mostly correlated with richness. Forest ecosystems that have burnt once or twice in the last 50 years were resilient; that is to say they recovered a biomass and composition similar to that of the pre-fire state. However, after more than 3-4 fires, shrubland communities displayed lower species richness and diversity indices than unburned plots. The time since the last fire and the number of fires were the most explanatory fire variables, governing the structure of post-fire plant communities. However, environmental factors, such as slope or exposure, also made a significant contribution. Higher rates of fire recurrence can affect the persistence or expansion of shrublands in the future, as observed in other Mediterranean areas.
The following values have no corresponding Zotero field: accession-num: 22721564
Keywords: Acidic soil; biomass; climate; cork-oak; Ecosystem; Erica arborea L.; Fire recurrence; Fires; France; Mediterranean Region; Plant communities; Plants; Plants: classification; Quercus; Seasons; Species Specificity; Trees

Spatial patterns of soil pathogens in declining Mediterranean forests: implications for tree species regeneration. - Gómez-Aparicio, LORENA; Ibáñez, Beatriz; Serrano, María S.; De Vita, Paolo; Avila, José M.; Pérez-Ramos, Ignacio M.; García, Luis V.; Esperanza Sánchez, M.; Marañón, Teodoro (The New phytologist, 2012)
Soil-borne pathogens are a key component of the belowground community because of the significance of their ecological and socio-economic impacts. However, very little is known about the complexity of their distribution patterns in natural systems. Here, we explored the patterns, causes and ecological consequences of spatial variability in pathogen abundance in Mediterranean forests affected by oak decline. We used spatially explicit neighborhood models to predict the abundance of soil-borne pathogen species (Phytophthora cinnamomi, Pythium spiculum and Pythium spp.) as a function of local abiotic conditions (soil texture) and the characteristics of the tree and shrub neighborhoods (species composition, size and health status). The implications of pathogen abundance for tree seedling performance were explored by conducting a sowing experiment in the same locations in which pathogen abundance was quantified. Pathogen abundance in the forest soil was not randomly distributed, but exhibited spatially predictable patterns influenced by both abiotic and, particularly, biotic factors (tree and shrub species). Pathogen abundance reduced seedling emergence and survival, but not in all sites or tree species. Our findings suggest that heterogeneous spatial patterns of pathogen abundance at fine spatial scale can be important for the dynamics and restoration of declining Mediterranean forests.
The following values have no corresponding Zotero field: accession-num: 22428751
Keywords: Biological; Forest decline; Host-Pathogen Interactions; Mediterranean Region; Models; neighborhood models; Phytophthora; Phytophthora: physiology; Pythium; Pythium: physiology; Quercus; Quercus suber; Quercus: microbiology; regeneration dynamics; Seedling; Seedling: microbiology; Soil Microbiology; soil texture; soil-borne pathogens; species coexistence

Summer season and long-term drought increase the richness of bacteria and fungi in the foliar phyllosphere of Quercus ilex in a mixed Mediterranean forest - Penuelas, J; Rico, L; Ogaya, R; Jump, A S; Terradas, J (Plant Biology, 2012)
We explored the changes in richness, diversity and evenness of epiphytic (on the leaf surface) and endophytic (within leaf tissues) bacteria and fungi in the foliar phyllosphere of Quercus ilex, the dominant tree species of Mediterranean forests. Bacteria and fungi were assessed during ontogenic development of the leaves, from the wet spring to the dry summer season in control plots and in plots subjected to drought conditions mimicking those projected for future decades. Our aim was to monitor succession in microbiota during the colonisation of plant leaves and its response to climate change. Ontogeny and seasonality exerted a strong influence on richness and diversity of the microbial phyllosphere community, which decreased in summer in the whole leaf and increased in summer in the epiphytic phyllosphere. Drought precluded the decrease in whole leaf phyllosphere diversity and increased the rise in the epiphytic phyllosphere. Both whole leaf bacterial and fungal richness decreased with the decrease in physiological activity and productivity of the summer season in control trees. As expected, the richness of epiphytic bacteria and fungi increased in summer after increasing time of colonisation. Under summer dry conditions, there was a positive relationship between TRF (terminal restriction fragments) richness and drought, both for whole leaf and epiphytic phyllosphere, and especially for fungal communities. These results demonstrate that changes in climate are likely to significantly alter microbial abundance and composition of the phyllosphere. Given the diverse functions and large number of phyllospheric microbes, the potential functional implications of such community shifts warrant exploration.
Keywords: Bacteria; Bacteria: genetics; Bacteria: growth & development; Bacterial; Bacterial TRF richness; Bacterial: genetics; Biodiversity; colonisation time; DNA; Drought; Droughts; endophytes; epiphytes; foliar and epiphytic microbial diversity; foliar phyllosphere; Fungal; fungal TRF richness; Fungal: genetics; fungi; Fungi: genetics; Fungi: growth & development; Mediterranean Region; Plant Leaves; Plant Leaves: microbiology; Polymorphism; Quercus; Quercus: microbiology; Restriction Fragment Length; Seasonality; Seasons; Trees; Trees: microbiology

Tree Species Effect on Litter Decomposition and Nutrient Release in Mediterranean Oak Forests Changes Over Time - Aponte, Cristina; García, Luis V.; Marañón, Teodoro (Ecosystems, 2012)
ree species can affect the decomposition process through the quality of their leaf fall and through the species-speciﬁc conditions that they generate in their environment. We compared the relative importance of these effects in a 2-year experiment. Litterbags containing leaf litter of the winter-deciduous Quercus canariensis, the evergreen Q. suber and mixed litter were incubated beneath distinct plant covers. We measured litter carbon loss, 9 macro- and micronutrients and 18 soil chemical, physical and biological parameters of the incubation environment. Tree species affected decay dynamics through their litter quality and, to a lesser extent, through the induced environmental conditions. The deciduous litter showed a faster initial decomposition but left a larger fraction of slow decomposable biomass compared with the perennial litter; in contrast the deciduous environment impeded early decomposition while promoting further carbon loss in the latter decay stages. The interaction of these effects led to a negative litter–environment interaction contradicting the home-ﬁeld advantage hypothesis. Leaf litter N, Ca and Mn as well as soil N, P and soil moisture were the best predictors for decomposition rates. Litter N and Ca exerted counteractive effects in early versus late decay stages; Mn was the best predictor for the decomposition limit value, that is, the fraction of slowly decomposable biomass at the later stage of decomposition; P and soil moisture showed a constant and positive relation with carbon loss. The deciduous oak litter had a higher initial nutrient content and released its nutrients faster and in a higher proportion than the perennial oak litter, signiﬁcantly increasing soil fertility beneath its canopy. Our ﬁndings provide further insights into the factors that control the early and late stages of the decomposition process and reveal potential mechanisms underlying tree species inﬂuence on litter decay rate, carbon accumulation and nutrient cycling.
Keywords: decomposition limit value; Lignin; litter chemistry; litterbag; Plant–soil interactions; Quercus; Soil fertility

Unveiling the fungal mycobiota present throughout the cork stopper manufacturing process - Barreto, Maria C; Houbraken, Jos; Samson, Robert A; Brito, Dulce; Gadanho, Mário; San Romão, Maria V (FEMS Microbiology Ecology, 2012)
A particular fungal population is present in the main stages of the manufacturing process of cork discs. Its diversity was studied using both dependent (isolation) and independent culture methods (denaturing gel gradient electrophoresis and cloning of the ITS1-5.8S-ITS2 region). The mycobiota in the samples taken in the stages before and after the first boiling seems to be distinct from the population in the subsequent manufacturing stages. Most isolated fungi belong to the genera Penicillium, Eurotium and Cladosporium. The presence of uncultivable fungi, Ascomycota and endophytes in raw cork was confirmed by sequencing. The samples taken after the first boiling contained uncultivable fungi, but in a few samples some isolated fungi were also detected. The main taxa present in the following stages were Chrysonilia sitophila, Penicillium glabrum and Penicillium spp. All applied techniques had complementary outcomes. The main factors driving the shift in cork fungal colonization seem to be the high levels of humidity and temperature to which the slabs are subjected during the boiling process.
Keywords: Biodiversity; cloning; Cork; denaturing gel electrophoresis; Denaturing Gradient Gel Electrophoresis; DNA; Fungal; Fungal: genetics; fungi; Fungi: classification; Fungi: isolation & purification; humidity; Industry; Metagenome; mycobiota diversity; Penicillium; Penicillium: classification; Penicillium: isolation & purification; phylogeny; Plant Bark; Plant Bark: microbiology; Portugal; Quercus; Quercus: microbiology; Ribosomal Spacer; Ribosomal Spacer: genetics; Spain; Temperature; uncultivable fungal species

Use of an airborne lidar system to model plant species composition and diversity of Mediterranean oak forests. - Simonson, William D; Allen, Harriet D; Coomes, David A (Conservation biology : the journal of the Society for Conservation Biology, 2012)
Airborne lidar is a remote-sensing tool of increasing importance in ecological and conservation research due to its ability to characterize three-dimensional vegetation structure. If different aspects of plant species diversity and composition can be related to vegetation structure, landscape-level assessments of plant communities may be possible. We examined this possibility for Mediterranean oak forests in southern Portugal, which are rich in biological diversity but also threatened. We compared data from a discrete, first-and-last return lidar data set collected for 31 plots of cork oak (Quercus suber) and Algerian oak (Quercus canariensis) forest with field data to test whether lidar can be used to predict the vertical structure of vegetation, diversity of plant species, and community type. Lidar- and field-measured structural data were significantly correlated (up to r= 0.85). Diversity of forest species was significantly associated with lidar-measured vegetation height (R(2) = 0.50, p < 0.001). Clustering and ordination of the species data pointed to the presence of 2 main forest classes that could be discriminated with an accuracy of 89% on the basis of lidar data. Lidar can be applied widely for mapping of habitat and assessments of habitat condition (e.g., in support of the European Species and Habitats Directive [92/43/EEC]). However, particular attention needs to be paid to issues of survey design: density of lidar points and geospatial accuracy of ground-truthing and its timing relative to acquisition of lidar data.
Keywords: Biodiversity; Biological; cluster analysis; Conservation of Natural Resources; Conservation of Natural Resources: methods; Ecosystem; mediterranean oak forest; Models; Portugal; predictive modeling; Quercus; Remote sensing; Remote Sensing Technology; Remote Sensing Technology: methods; Species Specificity; vascular plants

Complex selection on life-history traits and the maintenance of variation in exaggerated rostrum length in acorn weevils. - Bonal, Raul; Espelta, Josep Maria; Vogler, Alfried P. (Oecologia, 2011)
Trophic interactions can trigger the development of exaggerated specialized characters and promote morphological diversification. For example, acorn weevils (genus Curculio) present strikingly long rostrums, which are used by females to perforate oviposition holes through the seed coat. Species exhibiting longer rostrums are known to exploit larger acorns, and therefore rostrum length is thought to be subject to selection to match the preferred acorn type. However, rostrum length is strongly correlated with body size, and morphological divergence could result from either selection on rostrum length for optimal food exploitation or from other pressures acting on body size. We collected infested acorns at oak forests where the large Curculio elephas and the small-bodied Curculio glandium co-occur. There were no interspecific differences in adult female body size to rostrum length allometric relationships, and rostrum length is equally correlated with body size in either species. MtDNA-based species identification showed that C. glandium larvae were present within acorns of all sizes, whereas C. elephas larvae were restricted to acorns above a minimum size, irrespective of oak species. Hence, exploitation of large acorns can hardly have triggered rostrum enlargement, as the small sized C. glandium adults (with short rostrums) could perforate and oviposit in both small and large acorns. Rather, increased rostrum length is probably a by-product of the larger body sizes of individuals emerging from bigger acorns, which allow increased larval size and enhance larval survival likelihood. Summarizing, when exaggerated feeding traits co-vary with other body features, interspecific morphological variability may result from contrasting selective pressures acting on these correlated characters.
The following values have no corresponding Zotero field: accession-num: 21674207
Keywords: Body size; Curculio; Ecomorphological diversification; Quercus; Seed size; Trophic segregation

Cryphonectria naterciae: a new species in the Cryphonectria-Endothia complex and diagnostic molecular markers based on microsatellite-primed PCR. - Bragança, Helena; Rigling, Daniel; Diogo, Eugénio; Capelo, Jorge; Phillips, Alan; Tenreiro, Rogério (Fungal biology, 2011)
In a recent study intended to assess the distribution of Cryphonectria parasitica in Portugal, 22 morphologically atypical orange isolates were collected in the Midwestern regions. Eleven isolates were recovered from Castanea sativa, in areas severely affected by chestnut blight and eleven isolates from Quercus suber in areas with cork oak decline. These isolates were compared with known C. parasitica and Cryphonectria radicalis isolates using an integrated approach comprising morphological and molecular methods. Morphologically the atypical isolates were more similar to C. radicalis than to C. parasitica. Phylogenetic analyses based on internal transcribed spacer (ITS) and β-tubulin sequence data grouped the isolates in a well-supported clade separate from C. radicalis. Combining morphological, cultural, and molecular data Cryphonectria naterciae is newly described in the Cryphonectria-Endothia complex. Microsatellite-primed PCR fingerprinting with (GACA)(4) primer discriminated between C. naterciae, C. radicalis, and C. parasitica.
The following values have no corresponding Zotero field: accession-num: 21872182
Keywords: Ascomycota; Ascomycota: classification; Ascomycota: genetics; Ascomycota: isolation & purification; Chestnut tree; Cork oak tree; Cryphonectria parasitica; Cryphonectria radicalis (GACA)4; DNA; DNA Primers; DNA Primers: genetics; Endothiella gyrosa; Fagaceae; Fagaceae: microbiology; Fungal; Fungal Proteins; Fungal Proteins: genetics; Fungal: genetics; Microsatellite Repeats; Molecular Sequence Data; MSP-PCR; Mycological Typing Techniques; Mycological Typing Techniques: methods; phylogeny; Plant Diseases; Plant Diseases: microbiology; Polymerase Chain Reaction; Polymerase Chain Reaction: methods; Quercus; Quercus: microbiology; RFLP-PCR; Tubulin; Tubulin: genetics

Cytogenetic studies on Quercus L. (Fagaceae) species belonging to Ilex and Cerris section in Turkey - Yilmaz, Aykut; Uslu, Emel; Babac, M Tekin (CARYOLOGIA, 2011)
A detailed karyotype analyses of the five species of Quercus L. (Q. coccifera L., Q. ilex L., Q. aucheri Taub. & Spach, Q. cerris L. and Q. ithaburensis Decne subsp. macrolepsis (Kotschy) Hedge & Yak.) belonging to Ilex and Cerris section were examined. The somatic chromosome number of all studied taxa 2n=24 was found. The karyotypes of investigated species showed the great similarity with the chromosome length and the position of centromere. Chromosome number and detailed karyotype of these species were first time counted from Turkey.
Keywords: Cerris; ilex; Karyotype analyses; Quercus; Turkey

Evolution of rDNA FISH patterns in the Fagaceae - Ribeiro, Teresa; Loureiro, João; Santos, Conceição; Morais-Cecílio, Leonor (Tree Genetics & Genomes, 2011)
The Fagaceae is one of the most important plant families in European forest ecosystems, and it includes several genera distributed in the Northern hemisphere. In this work we studied the genome organization and evolution within the family, by karyotyping and physically mapping rDNA in ten European and Asian species of the genera Fagus, Quercus, and Castanea. All of the species studied had a chromosome number of 2n=2x=24, except for the first report of a single individual of Quercus suber which proved to be triploid (2n=3x=36). The rDNA physical mapping revealed several patterns: the dominant one is present in European and Asian Quercus subgenus Quercus, and in Castanea sativa and Castanea crenata, consisting of two 18S–25S rDNA loci (one subterminal major and one pericentromeric minor) and one 5S rDNA pericentromeric locus. In Fagus sylvatica and in Quercus sessilifolia, different patterns were observed: four terminal 18S–25S rDNA loci and two 5S rDNA pericentromeric loci in the former, and five 18S–25S rDNA loci (three terminal and two intercalary) and one 5S rDNA pericentromeric locus in the latter. In Castanea mollissima a distinct rDNA distribution pattern with two intercalary 18S–25S rDNA loci and two 5S rDNA was found. These findings suggest rDNA loci restructuring during Castanea evolution, and variability of 18S–25S loci between Quercus and Cyclobalanopsis subgenera.
Keywords: Castanea; fagaceae karyotype; Fagus; Quercus; rDNA; triploid quercus suber

Prospects of barcoding the Italian wild dendroflora: oaks reveal severe limitations to tracking species identity. - Piredda, Roberta; Simeone, Marco C; Attimonelli, Marcella; BELLAROSA, Rosanna; Schirone, Bartolomeo (Molecular ecology resources, 2011)
DNA barcoding may be particularly important in influencing ecology, economic issues, and the fundamental crisis facing biodiversity as a standardized, species-level identification tool for taxonomy assessment. Trees play important roles in the conservation of many land ecosystems, the wood trade, and the definition of biogeographical processes; nevertheless, peculiar biological, evolutionary and taxonomical features will probably constitute an intriguing challenge to barcoders. We examined whether four marker regions (trnh-psba, rbcL, rpoc1, matK) proposed by the Consortium for the Barcode of Life (CBOL) matched species taxonomy in a preliminary tree biodiversity survey of Italian forested land. Our objective was to provide a test of future in situ applications of DNA barcodes by evaluating the efficacy of species discrimination under the criteria of uniformity of methods and natural co-occurrence of the species in the main forest ecosystems. Fifty-two species were included in a floristic study. We obtained 73% total discrimination success, with trnH-psbA as the best performing marker and oaks as the least responsive plants to the markers used. A further taxon-based study of Quercus (thirty specimens, 12 species) revealed that this genus is refractory to barcoding (0% discrimination success), a probable consequence of low variation rate at the plastid genome level, hybridization, and the incidence of biogeography. We conclude that some species-rich tree genera in small geographical regions may prove exceptionally difficult to barcode. Until more efficient markers are developed, we recommend that improved and diversified sampling (multiple locations of sympatric and co-occurring congenerics) be embraced as a timely and important goal for the precise assessment of haplotype specificity to facilitate the productive application of barcoding in practice.
Keywords: DNA barcoding; forest trees; Italy; Quercus; regional sampling

Studies of variability in Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) through acorn protein profile analysis. - Valero Galván, José; Valledor, Luis; Navarro Cerrillo, Rafael M; Gil Pelegrín, Eustaquio; Jorrín-Novo, Jesús V (Journal of proteomics, 2011)
Studies of variability in Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.), the dominant tree species in the typical Mediterranean forest, have been carried out by using electrophoresis-based proteomic analysis of acorns. Ten populations distributed throughout the Andalusia region have been surveyed. Acorns were sampled from individual trees and proteins extracted from seed flour by using the TCA-acetone precipitation protocol. Extracts were subjected to SDS-PAGE and 2-DE for protein separation, gel images captured, spot or bands quantified, and subjected to statistical analysis (ANOVA, SOM and clustering). Variable bands or spots among populations were subjected to MALDI-TOF/TOF and LC-MS/MS for identification. The protein yield of the used protocol varied among populations, and it was in the 2.92-5.92 mg/g dry weight range. A total of 23 bands were resolved by SDS-PAGE in the 3-35 kDa Mr range, with 8 and 12, out of the total, showing respectively qualitative and quantitative statistically significant differences among populations. Data allowed grouping populations, with groups being correlated according to geographical location and climate conditions, to northern and southern, as well as the discrimination of both mesic and xeric groups. Acorn flour extracts from the most distant populations were analyzed by 2-DE, and 56 differential spots were proposed as markers of variability. Identified proteins were classified into two principal categories; storage and stress/defense protein. Besides providing the first reference map of mature acorn seeds, the use of SDS-PAGE and proteomics in characterizing natural biodiversity in forest trees will be discussed.
Keywords: Acorn proteomics; Chromatography; Electrophoresis; Gene Expression Profiling; Holm oak variability; Liquid; Mass; Matrix-Assisted Laser Desorpti; Plant Proteins; Plant Proteins: metabolism; Polyacrylamide Gel; Quercus; Quercus ilex proteomics; Quercus: genetics; Quercus: metabolism; Seeds; Seeds: chemistry; Spectrometry; Tandem mass spectrometry

Tropospheric ozone effects on chemical composition and decomposition rate of Quercus ilex L. leaves. - Baldantoni, Daniela; Fagnano, Massimo; Alfani, Anna (The Science of the total environment, 2011)
We determined the effects of tropospheric ozone on the chemical composition of Quercus ilex L. leaves and their decomposition, with a view to assessing the influence of ozone on nutrient cycling and the sustainability of Mediterranean holm oak forests. Forming one of the most widespread thermophilous vegetation communities in the area, Q. ilex is a dominant and widespread evergreen oak in the Mediterranean, where concentrations of tropospheric ozone are particularly high. The dynamics of carbon, nitrogen, lignin and cellulose concentrations were monitored for six months during the decomposition of leaves from plants subjected to controlled ozone exposure in open-top chambers. Ozone-exposed leaves, compared to unexposed leaves, showed no significant differences in C, N, lignin and cellulose concentrations prior to the incubation in mesocosms. However, during decomposition, leaves from plants exposed to ozone lost C significantly more slowly and showed a higher C/N ratio than unexposed leaves. Ozone exposure significantly slowed down the decomposition rate, indicating a negative effect of tropospheric ozone on nutrient cycling, which may reduce long-term sustainability of the holm oak forest.
Keywords: Air Pollutants; Air Pollutants: chemistry; Air Pollutants: metabolism; Air Pollutants: toxicity; Atmosphere; Atmosphere: chemistry; Carbon; carbon cycle; Carbon: analysis; Carbon: metabolism; Cellulose; Cellulose: analysis; Cellulose: metabolism; Decaying leaf composition; Holm oak leaves; Lignin; Lignin: analysis; Lignin: metabolism; Mediterranean area; nitrogen; nitrogen cycle; Nitrogen: analysis; Nitrogen: metabolism; Ozone; ozone exposure; Ozone: chemistry; Ozone: metabolism; Ozone: toxicity; Plant Leaves; Plant Leaves: chemistry; Plant Leaves: metabolism; Quercus; Quercus: chemistry; Quercus: metabolism

The use of cork waste as a biosorbent for persistent organic pollutants–Study of adsorption/desorption of polycyclic aromatic hydrocarbons - Olivella, Maria À; Jové, Patrícia; Oliveras, Anna (Journal of Environmental Science and Health, Part A, 2011)
The aim of this study is to determine the sorption-desorption behavior of a mixture of thirteen aqueous PAHs on cork waste at a particle of size 0.25?0.42 mm obtained from the remains of cork strips. The final purpose is to use this natural adsorbent as an alternative to activated carbon in an innovative approach for the removal of this class of toxic compounds, and significantly reduce the regeneration costs of the process. The chemical composition of the selected cork revealed that suberin (38.5 %) and lignin (31.6 %) were the main structural components of the cell wall. The high efficiency of cork as a biosorbent of PAHs is shown by the fact that just over 80 % of adsorption occurred during the first two minutes of contact time. Both Freundlich's and Langmuir's isotherms gave good fits to the sorption process. The highest adsorption affinities were exhibited for pyrene, anthracene, and phenanthrene. Desorption studies indicate a high degree of irreversibility for all PAHs, and especially so in the case of high molecular PAHs. The correlation with KF and low molecular weight PAHs was the most significant. The quantity of cork required to reduce water pollution was estimated to be between 3 and 15 times less than the quantities required in the case of other materials (i.e. aspen wood and leonardite). This study demonstrates for the first time that cork is a potential biosorbent for PAHs and may have relevance in the future treatment of PAH-contaminated waters.
From Duplicate 1 (The use of cork waste as a biosorbent for persistent organic pollutants–Study of adsorption/desorption of polycyclic aromatic hydrocarbons - Olivella, Maria À; Jové, Patrícia; Oliveras, Anna)From Duplicate 1 (The use of cork waste as a biosorbent for persistent organic pollutants–Study of adsorption/desorption of polycyclic aromatic hydrocarbons - Olivella, Maria À; Jové, Patrícia; Oliveras, Anna)The following values have no corresponding Zotero field: publisher: Taylor & Francis accession-num: 21644164
Keywords: Adsorption; Aromatic; Aromatic: chemistry; biosorbent; Chemical; Chemical: chemistry; Cork waste; Environmental Remediation; Environmental Remediation: methods; Gas Chromatography-Mass Spectrometry; Lignin; Lignin: chemistry; Lipids; Lipids: chemistry; organic pollutants; PAHs; Polycyclic Hydrocarbons; Quercus; Quercus: chemistry; Solid Phase Microextraction; sorption-desorption; Time Factors; Water Pollutants; water treatment

Adsorption equilibria of water vapor on cork. - Lequin, Sonia; Chassagne, David; Karbowiak, Thomas; Gougeon, Régis; Brachais, Laurent; Bellat, Jean-Pierre (Journal of agricultural and food chemistry, 2010)
We report here for the first time a complete thermodynamic study of water vapor adsorption on crude cork powder and plate. Adsorption-desorption isotherms were accurately measured by thermogravimetry at 283, 298, and 313 K in a large range of relative pressure. Adsorption enthalpies were determined by calorimetry as a function of loading. Adsorption-desorption isotherms exhibit a hysteresis due to the swelling of the material. The influence of the presence of lenticels on the adsorption properties of cork is found to be negligible. A detailed analysis and interpretation of adsorption data allow proposal of an adsorption mechanism in two steps. (i) First, water adsorbs on hydrophilic sites constituted by hydroxyl and methoxyl groups. (ii) Then water adsorption continues by clusters formation around the hydrophilic sites.
The following values have no corresponding Zotero field: accession-num: 20192215
Keywords: Adsorption; Plant Bark; Plant Bark: chemistry; Quercus; Quercus: chemistry; Thermodynamics; water; Water: chemistry

Changes in water content and distribution in Quercus ilex leaves during progressive drought assessed by in vivo 1H magnetic resonance imaging. - Sardans, Jordi; Penuelas, Josep; Lope-Piedrafita, Silvia (BMC plant biology, 2010)
Drought is a common stressor in many regions of the world and current climatic global circulation models predict further increases in warming and drought in the coming decades in several of these regions, such as the Mediterranean basin. The changes in leaf water content, distribution and dynamics in plant tissues under different soil water availabilities are not well known. In order to fill this gap, in the present report we describe our study withholding the irrigation of the seedlings of Quercus ilex, the dominant tree species in the evergreen forests of many areas of the Mediterranean Basin. We have monitored the gradual changes in water content in the different leaf areas, in vivo and non-invasively, by 1H magnetic resonance imaging (MRI) using proton density weighted (rhow) images and spin-spin relaxation time (T2) maps.
From Duplicate 1 ( Changes in water content and distribution in Quercus ilex leaves during progressive drought assessed by in vivo 1H magnetic resonance imaging. - Sardans, Jordi; Peñuelas, Josep; Lope-Piedrafita, Silvia )
Keywords: Droughts; Magnetic Resonance Imaging; Physiological; Plant Leaves; Plant Leaves: metabolism; Quercus; Quercus: metabolism; Seedling; Seedling: metabolism; Soil; Soil: analysis; Stress; Time Factors; water; Water: metabolism (citation)

Remobilization of acorn nitrogen for seedling growth in holm oak (Quercus ilex), cultivated with contrasting nutrient availability. - Villar-Salvador, Pedro; Heredia, Norberto; Millard, Peter (Tree physiology, 2010)
The relative contribution of nitrogen (N) reserves from seeds or uptake by the roots to the growth and N content of young seedlings has received little attention. In this study, we investigated the contribution of N from the acorn or uptake by the roots to the N content of holm oak (Quercus ilex L.) seedlings and determined if remobilization of acorn N was affected by nutrient availability in the growing media. Q. ilex seedlings were cultivated for 3 months, until the end of the second shoot flush of growth, with three N fertilization rates: 8.6 mM N, 1.4 mM N or no fertilization. Fertilizer N was enriched in (15)N. Between 62 and 75% of the N contained in high and low fertilized seedlings, respectively, at the end of the second flush of growth was derived from the acorn. However, the dependence on acorn N was greater during the early root growth and first shoot flush of growth and decreased during the second shoot flush of growth, with root uptake contributing 32-54% of plant new N in this latter developmental stage in high and low fertilized plants, respectively. Fertilization rate did not affect the amount of N taken up during the earliest developmental stages, but it increased it during the second shoot flush of growth. Fertilization increased the mass of the shoot segment formed during the second shoot flush of growth and reduced the root mass, with no effect on whole plant growth. Remobilization of acorn N was faster in unfertilized plants than in fertilized plants. It is concluded that the holm oak seedlings depend greatly upon acorn N until the end of the second shoot flush of growth, that significant root N uptake starts at the beginning of the second shoot flush of growth and that acorn N remobilization is a plastic process that is accelerated under extremely low substratum nutrient content.
Keywords: germination; nitrogen; Nitrogen Isotopes; Nitrogen Isotopes: metabolism; Nitrogen: metabolism; Quercus; Quercus: growth & development; Quercus: metabolism; Seedling; Seedling: growth & development; Seedling: metabolism; Seeds; Seeds: metabolism; Soil

Acorn crop size and pre-dispersal predation determine inter-specific differences in the recruitment of co-occurring oaks. - Espelta, Josep Maria; Cortes, P.; Molowny-Horas, R.; Retana, J. (Oecologia, 2009)
The contribution of pre-dispersal seed predation to inter-specific differences in recruitment remains elusive. In species with no resistance mechanisms, differences in pre-dispersal predation may arise from differences in seed abundance (plant satiation) or in the ability of seeds to survive insect infestation (seed satiation). This study aimed to analyse the impact of pre-dispersal acorn predation by weevils in two co-occurring Mediterranean oaks (Quercus ilex and Quercus humilis) and to compare its relevance with other processes involved in recruitment. We monitored the patterns of acorn production and acorn infestation by weevils and we conducted experimental tests of acorn germination after weevil infestation, post-dispersal predation and seedling establishment in mixed forests. Monitoring and experimental data were integrated in a simulation model to test for the effects of pre-dispersal predation in recruitment. In both oaks pre-dispersal acorn infestation decreased with increasing acorn crop size (plant satiation). This benefited Q. ilex which exhibited stronger masting behaviour than Q. humilis, with almost a single and outstanding reproductive event in 6 years. Acorn infestation was more than twice as high in Q. humilis (47.0%) as in Q. ilex (20.0%) irrespective of the number of seeds produced by each species. Although germination of infested acorns (seed satiation) was higher in Q. humilis (60%) than in Q. ilex (21%), this could barely mitigate the higher infestation rate in the former species, to reduce seed loss. Conversely to pre-dispersal predation, no inter-specific differences were observed either in post-dispersal predation or seedling establishment. Our results indicate that pre-dispersal predation may contribute to differences in seed supply, and ultimately in recruitment, between co-existing oaks. Moreover, they suggest that seed satiation can barely offset differences in seed infestation rates. This serves as a warning against overemphasising seed satiation as a mechanism to overcome seed predation by insects.
The following values have no corresponding Zotero field: accession-num: 19544074
Keywords: Animals; Feeding Behavior; Feeding Behavior: physiology; germination; Germination: physiology; Models, Biological; Quercus; Quercus: physiology; Seeds; Seeds: growth & development; Spain; Species Specificity; weevils; Weevils: physiology

Antioxidant and Biological Properties of Bioactive Phenolic Compounds from Quercus suber L. - Fernandes, Ana; Fernandes, Iva; Cruz, Luís Luís; Mateus, Nuno; Cabral, Miguel; de Freitas, Victor (Journal of Agricultural and Food Chemistry, 2009)
Phenolic compounds, namely, hydrolyzable tannins and low molecular weight phenolic compounds, were isolated and purified from Portuguese cork from Quercus suber L. Some of these compounds were studied to evaluate their antioxidant activity, including free-radical scavenging capacity (DPPH method) and reducing capacity (FRAP method). All compounds tested showed significant antioxidant activity, namely, antiradical and reducing properties. The antiradical capacity seemed to increase with the presence of galloyl groups. Regarding the reducing capacity, this structure-activity relationship was not so clear. These compounds were also studied to evaluate the growth inhibitory effect on the estrogen responsive human breast cancer cell line (ERþ) MCF-7 and two other colon cancer cell lines (Caco-2 and HT-29). Generally, all the compounds tested exhibited, after a continuous exposure during a 48 h period, a dose-dependent growth inhibitory effect. Relative inhibitory activity was primarily related to the number of phenolic hydroxyl groups (galloyl and HHDP moieties) found in the active structures, with more groups generally conferring increased effects, except for HHDP-di-galloyl-glucose. Mongolicain B showed a greater potential to inhibit the growth of the three cell lines tested, identical to the effect observed with castalagin. Since these compounds are structurally related with each other, this activity might be based within the C-glycosidic ellagitannin moiety.
From Duplicate 2 (Antioxidant and Biological Properties of Bioactive Phenolic Compounds from Quercus suber L. - Fernandes, Ana; Fernandes, Iva; Cruz, Luís; Mateus, Nuno; Cabral, Miguel; de Freitas, Victor)From Duplicate 2 (Antioxidant and Biological Properties of Bioactive Phenolic Compounds from Quercus suber L. - Fernandes, Ana; Fernandes, Iva; Cruz, Luís; Mateus, Nuno; Cabral, Miguel; de Freitas, Victor)The following values have no corresponding Zotero field: publisher: American Chemical Society accession-num: 19888728
Keywords: antioxidants; Antioxidants: chemistry; Antioxidants: isolation & purification; Antioxidants: pharmacology; Antitumor activity; Cell Line; Cell Proliferation; Cell Proliferation: drug effects; Cork; Humans; Hydrolyzable Tannins; Hydrolyzable Tannins: chemistry; Hydrolyzable Tannins: isolation & purification; Hydrolyzable Tannins: pharmacology; phenolic compounds; Plant Extracts; Plant Extracts: chemistry; Plant Extracts: isolation & purification; Plant Extracts: pharmacology; Quercus; Quercus suber L.; Quercus: chemistry; Tumor

Antioxidant and Biological Properties of Bioactive Phenolic Compounds from Quercus suber L. - Fernandes, Ana; Fernandes, Iva; Cruz, Luís Luís; Mateus, Nuno; Cabral, Miguel; de Freitas, Victor (Journal of Agricultural and Food Chemistry, 2009)
Phenolic compounds, namely, hydrolyzable tannins and low molecular weight phenolic compounds, were isolated and purified from Portuguese cork from Quercus suber L. Some of these compounds were studied to evaluate their antioxidant activity, including free-radical scavenging capacity (DPPH method) and reducing capacity (FRAP method). All compounds tested showed significant antioxidant activity, namely, antiradical and reducing properties. The antiradical capacity seemed to increase with the presence of galloyl groups. Regarding the reducing capacity, this structure-activity relationship was not so clear. These compounds were also studied to evaluate the growth inhibitory effect on the estrogen responsive human breast cancer cell line (ERþ) MCF-7 and two other colon cancer cell lines (Caco-2 and HT-29). Generally, all the compounds tested exhibited, after a continuous exposure during a 48 h period, a dose-dependent growth inhibitory effect. Relative inhibitory activity was primarily related to the number of phenolic hydroxyl groups (galloyl and HHDP moieties) found in the active structures, with more groups generally conferring increased effects, except for HHDP-di-galloyl-glucose. Mongolicain B showed a greater potential to inhibit the growth of the three cell lines tested, identical to the effect observed with castalagin. Since these compounds are structurally related with each other, this activity might be based within the C-glycosidic ellagitannin moiety.
From Duplicate 2 (Antioxidant and Biological Properties of Bioactive Phenolic Compounds from Quercus suber L. - Fernandes, Ana; Fernandes, Iva; Cruz, Luís; Mateus, Nuno; Cabral, Miguel; de Freitas, Victor)
Keywords: antioxidants; Antioxidants: chemistry; Antioxidants: isolation & purification; Antioxidants: pharmacology; Antitumor activity; Cell Line; Cell Proliferation; Cell Proliferation: drug effects; Cork; Humans; Hydrolyzable Tannins; Hydrolyzable Tannins: chemistry; Hydrolyzable Tannins: isolation & purification; Hydrolyzable Tannins: pharmacology; phenolic compounds; Plant Extracts; Plant Extracts: chemistry; Plant Extracts: isolation & purification; Plant Extracts: pharmacology; Quercus; Quercus suber L.; Quercus: chemistry; Tumor

CALCIUM OXALATE CRYSTALS IN LEAVES OF QUERCUS CERRIS L. AND Q-ILEX L. - Kaplan, Hatice Coelgecen Ayse; Buyukkartal, H Nurhan (BANGLADESH JOURNAL OF BOTANY, 2009)
Leaves of Quercus cerris L. were collected from Zonguldak, Devrek and those of Q. ilex L. samples were collected from Zonguldak, Eregli, Turkey. The leaf sections were subjected to histochemical analysis and brown-black stained calcium oxalate crystals were identified. The organic contents in the leaves were completely cleaned for polarizing microscope investigation. Calcium oxalate crystals were found to be druz and prismatic in Q. cerris and Q. ilex species. While druz crystals were localized in mesophyll, prismatic ones were localized around the leaf vessels. The amount of calcium oxalate crystals per mm(2) was determined in permanent preparations.
Keywords: Calcium oxalate crystals; leaf anatomy; Quercus

Differential photosynthetic performance and photoprotection mechanisms of three Mediterranean evergreen oaks under severe drought stress - Javier Peguero-Pina, Jose; Sancho-Knapik, Domingo; Morales, Fermín; Flexas, Jaume; Gil-Pelegrín, Eustaquio (FUNCTIONAL PLANT BIOLOGY, 2009)
The ability of three Mediterranean oaks (Quercus coccifera L., Quercus ilex ssp. ballota (Desf.) Samp and Quercus suber L.) to cope with intense drought was investigated. Water stress reduced stomatal conductance and photosynthesis in these species. Drought-mediated changes in photosynthetic-related parameters allowed the characterisation of the specific photo-protective mechanisms. Specifically, Q. suber downregulated photosynthetic electron transport rates (ETR) closing PSII reaction centres (i.e. decreasing photochemical quenching) and through an antheraxanthin (A) + zeaxanthin (Z)-mediated diminished intrinsic PSII efficiency (Phi(exc.).). These changes were lower in Q. coccifera and Q. ilex ssp. ballota, which decreased further ETR photo-inactivating PSII centres (evidenced by their low predawn F(v)/F(m) ratios at high water stress). The predawn F(v)/F(m) ratio decreased in Q. coccifera largely due to F(m) decreases, whereas in Q. ilex ssp. ballota F(v)/F(m) decreases were due to F(0) increases, below -4 MPa. These F(v)/F(m) decreases were well correlated with increases in the A + Z photo-protective pigments. An analysis of dark respiration and photorespiration as alternative electron sinks under intense drought stress also revealed interspecific differences. The largest imbalance between electrons generated and consumed increased potentially oxidative damage in Q. suber. Subsequently, only Q. suber showed loss of chlorophyll, which is one of the main targets of oxidative damage. Data suggest that Q. coccifera and Q. ilex ssp. ballota seem more able than Q. suber to withstand highly xeric conditions. Therefore, our results question the consideration of Mediterranean evergreen oaks as a homogeneous physiological group.
Keywords: morphological convergence; photoprotection; physiological performance; Quercus; Summer aridity; water stress

Genetic transformation of cork oak (Quercus suber L.) for herbicide resistance. - Alvarez, Rubén; Alvarez, José M.; Humara, Jaime M.; Revilla, Angeles; Ordás, Ricardo J. (Biotechnology letters, 2009)
The bar gene was introduced into the cork oak genome. Cork oak embryogenic masses were transformed using the Agrobacterium strain AGL1 which carried the plasmid pBINUbiBar. This vector harbours the genes, nptII and bar, the latter under control of the maize ubiquitin promoter. The transgenic embryogenic lines were cryopreserved. Varying activities of phosphinothricin acetyl transferase were detected among the lines, which carried 1-4 copies of the insert. Molecular and biochemical assays confirmed the stability and expression of the transgenes 3 months after thawing the cultures. These results demonstrate genetic engineering of herbicide tolerance in Quercus spp.
The following values have no corresponding Zotero field: accession-num: 19543858
Keywords: Acetyltransferases; Acetyltransferases: genetics; Acetyltransferases: metabolism; Gene Dosage; Genomic Instability; Herbicide Resistance; Herbicides; Herbicides: toxicity; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Plants, Genetically Modified; Plants, Genetically Modified: drug effects; Plants, Genetically Modified: genetics; Plants, Genetically Modified: physiology; Plasmids; Promoter Regions, Genetic; Quercus; Quercus: drug effects; Quercus: genetics; Quercus: physiology; Rhizobium; Rhizobium: genetics; Transformation, Genetic; Zea mays; Zea mays: genetics

Genetic transformation of cork oak (Quercus suber L.) for herbicide resistance. - Alvarez, Rubén; Alvarez, José M; Humara, Jaime M; Revilla, Angeles; Ordás, Ricardo J (Biotechnology letters, 2009)
The bar gene was introduced into the cork oak genome. Cork oak embryogenic masses were transformed using the Agrobacterium strain AGL1 which carried the plasmid pBINUbiBar. This vector harbours the genes, nptII and bar, the latter under control of the maize ubiquitin promoter. The transgenic embryogenic lines were cryopreserved. Varying activities of phosphinothricin acetyl transferase were detected among the lines, which carried 1-4 copies of the insert. Molecular and biochemical assays confirmed the stability and expression of the transgenes 3 months after thawing the cultures. These results demonstrate genetic engineering of herbicide tolerance in Quercus spp.
Keywords: Acetyltransferases; Acetyltransferases: genetics; Acetyltransferases: metabolism; Gene Dosage; Genomic Instability; Herbicide Resistance; Herbicides; Herbicides: toxicity; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Plants, Genetically Modified; Plants, Genetically Modified: drug effects; Plants, Genetically Modified: genetics; Plants, Genetically Modified: physiology; Plasmids; Promoter Regions, Genetic; Quercus; Quercus: drug effects; Quercus: genetics; Quercus: physiology; Rhizobium; Rhizobium: genetics; Transformation, Genetic; Zea mays; Zea mays: genetics

La productividad de bellota en la dehesa y su relación con parámetros meteorológicos - CARBONERO, M. D.; GARCÍA-MORENO, A.; Calzado, C.; FERNÁNDEZ-REBOLLO, P. (Actas de la XLVIII RC de la SEEP. Huesca La multifuncionalidad de los pastos: producción ganadera sostenible y gestión de los ecosistemas, 2009)
Economically, holm-oak acorn crop is the major component in Iberian Mediterranean eco- systems. As in most Quercus species, the chief feature of holm-oak acorn production is its high variability among individuals and years, because of variables as masting, weather, etc. From 2001 to 2006 we studied fruit production and meteorology in a holm-oak natural area of South Spain. The results obtained, indicated that weather conditions at spring and autumn beginning had a marked influence on acorn production. Flowering survival and production improved by mild temperature in March and crop acorn was stronger because of rainfall in September
The following values have no corresponding Zotero field: periodical: Actas de la XLVIII RC de la SEEP. Huesca La multifuncionalidad de los pastos: producción ganadera sostenible y gestión de los ecosistemas pub-location: Huesca
Keywords: crop; Quercus; seed

La productividad de bellota en la dehesa y su relación con parámetros meteorológicos - CARBONERO, M D; GARCÍA-MORENO, A; Calzado, C; FERNÁNDEZ-REBOLLO, P (Actas de la XLVIII RC de la SEEP. Huesca La multifuncionalidad de los pastos: producción ganadera sostenible y gestión de los ecosistemas, 2009)
Economically, holm-oak acorn crop is the major component in Iberian Mediterranean eco- systems. As in most Quercus species, the chief feature of holm-oak acorn production is its high variability among individuals and years, because of variables as masting, weather, etc. From 2001 to 2006 we studied fruit production and meteorology in a holm-oak natural area of South Spain. The results obtained, indicated that weather conditions at spring and autumn beginning had a marked influence on acorn production. Flowering survival and production improved by mild temperature in March and crop acorn was stronger because of rainfall in September
Keywords: crop; Quercus; seed

Modelling the drought impact on monoterpene fluxes from an evergreen Mediterranean forest canopy. - Grote, Rüdiger; LAVOIR, ANNE-VIOLETTE; Rambal, Serge; Staudt, Michael; Zimmer, Ina; Schnitzler, Jörg-Peter (Oecologia, 2009)
In many ecosystems drought cycles are common during the growing season but their impact on volatile monoterpene emissions is unclear. Therefore, we aimed to develop and evaluate a process-based modelling approach to explore the explanatory power of likely mechanisms. The biochemically based isoprene and monoterpene emission model SIM-BIM2 has been modified and linked to a canopy model and a soil water balance model. Simulations are carried out for Quercus ilex forest sites and results are compared to measured soil water, photosynthesis, terpene-synthase activity, and monoterpene emission rates. Finally, the coupled model system is used to estimate the annual drought impact on photosynthesis and emission. The combined and adjusted vegetation model was able to simulate photosynthesis and monoterpene emission under dry and irrigated conditions with an R(2) of 0.74 and 0.52, respectively. We estimated an annual reduction of monoterpene emission of 67% for the extended and severe drought period in 2006 in the investigated Mediterranean ecosystem. It is concluded that process-based ecosystem models can provide a useful tool to investigate the involved mechanisms and to quantify the importance of specific environmental constraints.
Keywords: Biological; Carbon dioxide; Carbon Dioxide: metabolism; Computer Simulation; Drought impact; Droughts; France; Model coupling; Models; monoterpene emission; Monoterpenes; Monoterpenes: metabolism; photosynthesis; Photosynthesis: physiology; Plant Leaves; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: metabolism; Scaling; Trees; Trees: metabolism; water; Water: metabolism

Photosynthesis studies on European evergreen and deciduous oaks grown under Central European climate conditions. I: a case study of leaf development and seasonal variation of photosynthetic capacity in Quercus robur (L.), Q. ilex (L.) and their semidecidu - Both, Holger; Brüggemann, Wolfgang (Trees, 2009)
Leaf development of Quercus robur (deciduous), Q. ilex (evergreen) and of their hybrid Q. 9 turneri was assessed under Central European climate conditions. In all three taxa, development of maximum photosynthetic capacity was slow, although whole chain electron transport, grana development, the xanthophyll cycle and the biochemical capacity for photosynthesis were already completely present at day 7 after budbreak (DAB 7). In the course of the following 30 days, shifts in the levels of metabolites of the photosynthetic dark reactions were observed, indicating a change from ribulose bisphosphate (RubP) regeneration limitation towards RubP consumption limitation of photosynthesis. At the same time, electron transport rates had strongly increased and the capacity of the light reactions did not seem to limit photosynthesis. Sucrose levels in the leaves increased strongly, indicating sink limitation of photosynthesis, which might be responsible for the observed slow development of maximum photosynthetic capacity in all three taxa.
Keywords: á; leaf development; leaf development á quercus; photosynthesis; Quercus; Sink limitation; sink limitation á photosynthesis

Photosynthesis studies on European evergreen and deciduous oaks grown under Central European climate conditions: II. Photoinhibitory and light-independent violaxanthin deepoxidation and downregulation of photosystem II in evergreen, winter-acclimated Euro - Brüggemann, Wolfgang; Bergmann, Michael; Nierbauer, Kai-Uwe; Pflug, Ellen; Schmidt, Carlo; Weber, Daniel (Trees, 2009)
In the context of the search for future forestry species in Central Europe under climate change scenarios, the evergreen Mediterranean Quercus taxa Q. ilex ssp. ilex and Q. suber and the semideciduous hybrids. Q. 9 turneri and Q. 9 hispanica were studied in relation to their photochemical efﬁciency of photosystem II and to the activity of the xanthophyll cycle under Central European winter conditions. The evergreen taxa were remarkably insensitive to winter stress in the ﬁeld and reacted towards frost periods with the phenomenon of ‘‘chronic photoinhibition’’, i.e. a decrease in pre-dawn Fv/Fm and an increase in the deepoxidation state of the xanthophylls. Under dark and warmer conditions (room temperature), winter-acclimated leaves of the evergreen taxa except for Q. 9 turneri produced zeaand antheraxanthin and decreased Fv/Fm, possibly by creation of a chlororespiratory pH-gradient. It is suggested that the ability for dark violaxanthin deepoxidation may contribute to the winter hardiness of the evergreen taxa.
Keywords: á downregulation of ps; chlororespiration; chlororespiration á photoinhibition á; downregulation of ps II; ii; photoinhibition; Quercus; quercus á winter acclimation; winter acclimation

Photosynthesis studies on European evergreen and deciduous oaks grown under Central European climate conditions. I: a case study of leaf development and seasonal variation of photosynthetic capacity in Quercus robur (L.), Q. ilex (L.) and their semidecidu - Both, Holger; Brüggemann, Wolfgang (Trees, 2009)
Leaf development of Quercus robur (deciduous), Q. ilex (evergreen) and of their hybrid Q. 9 turneri was assessed under Central European climate conditions. In all three taxa, development of maximum photosynthetic capacity was slow, although whole chain electron transport, grana development, the xanthophyll cycle and the biochemical capacity for photosynthesis were already completely present at day 7 after budbreak (DAB 7). In the course of the following 30 days, shifts in the levels of metabolites of the photosynthetic dark reactions were observed, indicating a change from ribulose bisphosphate (RubP) regeneration limitation towards RubP consumption limitation of photosynthesis. At the same time, electron transport rates had strongly increased and the capacity of the light reactions did not seem to limit photosynthesis. Sucrose levels in the leaves increased strongly, indicating sink limitation of photosynthesis, which might be responsible for the observed slow development of maximum photosynthetic capacity in all three taxa.
Keywords: á; leaf development; leaf development á quercus; photosynthesis; Quercus; Sink limitation; sink limitation á photosynthesis

Photosynthesis studies on European evergreen and deciduous oaks grown under Central European climate conditions: II. Photoinhibitory and light-independent violaxanthin deepoxidation and downregulation of photosystem II in evergreen, winter-acclimated Euro - Brüggemann, Wolfgang; Bergmann, Michael; Nierbauer, Kai-Uwe; Pflug, Ellen; Schmidt, Carlo; Weber, Daniel (Trees, 2009)
In the context of the search for future forestry species in Central Europe under climate change scenarios, the evergreen Mediterranean Quercus taxa Q. ilex ssp. ilex and Q. suber and the semideciduous hybrids. Q. 9 turneri and Q. 9 hispanica were studied in relation to their photochemical efﬁciency of photosystem II and to the activity of the xanthophyll cycle under Central European winter conditions. The evergreen taxa were remarkably insensitive to winter stress in the ﬁeld and reacted towards frost periods with the phenomenon of ‘‘chronic photoinhibition’’, i.e. a decrease in pre-dawn Fv/Fm and an increase in the deepoxidation state of the xanthophylls. Under dark and warmer conditions (room temperature), winter-acclimated leaves of the evergreen taxa except for Q. 9 turneri produced zeaand antheraxanthin and decreased Fv/Fm, possibly by creation of a chlororespiratory pH-gradient. It is suggested that the ability for dark violaxanthin deepoxidation may contribute to the winter hardiness of the evergreen taxa.
Keywords: á downregulation of ps; chlororespiration; chlororespiration á photoinhibition á; downregulation of ps II; ii; photoinhibition; Quercus; quercus á winter acclimation; winter acclimation

Plasticity and stress tolerance override local adaptation in the responses of Mediterranean holm oak seedlings to drought and cold - Gimeno, Teresa E; Pías, Beatriz; Lemos-Filho, José P; Valladares, Fernando (Tree Physiology, 2009)
Plant populations of widely distributed species experience a broad range of environmental conditions that can be faced by phenotypic plasticity or ecotypic differentiation and local adaptation. The strategy chosen will determine a population’s ability to respond to climate change. To explore this, we grew Quercus ilex (L.) seedlings from acorns collected at six selected populations from climatically contrasting localities and evaluated their response to drought and late season cold events. Maximum photosynthetic rate (Amax), instantaneous water use efficiency (iWUE), and thermal tolerance to freeze and heat (estimated from chlorophyll fluorescence versus temperature curves) were measured in 5-month-old seedlings in control (no stress), drought (water-stressed), and cold (low suboptimal temperature) conditions. The observed responses were similar for the six populations: drought decreased Amax and increased iWUE, and cold reduced Amax and iWUE. All the seedlings maintained photosynthetic activity under adverse conditions (drought and cold), and rapidly increased their iWUE by closing stomata when exposed to drought. Heat and freeze tolerances were similarly high for seedlings from all the populations, and they were significantly increased by drought and cold, respectively; and were positively related to each other. Differences in seedling performance across populations were primarily induced by maternal effects mediated by seed size and to a lesser extent by idiosyncratic physiologic responses to drought and low temperatures. Tolerance to multiple stresses together with the capacity to physiologically acclimate to heat waves and cold snaps may allow Q. ilex to cope with the increasingly stressful conditions imposed by climate change. Lack of evidence of physiologic seedling adaptation to local climate may reflect opposing selection pressures to complex, multidimensional environmental conditions operating within the distribution range of this species.
10.1093/treephys/tpn007
Keywords: Adaptation; Biological; Biological: physiology; Cold Temperature; Droughts; eﬃciency; Freezing; Genetic Variation; Hot Temperature; Nuts; photosynthesis; Photosynthesis: physiology; Physiological; Quercus; Quercus ilex; Quercus: physiology; Stress; thermal tolerance; Trees; water; water use; Water: physiology

Proteomic analysis from haploid and diploid embryos of Quercus suber L. identifies qualitative and quantitative differential expression patterns. - Gómez, Aranzazu; López, Juan Antonio; Pintos, Beatriz; Camafeita, Emilio; Bueno, Ma Angeles (Proteomics, 2009)
Quercus suber L. is a Mediterranean forest species with ecological, social and economic value. Clonal propagation of Q. suber elite trees has been successfully obtained from in vitro-derived somatic and gametic embryos. These clonal lines play a main role in breeding and genetic studies of Q. suber. To aid in unravelling diverse genetic and biological unknowns, a proteomic approach is proposed. The proteomic analysis of Q. suber somatic and gametic in vitro culture-derived embryos, based on DIGE and MALDI-MS, has produced for the first time proteomic data on this species. Seventeen differentially expressed proteins have been identified which display significantly altered levels between gametic and somatic embryos. These proteins are involved in a variety of cellular processes, most of which had been neither previously associated with embryo development nor identified in the genus Quercus. Some of these proteins are involved in stress and pollen development and others play a role in the metabolism of tannins and phenylpropanoids, which represent two of the major pathways for the synthesis of cork chemical components. Furthermore, the augmented expression levels found for specific proteins are probably related to the homozygous state of a doubled-haploid sample. Proteins involved in synthesis of cork components can be detected at such early stages of development, showing the potential of the method to be useful in searching for biomarkers related to cork quality.
Keywords: cluster analysis; Cork oak; Diploidy; Electrophoresis; Embryonic Development; flow cytometry; Gametic embryogenesis; Gel; Haploid and diploid embryos; Haploidy; Plant Proteins; Plant Proteins: analysis; Plant Proteins: biosynthesis; Plant Proteins: genetics; Plant proteomics; Ploidies; Ploidy level; Principal component analysis; Proteomics; Proteomics: methods; Quercus; Quercus suber L.; Quercus: chemistry; Quercus: genetics; Quercus: metabolism; Seeds; Seeds: chemistry; Seeds: genetics; Seeds: metabolism; Two-Dimensional; Up-Regulation

Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J.; Soto, Álvaro; Gil, Luis; Soto, Álvaro; Gil, Luis (Annals of Botany, 2009)
Background and Aims Marginal populations of widely distributed species can be of high conservation interest when they hold a significant or unique portion of the genetic diversity of the species. However, such genetic information is frequently lacking. Here the relevance of genetic surveys to develop efficient conservation strategies for such populations is illustrated using cork oak (Quercus suber) from Minorca (Balearic Islands, Spain) as a case study. Cork oak is highly endangered on the island, where no more than 67 individuals live in small, isolated stands in siliceous sites. As a consequence, it was recently granted protected status.Methods Two Bayesian clustering approaches were used to analyse the genetic structure of the Minorcan population, on the basis of nuclear microsatellite data. The different groups within the island were also compared with additional island and continental populations surrounding Minorca.Key Results Very high genetic diversity was found, with values comparable with those observed in continental parts of the species' range. Furthermore, the Minorcan oak stands were highly differentiated from one another and were genetically related to different continental populations of France and Spain.Conclusions The high levels of genetic diversity and inter-stands differentiation make Minorcan cork oak eligible for specific conservation efforts. The relationship of Minorcan stands to different continental populations in France and Spain probably reflects multiple colonization events. However, discrepancy between chloroplast DNA- and nuclear DNA-based groups does not support a simple scenario of recent introduction. Gene exchanges between neighbouring cork oak stands and with holm oak have created specific and exceptional genetic combinations. They also constitute a wide range of potential genetic resources for research on adaptation to new environmental conditions. Conservation guidelines that take into account these findings are provided.
From Duplicate 2 (Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J; Soto, Álvaro; Gil, Luis)From Duplicate 2 (Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J; Soto, Álvaro; Gil, Luis)The following values have no corresponding Zotero field: accession-num: 19671575
Keywords: Balearic Islands; cluster analysis; conservation guidelines; Conservation of Natural Resources; Genetic Variation; Geography; marginal populations; Minorca; Nuclear microsatellites; Population Dynamics; Q. ilex (holm oak); Quercus; Quercus suber (cork oak); Quercus: genetics; Soil; Spain; western Mediterranean

Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J; Soto, Álvaro; Gil, Luis; Soto, Álvaro; Gil, Luis (Annals of Botany, 2009)
Background and Aims Marginal populations of widely distributed species can be of high conservation interest when they hold a significant or unique portion of the genetic diversity of the species. However, such genetic information is frequently lacking. Here the relevance of genetic surveys to develop efficient conservation strategies for such populations is illustrated using cork oak (Quercus suber) from Minorca (Balearic Islands, Spain) as a case study. Cork oak is highly endangered on the island, where no more than 67 individuals live in small, isolated stands in siliceous sites. As a consequence, it was recently granted protected status.Methods Two Bayesian clustering approaches were used to analyse the genetic structure of the Minorcan population, on the basis of nuclear microsatellite data. The different groups within the island were also compared with additional island and continental populations surrounding Minorca.Key Results Very high genetic diversity was found, with values comparable with those observed in continental parts of the species' range. Furthermore, the Minorcan oak stands were highly differentiated from one another and were genetically related to different continental populations of France and Spain.Conclusions The high levels of genetic diversity and inter-stands differentiation make Minorcan cork oak eligible for specific conservation efforts. The relationship of Minorcan stands to different continental populations in France and Spain probably reflects multiple colonization events. However, discrepancy between chloroplast DNA- and nuclear DNA-based groups does not support a simple scenario of recent introduction. Gene exchanges between neighbouring cork oak stands and with holm oak have created specific and exceptional genetic combinations. They also constitute a wide range of potential genetic resources for research on adaptation to new environmental conditions. Conservation guidelines that take into account these findings are provided.
From Duplicate 2 (Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J; Soto, Álvaro; Gil, Luis)
Keywords: Balearic Islands; cluster analysis; conservation guidelines; Conservation of Natural Resources; Genetic Variation; Geography; marginal populations; Minorca; Nuclear microsatellites; Population Dynamics; Q. ilex (holm oak); Quercus; Quercus suber (cork oak); Quercus: genetics; Soil; Spain; western Mediterranean

Adsorption of Zn(II) in aqueous solution by activated carbons prepared from evergreen oak (Quercus rotundifolia L.). - Gómez-Tamayo, M Del Mar; Macías-García, Antonio; Díaz Díez, M Angeles; Cuerda-Correa, Eduardo M (Journal of hazardous materials, 2008)
In the present work activated carbons have been prepared from evergreen oak wood. Different samples have been prepared varying the concentration of the activating agent (H(3)PO(4)) and the treatment temperature. The yield of the process decreases with increasing phosphoric acid concentrations. Furthermore, high concentrations of activating agent lead to mainly mesoporous activated carbons to the detriment of the microporous texture. Treatment temperatures up to 450 degrees C lead to a progressive increase of the micro- and mesopore volumes. Values of specific surface area (S(BET)) as high as 1723 m(2) g(-1)have been obtained using appropriate phosphoric acid concentrations and treatment temperatures. The samples prepared have been successfully used in the removal of Zn(II) from aqueous solutions. From the adsorption kinetic data it may be stated that the equilibrium time is, in all cases, below 170 h. The adsorption process as a rule becomes faster as the mesopore volume and specific surface area of the samples increase. The adsorption isotherms in liquid phase point out that the adsorption capacity (n(0)(s)) and the affinity towards the solute (K(ci)) are higher for the sample showing the most developed mesoporous texture and surface area as well.
Keywords: Adsorption; Carbon; Carbon: chemistry; Hydrogen-Ion Concentration; Quercus; Solutions; Water Pollutants, Chemical; Water Pollutants, Chemical: chemistry; Water Purification; Water Purification: methods; Wood; Zinc; Zinc: chemistry

A coastal reservoir of biodiversity for Upper Pleistocene human populations: palaeoecological investigations in Gorham's Cave (Gibraltar) in the context of the Iberian Peninsula - Carrión, J S; Finlayson, C; Fernández, S; Finlayson, G; Allué, E; López-Sáez, J A; López-García, P; Gil-Romera, G; Bailey, G; González-Sampériz, P; Carrion, J; Fernández, S; et al. (Quaternary Science Reviews, 2008)
Palaeobotanical (pollen, charcoal) data from Gorham’s Cave reveals a diversified landscape in the Gibraltar region during the Middle (c. 32 560–23 780 year BP) and Upper Palaeolithic (c. 18 440–10 880 BP). Inferred vegetation types include oak, pine, juniper, and mixed woodlands and savannahs, grasslands with heaths, heliophytic matorrals, phreatophytic formations (e.g. riverine forests, wetlands), and thermomediterranean coastal scrub. A revision of palaeoecological data suggests that patches of trees persisted even in northern and continental territories of the Iberian Peninsula during the cold stages of OIS3 and OIS2. However, a southern Mediterranean coastal shelf extending from Gibraltar to Málaga, and probably further north up to Murcia, was unique in its combination of thermo-, meso-, and supramediterranean plant and animal species. Given the composition of these assemblages, this shelf and its adjacent mountains represented a crucial reservoir of biodiversity during the Upper Pleistocene. It is within this physiographically complex context with its diversity of resources where the last Neanderthals extraordinarily survived until c. 24 000 BP, that is over 10 000 years later than the disappearance of Neanderthals from elsewhere in temperate Europe.
Keywords: climatic fluctuations (voyant); Gibraltar; glacial refugia; Mediterranean; Quercus

Effectiveness of rodents as local seed dispersers of Holm oaks. - Gómez, José M; Puerta-Piñero, Carolina; Schupp, Eugene W (Oecologia, 2008)
In this study we assessed the effectiveness of rodents as dispersers of Quercus ilex in a patchy landscape in southeastern Spain. We experimentally followed the fates of 3,200 marked and weighed acorns from dispersal through the time of seedling emergence over three years. Rodents handled about 99% of acorns, and dispersed 67% and cached 7.4% of the dispersed acorns. Most caches were recovered and consumed, and only 1.3% of the original experimental acorns were found alive in caches the following spring. Dispersal distances were short (mean = 356.2 cm, median = 157 cm) and strongly right-skewed. Heavier acorns were dispersed further and were more likely to be cached and survive than lighter acorns. All caches were in litter or soil, and each contained a single acorn. Rodents moved acorns nonrandomly, mostly to oaks and pines. Most surviving acorns were either in oaks, a poor microhabitat for oak recruitment, or shrubs, a suitable microhabitat for oak recruitment. Our results suggest that rodents, by burying a relatively high proportion of acorns singly in shrubs and pines, act as moderately effective dispersers of Q. ilex. Nonetheless, this dispersal comes at a very heavy cost.
Keywords: Animals; Ecosystem; Feeding Behavior; germination; Germination: physiology; Quercus; Quercus: physiology; Rodentia; Rodentia: psychology; Seeds; Seeds: physiology; Soil; Spain

Effects of moderate shade and irrigation with eutrophicated water on the nitrogen economy of Mediterranean oak seedlings - Castro-Díez, Pilar; Navarro, Javier; Maestro, Melchor (Flora - Morphology, Distribution, Functional Ecology of Plants, 2008)
We evaluated the effects of moderate shade (43% vs. 100% of full sunlight) and irrigation with eutrophicated river water (daily vs. alternate-day watering) on growth and nitrogen economy of seedlings of three Mediterranean oak species, two evergreen (Quercus coccifera, Quercus ilex subsp. ballota) and a deciduous (Quercus faginea), grown in pots outdoors. Seedling biomass, N pool, N concentration and N losses by litter fall were measured at the beginning (March 2002) and end (November 2002) of a growing season. All species showed an increase of biomass and N pool under shade and/or high irrigation, while only Q. coccifera – from more arid regions – did the same under full sunlight and low irrigation. At the end of the experiment, biomass of the evergreens was higher in shade than in sun, and in high than in low irrigation, while Q. faginea – from more humid zones – responded to irrigation only. Shade-induced growth was accompanied by a decline in N concentration in the evergreens, but irrigation reduced N concentration only of Q. faginea. Shade, but not irrigation, reduced above-ground N loss. We conclude that both treatments differentially affected the evergreen and the deciduous oaks, probably due to differences in plant hydraulic and stomatal conductance. Although both treatments have similar effects on the growth of evergreens, they produced different effects on seedling N economy, which may have important consequences on future ﬁeld seedling performance
Keywords: deciduous tree; Drought stress; evergreen tree; leaf shedding; Quercus; seedling growth

Effects of moderate shade and irrigation with eutrophicated water on the nitrogen economy of Mediterranean oak seedlings - Castro-Díez, Pilar; Navarro, Javier; Maestro, Melchor (Flora - Morphology, Distribution, Functional Ecology of Plants, 2008)
We evaluated the effects of moderate shade (43% vs. 100% of full sunlight) and irrigation with eutrophicated river water (daily vs. alternate-day watering) on growth and nitrogen economy of seedlings of three Mediterranean oak species, two evergreen (Quercus coccifera, Quercus ilex subsp. ballota) and a deciduous (Quercus faginea), grown in pots outdoors. Seedling biomass, N pool, N concentration and N losses by litter fall were measured at the beginning (March 2002) and end (November 2002) of a growing season. All species showed an increase of biomass and N pool under shade and/or high irrigation, while only Q. coccifera – from more arid regions – did the same under full sunlight and low irrigation. At the end of the experiment, biomass of the evergreens was higher in shade than in sun, and in high than in low irrigation, while Q. faginea – from more humid zones – responded to irrigation only. Shade-induced growth was accompanied by a decline in N concentration in the evergreens, but irrigation reduced N concentration only of Q. faginea. Shade, but not irrigation, reduced above-ground N loss. We conclude that both treatments differentially affected the evergreen and the deciduous oaks, probably due to differences in plant hydraulic and stomatal conductance. Although both treatments have similar effects on the growth of evergreens, they produced different effects on seedling N economy, which may have important consequences on future ﬁeld seedling performance
Keywords: deciduous tree; Drought stress; evergreen tree; leaf shedding; Quercus; seedling growth

In vitro and in vivo quantification of elicitin expression in Phytophthora cinnamomi - Horta, Marília; Sousa, Nelson; Coelho, Ana C.; Neves, Dina; Cravador, Alfredo (Physiological and Molecular Plant Pathology, 2008)
The differential expression of four Phytophthora cinnamomi elicitin genes was analysed by Real Time RT-PCR. In in vitro cultures, the a-cinnamomin gene showed the highest level of expression, the b-cinnamomin gene (b-cin) was the most inducible, and the HAE transcripts were in low abundance. Transcription of all the elicitins was active during the active growth of the pathogen when infecting cork oak (Quercus suber) roots, and as host colonization progressed, the level of b-cin expression fell, while that of a-cin rose. In an antisense transgenic strain, the silencing of b-cin also negatively affected the expression of other elicitin genes in the cluster. The reduced in planta growth of the b-cin knock-out is related to the altered pattern of elicitin gene expression, supporting the idea that one of the functions of elicitins is related, directly or indirectly, with pathogenesis
Keywords: Elicitin expression; Gene silencing; Pathogenesis; phytophthora cinnamomi; Quercus; Real time RT-PCR; Transformation

Leaf accumulation of trace elements and polycyclic aromatic hydrocarbons (PAHs) in Quercus ilex L. - De Nicola, F; Maisto, G; Prati, M V; Alfani, a (Environmental pollution (Barking, Essex : 1987), 2008)
Quercus ilex L. leaves were collected four times in one year at six urban sites and one remote area in order to determine trace element and PAH accumulation through concomitant analyses of unwashed and water-washed leaves. Both unwashed and washed leaves showed the highest amounts of trace elements and PAHs in the urban area. Unwashed leaves showed greater differences between urban and remote areas and among the urban sites than washed leaves for trace element and PAH concentrations. Water-washing resulted in a significant (P<0.001) decrease in leaf concentrations of Cr, Cu, Fe, Pb, V and Zn. By contrast, Cd and total PAH concentrations showed no differences between unwashed and washed leaves.
Keywords: Air Pollutants; Air Pollutants: analysis; Aromatic; Aromatic: analysis; Atomic; biomonitoring; cadmium; Cadmium: analysis; chromium; Chromium: analysis; Cities; copper; Copper: analysis; Environmental Monitoring; Environmental Monitoring: methods; Iron; Iron: analysis; Italy; lead; Lead: analysis; PAHs; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus ilex L.; Spectrophotometry; Trace Elements; Trace Elements: analysis; Unwashed and washed leaves; Vanadium; Vanadium: analysis; Zinc; Zinc: analysis

Leaf accumulation of trace elements and polycyclic aromatic hydrocarbons (PAHs) in Quercus ilex L. - De Nicola, F.; Maisto, G.; Prati, M. V.; Alfani, A. (Environmental pollution (Barking, Essex : 1987), 2008)
Quercus ilex L. leaves were collected four times in one year at six urban sites and one remote area in order to determine trace element and PAH accumulation through concomitant analyses of unwashed and water-washed leaves. Both unwashed and washed leaves showed the highest amounts of trace elements and PAHs in the urban area. Unwashed leaves showed greater differences between urban and remote areas and among the urban sites than washed leaves for trace element and PAH concentrations. Water-washing resulted in a significant (P<0.001) decrease in leaf concentrations of Cr, Cu, Fe, Pb, V and Zn. By contrast, Cd and total PAH concentrations showed no differences between unwashed and washed leaves.
The following values have no corresponding Zotero field: accession-num: 17892907
Keywords: Air Pollutants; Air Pollutants: analysis; Aromatic; Aromatic: analysis; Atomic; biomonitoring; cadmium; Cadmium: analysis; chromium; Chromium: analysis; Cities; copper; Copper: analysis; Environmental Monitoring; Environmental Monitoring: methods; Iron; Iron: analysis; Italy; lead; Lead: analysis; PAHs; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus ilex L.; Spectrophotometry; Trace Elements; Trace Elements: analysis; Unwashed and washed leaves; Vanadium; Vanadium: analysis; Zinc; Zinc: analysis

Oak seedling survival and growth along resource gradients in Mediterranean forests: implications for regeneration in current and future environmental scenarios - Gómez-Aparicio, L.; PÉREZ-RAMOS, I. M.; Mendoza, I.; Matías, L.; Quero, J. L.; Castro, J.; Zamora, R.; MARAÑON, T. (Oikos, 2008)
Understanding seedling performance across resource gradients is crucial for defining the regeneration niche of plant species under current environmental conditions and for predicting potential changes under a global change scenario. A 2-year field experiment was conducted to determine how seedling survival and growth of two evergreen and two deciduous Quercus species vary along gradients of light and soil properties in two Mediterranean forests with contrasting soils and climatic conditions. Half the seedlings were subjected to an irrigation treatment during the first year to quantify the effects on performance of an alteration in the summer drought intensity. Linear and non-linear models were parameterized and compared to identify major resources controlling seedling performance. We found both site-specific and general patterns of regeneration. Strong site-specificity was found in the identity of the best predictors of seedling survival: survival decreased linearly with increasing light (i.e. increasing desiccation risk) in the drier site, whereas it decreased logistically with increasing spring soil water content (i.e. increasing waterlogging risk) in the wetter site. We found strong empirical support for multiple resource limitation at the drier site, the response to light being modulated by the availability of soil resources (water and P). Evidence for regeneration niche partitioning among Quercus species was only found at the wetter site. However, at both sites Quercus species shared the same response to summer drought alleviation through water addition: increased first-year survival but not final survival (i.e. after two years). This suggests that extremely dry summers (i.e. the second summer in the experiment) can cancel out the positive effects of previous wetter summers. Therefore, an increase in the intensity and frequency of summer drought with climate change might cause a double negative impact on Quercus regeneration, due to a general reduction in survival probability and the annulment of the positive effects of (infrequent) ‘wet’ years. Overall, results presented in this study are a major step towards the development of a mechanistic model of Mediterranean forest dynamics that incorporates the idiosyncrasies and generalities of tree regeneration in these systems, and that allow simulation and prediction of the ecological consequences of resource level alterations due to global change.
Keywords: abiotic factors; growth (voyant); light; Mediterranean forests; Quercus; Regeneration; seedling survival; soil conditions; summer drought

Regional phenological models for forecasting the start and peak of the Quercus pollen season in Spain - García-Mozo, H.; Chuine, I.; Aira, M. J. J.; Belmonte, J.; Bermejo, D.; Díaz de la Guardia, C.; Elvira, B.; Gutiérrez, M.; Rodríguez-Rajo, J.; Ruiz, L.; Trigo, M. M. M.; Tormo, R.; et al. (Agricultural and Forest Meteorology, 2008)
he study sought to achieve the broadest possible spatial and temporal predictions by examining genetic variations in the timing of ﬂowering between populations of the Iberian Quercus species using pollen data from 15 sites in Spain. The speciﬁc objective of the study was to develop and ﬁt regional phenological model to predict the ﬂowering start and ﬂowering peak of Quercus species in the Iberian Peninsula by ascertaining whether potentially signiﬁcant genetic variations in the timing of ﬂowering required different phenological models or if, on the contrary, regional models for several localities can explain the variability detected in Quercus phenology in Spain. Model estimates did not vary greatly as a function of environment within similar climate areas where the same species grew; thus, model estimates of the temperature response of individuals growing in similar climate areas did not differ signiﬁcantly. The percentage of variance explained by models was greater in models ﬁtted with local data (75–97%). Nevertheless, acceptable results were also obtained using regional models (55–85%). The lowest value was found for the Simplifed Model including all Spanish sites together (51%).
Keywords: Aerobiology; Modelling; oak forest; Phenology; pollen; Quercus

Regional phenological models for forecasting the start and peak of the Quercus pollen season in Spain - García-Mozo, H.; Chuine, I.; Aira, M.J. J; Belmonte, J.; Bermejo, D.; Díaz de la Guardia, C.; Elvira, B.; Gutiérrez, M.; Rodríguez-Rajo, J.; Ruiz, L.; Trigo, M.M. M; Tormo, R.; et al. (Agricultural and Forest Meteorology, 2008)
he study sought to achieve the broadest possible spatial and temporal predictions by examining genetic variations in the timing of ﬂowering between populations of the Iberian Quercus species using pollen data from 15 sites in Spain. The speciﬁc objective of the study was to develop and ﬁt regional phenological model to predict the ﬂowering start and ﬂowering peak of Quercus species in the Iberian Peninsula by ascertaining whether potentially signiﬁcant genetic variations in the timing of ﬂowering required different phenological models or if, on the contrary, regional models for several localities can explain the variability detected in Quercus phenology in Spain. Model estimates did not vary greatly as a function of environment within similar climate areas where the same species grew; thus, model estimates of the temperature response of individuals growing in similar climate areas did not differ signiﬁcantly. The percentage of variance explained by models was greater in models ﬁtted with local data (75–97%). Nevertheless, acceptable results were also obtained using regional models (55–85%). The lowest value was found for the Simplifed Model including all Spanish sites together (51%).
Keywords: Aerobiology; Modelling; oak forest; Phenology; pollen; Quercus

Relationship between net photosynthesis and leaf respiration in Mediterranean evergreen species - Gratani, L; Varone, L; Catoni, R (Photosynthetica, 2008)
The relationship between net photosynthetic (PN) and leaf respiration (R) rates of Quercus ilex, Phillyrea latifolia, Myrtus communis, Arbutus unedo, and Cistus incanus was monitored in the period February 2006 to February 2007. The species investigated had low R and PN during winter, increasing from March to May, when mean air temperature reached 19.2 °C. During the favourable period, C. incanus and A. unedo had a higher mean PN (16.4±2.4 µmol m −2 s −1 ) than P. latifolia, Q. ilex, and M. communis (10.0±1.3 µmol m −2 s −1 ). The highest R (1.89±0.30 µmol m −2 s −1 , mean of the species), associated to a significant PN decrease (62 % of the maximum, mean value of the species), was measured in July (mean R/PN ratio 0.447±0.091). Q10, indicating the respiration sensitivity to short-term temperature increase, was in the range 1.49 to 2.21. Global change might modify R/PN determining differences in dry matter accumulation among the species, and Q. ilex and P. latifolia might be the most favoured species by their ability to maintain sufficiently higher PN and lower R during stress periods.
Keywords: arbutus; cistus; Myrtus; Phillyrea; Q10; Quercus; seasonal course; temperature.

Trace element accumulation in woody plants of the Guadiamar Valley, SW Spain: a large-scale phytomanagement case study. - Domínguez, María T; Marañón, Teodoro; Murillo, José M; Schulin, Rainer; Robinson, Brett H (Environmental pollution (Barking, Essex : 1987), 2008)
Phytomanagement employs vegetation and soil amendments to reduce the environmental risk posed by contaminated sites. We investigated the distribution of trace elements in soils and woody plants from a large phytomanaged site, the Guadiamar Valley (SW Spain), 7 years after a mine spill, which contaminated the area in 1998. At spill-affected sites, topsoils (0-25 cm) had elevated concentrations of As (129 mg kg(-1)), Bi (1.64 mg kg(-1)), Cd (1.44 mg kg(-1)), Cu (115 mg kg(-1)), Pb (210 mg kg(-1)), Sb (13.8 mg kg(-1)), Tl (1.17 mg kg(-1)) and Zn (457 mg kg(-1)). Trace element concentrations in the studied species were, on average, within the normal ranges for higher plants. An exception was white poplar (Populus alba), which accumulated Cd and Zn in leaves up to 3 and 410 mg kg(-1) respectively. We discuss the results with regard to the phytomanagement of trace element contaminated sites.
Keywords: Bioaccumulation; biodegradation; Environmental; Environmental Monitoring; Environmental Monitoring: methods; Heavy; Heavy metal; Heavy: analysis; Mass spectrometry; metals; Mining; Olea; Olea europaea; Olea: chemistry; Phytoremediation; Plant Leaves; Plant Leaves: chemistry; Populus; Populus alba; Populus: chemistry; Quercus; Quercus ilex; Quercus: chemistry; Soil; Soil Pollutants; Soil Pollutants: analysis; Soil: analysis; Spain; Species Specificity

Trace element accumulation in woody plants of the Guadiamar Valley, SW Spain: a large-scale phytomanagement case study. - Domínguez, María T.; Marañón, Teodoro; Murillo, José M.; Schulin, Rainer; Robinson, Brett H. (Environmental pollution (Barking, Essex : 1987), 2008)
Phytomanagement employs vegetation and soil amendments to reduce the environmental risk posed by contaminated sites. We investigated the distribution of trace elements in soils and woody plants from a large phytomanaged site, the Guadiamar Valley (SW Spain), 7 years after a mine spill, which contaminated the area in 1998. At spill-affected sites, topsoils (0-25 cm) had elevated concentrations of As (129 mg kg(-1)), Bi (1.64 mg kg(-1)), Cd (1.44 mg kg(-1)), Cu (115 mg kg(-1)), Pb (210 mg kg(-1)), Sb (13.8 mg kg(-1)), Tl (1.17 mg kg(-1)) and Zn (457 mg kg(-1)). Trace element concentrations in the studied species were, on average, within the normal ranges for higher plants. An exception was white poplar (Populus alba), which accumulated Cd and Zn in leaves up to 3 and 410 mg kg(-1) respectively. We discuss the results with regard to the phytomanagement of trace element contaminated sites.
The following values have no corresponding Zotero field: accession-num: 17602809
Keywords: Bioaccumulation; biodegradation; Environmental; Environmental Monitoring; Environmental Monitoring: methods; Heavy; Heavy metal; Heavy: analysis; Mass spectrometry; metals; Mining; Olea; Olea europaea; Olea: chemistry; Phytoremediation; Plant Leaves; Plant Leaves: chemistry; Populus; Populus alba; Populus: chemistry; Quercus; Quercus ilex; Quercus: chemistry; Soil; Soil Pollutants; Soil Pollutants: analysis; Soil: analysis; Spain; Species Specificity

The Cd(II)-binding abilities of recombinant Quercus suber metallothionein: bridging the gap between phytochelatins and metallothioneins. - Domenech, Jordi; Orihuela, Ruben; Mir, Gisela; Molinas, Marisa; Atrian, Silvia; Capdevila, Merce (Journal of biological inorganic chemistry : JBIC : a publication of the Society of Biological Inorganic Chemistry, 2007)
In this work, we have analyzed both at stoichiometric and at conformational level the Cd(II)-binding features of a type 2 plant metallothionein (MT) (the cork oak, Quercus suber, QsMT). To this end four peptides, the wild-type QsMT and three constructs previously engineered to characterize its Zn(II)- and Cu(I)-binding behaviour, were heterologously produced in Escherichia coli cultures supplemented with Cd(II), and the corresponding complexes were purified up to homogeneity. The Cd(II)-binding ability of these recombinant peptides was determined through the chemical, spectroscopic and spectrometric characterization of the recovered clusters. Recombinant synthesis of the four QsMT peptides in cadmium-rich media rendered complexes with a higher metal content than those obtained from zinc-supplemented cultures and, consequently, the recovered Cd(II) species are nonisostructural to those of Zn(II). Also of interest is the fact that three out of the four peptides yielded recombinant preparations that included S(2-)-containing Cd(II) complexes as major species. Subsequently, the in vitro Zn(II)/Cd(II) replacement reactions were studied, as well as the in vitro acid denaturation and S(2-) renaturation reactions. Finally, the capacity of the four peptides for preventing cadmium deleterious effects in yeast cells was tested through complementation assays. Consideration of all the results enables us to suggest a hairpin folding model for this typical type 2 plant Cd(II)-MT complex, as well as a nonnegligible role of the spacer in the detoxification function of QsMT towards cadmium.
Keywords: cadmium; Cadmium: chemistry; Cadmium–His binding; Drug; Glutathione; Metabolic Detoxication; metallothionein; Metallothionein: chemistry; Metallothionein: metabolism; Phytochelatins; Plant metallothionein; Plant Proteins; Plant Proteins: chemistry; Plant Proteins: metabolism; Protein Binding; Protein Conformation; Quercus; Recombinant Proteins; Sulfide ligands; yeast complementation

The Cd(II)-binding abilities of recombinant Quercus suber metallothionein: bridging the gap between phytochelatins and metallothioneins. - Domenech, Jordi; Orihuela, Ruben; Mir, Gisela; Molinas, Marisa; Atrian, Silvia; Capdevila, Merce (Journal of biological inorganic chemistry : JBIC : a publication of the Society of Biological Inorganic Chemistry, 2007)
In this work, we have analyzed both at stoichiometric and at conformational level the Cd(II)-binding features of a type 2 plant metallothionein (MT) (the cork oak, Quercus suber, QsMT). To this end four peptides, the wild-type QsMT and three constructs previously engineered to characterize its Zn(II)- and Cu(I)-binding behaviour, were heterologously produced in Escherichia coli cultures supplemented with Cd(II), and the corresponding complexes were purified up to homogeneity. The Cd(II)-binding ability of these recombinant peptides was determined through the chemical, spectroscopic and spectrometric characterization of the recovered clusters. Recombinant synthesis of the four QsMT peptides in cadmium-rich media rendered complexes with a higher metal content than those obtained from zinc-supplemented cultures and, consequently, the recovered Cd(II) species are nonisostructural to those of Zn(II). Also of interest is the fact that three out of the four peptides yielded recombinant preparations that included S(2-)-containing Cd(II) complexes as major species. Subsequently, the in vitro Zn(II)/Cd(II) replacement reactions were studied, as well as the in vitro acid denaturation and S(2-) renaturation reactions. Finally, the capacity of the four peptides for preventing cadmium deleterious effects in yeast cells was tested through complementation assays. Consideration of all the results enables us to suggest a hairpin folding model for this typical type 2 plant Cd(II)-MT complex, as well as a nonnegligible role of the spacer in the detoxification function of QsMT towards cadmium.
The following values have no corresponding Zotero field: accession-num: 17503092
Keywords: cadmium; Cadmium: chemistry; Cadmium–His binding; Drug; Glutathione; Metabolic Detoxication; metallothionein; Metallothionein: chemistry; Metallothionein: metabolism; Phytochelatins; Plant metallothionein; Plant Proteins; Plant Proteins: chemistry; Plant Proteins: metabolism; Protein Binding; Protein Conformation; Quercus; Recombinant Proteins; Sulfide ligands; yeast complementation

Flowering phenology of Mediterranean Quercus species in different locations (Córdoba, SW Iberian Peninsula) - Gómez-Casero, M T (Acta botánica malacitana, 2007)
Periodical qualitative and quantitative checking of flowering phases was carried out over six growing seasons (1997-2002) for the three Mediterranean Quercusspecies found in Sierra Morena (Córdoba, SW Spain): Q. ilex L. ssp. ballota (Desf.) Samp., Q. coccifera L. and Q. suber L. A total of 60 individuals were selected. Additionally, 30 Quercus ilex ssp. ballota individuals were selected and studied in Sierras Subbéticas (Priego de Córdoba, SW Spain) in 1999 and 2000. Morphological changes occurring at different points in each phenological phase were charted. Among species differences were found for inflorescences/male and female flowers, in terms of the phenological flowering sequence. Male inflorescences displayed a more homogeneous development. All individuals and populations were proterandrous. Phenological trends and ranges were charted. Although trends varied with species and year, the overall phenological trend seemed to fit a sigmoid curve in all cases, increasing with phenological development. Shorter ranges were obtained in years with warmer springs, and longer ranges in colder years. Moreover, phenological range differed as a function of species and location. In general, Q. ilex ssp. ballota flowered earlier than the rest, Q. suber displaying the latest flowering period. Individuals located at lower altitudes and facing the sun flowered earlier, followed in most years by those located at higher altitudes. Thus, Q. ilex ssp. ballota flowered earlier in Sierra Morena than in the higher-altitude Sierras Subbéticas.
Keywords: flowering; Quercus; range; reproductive phenology; tendency

Geophysical imaging of root-zone, trunk, and moisture heterogeneity - Attia Al Hagrey, Said (Journal of Experimental Botany, 2007)
The most significant biotic and abiotic stress agents of water extremity, salinity, and infection lead to wood decay and modifications of moisture and ion content, and density. This strongly influences the (di-)electrical and mechanical properties and justifies the application of geophysical imaging techniques. These are less invasive and have high resolution in contrast to classical methods of destructive, single-point measurements for inspecting stresses in trees and soils. This review presents some in situ and in vivo applications of electric, radar, and seismic methods for studying water status and movement in soils, roots, and tree trunks. The electrical properties of a root-zone are a consequence of their moisture content. Electrical imaging discriminates resistive, woody roots from conductive, soft roots. Both types are recognized by low radar velocities and high attenuation. Single roots can generate diffraction hyperbolas in radargrams. Pedophysical relationships of water content to electrical resistivity and radar velocity are established by diverse infiltration experiments in the field, laboratory, and in the full-scale ‘GeoModel’ at Kiel University. Subsurface moisture distributions are derived from geophysical attribute models. The ring electrode technique around trunks images the growth ring structure of concentric resistivity, which is inversely proportional to the fluid content. Healthy trees show a central high resistivity within the dry heartwood that strongly decreases towards the peripheral wet sapwood. Observed structural deviations are caused by infection, decay, shooting, or predominant light and/or wind directions. Seismic trunk tomography also differentiates between decayed and healthy woods.
10.1093/jxb/erl237
Keywords: Electric Impedance; Electrical resistivity techniques; Electrodes; Geological Phenomena; Geology; Plant Roots; Plant Roots: metabolism; Populus; Populus: physiology; Portugal; Quercus; Quercus: anatomy & histology; Quercus: metabolism; Radar; radar imaging; ring electrode array; root-zone; sap flow; seismic tomography; trunk ring structure; vadose zone; water; water content; water flow; Water: analysis; Water: metabolism

Geophysical imaging of root-zone, trunk, and moisture heterogeneity - Attia Al Hagrey, Said (Journal of Experimental Botany, 2007)
The most significant biotic and abiotic stress agents of water extremity, salinity, and infection lead to wood decay and modifications of moisture and ion content, and density. This strongly influences the (di-)electrical and mechanical properties and justifies the application of geophysical imaging techniques. These are less invasive and have high resolution in contrast to classical methods of destructive, single-point measurements for inspecting stresses in trees and soils. This review presents some in situ and in vivo applications of electric, radar, and seismic methods for studying water status and movement in soils, roots, and tree trunks. The electrical properties of a root-zone are a consequence of their moisture content. Electrical imaging discriminates resistive, woody roots from conductive, soft roots. Both types are recognized by low radar velocities and high attenuation. Single roots can generate diffraction hyperbolas in radargrams. Pedophysical relationships of water content to electrical resistivity and radar velocity are established by diverse infiltration experiments in the field, laboratory, and in the full-scale ‘GeoModel’ at Kiel University. Subsurface moisture distributions are derived from geophysical attribute models. The ring electrode technique around trunks images the growth ring structure of concentric resistivity, which is inversely proportional to the fluid content. Healthy trees show a central high resistivity within the dry heartwood that strongly decreases towards the peripheral wet sapwood. Observed structural deviations are caused by infection, decay, shooting, or predominant light and/or wind directions. Seismic trunk tomography also differentiates between decayed and healthy woods.
10.1093/jxb/erl23710.1093/jxb/erl237The following values have no corresponding Zotero field: accession-num: 17229759
Keywords: Electric Impedance; Electrical resistivity techniques; Electrodes; Geological Phenomena; Geology; Plant Roots; Plant Roots: metabolism; Populus; Populus: physiology; Portugal; Quercus; Quercus: anatomy & histology; Quercus: metabolism; Radar; radar imaging; ring electrode array; root-zone; sap flow; seismic tomography; trunk ring structure; vadose zone; water; water content; water flow; Water: analysis; Water: metabolism

Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I; Tomás-Barberán, Francisco a (Journal of Agricultural and Food Chemistry, 2007)
Ellagitannin-containing foods (strawberries, walnuts, pomegranate, raspberries, oak-aged wine, etc.) have attracted attention due to their cancer chemopreventive, cardioprotective, and antioxidant effects. Ellagitannins (ETs) are not absorbed as such but are metabolized by the intestinal flora to yield urolithins (hydroxydibenzopyran-6-one derivatives). In this study, Iberian pig is used as a model to clarify human ET metabolism. Pigs were fed either cereal fodder or acorns, a rich source of ETs. Plasma, urine, bile, lumen and intestinal tissues (jejunum and colon), feces, liver, kidney, heart, brain, lung, muscle, and subcutaneous fat tissue were analyzed. The results demonstrate that acorn ETs release ellagic acid (EA) in the jejunum, then the intestinal flora metabolizes EA sequentially to yield tetrahydroxy- (urolithin D), trihydroxy- (urolithin C), dihydroxy- (urolithin A), and monohydroxy- (urolithin B) dibenzopyran-6-one metabolites, which were absorbed preferentially when their lipophilicity increased. Thirty-one ET-derived metabolites were detected, including 25 urolithin and 6 EA derivatives. Twenty-six extensively conjugated metabolites were detected in bile, glucuronides and methyl glucuronides of EA and particularly urolithin A, C, and D derivatives, confirming a very active enterohepatic circulation. Urolithins A and B as well as dimethyl-EA-glucuronide were detected in peripheral plasma. The presence of EA metabolites in bile and in urine and its absence in intestinal tissues suggested its absorption in the stomach. Urolithin A was the only metabolite detected in feces and together with its glucuronide was the most abundant metabolite in urine. No metabolites accumulated in any organ analyzed. The whole metabolism of ETs is shown for the first time, confirming previous studies in humans and explaining the long persistency of urolithin metabolites in the body mediated by an active enterohepatic circulation.
From Duplicate 2 (Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I; Tomás-Barberán, Francisco A)
Keywords: Animal; Animals; bile; bioavailability; Biological Availability; Body Fluids; Body Fluids: chemistry; Cereals; Cereals: chemistry; colon; diet; ellagic acid; Ellagitannin; gall bladder; Humans; Hydrolyzable Tannins; Hydrolyzable Tannins: metabolism; Hydrolyzable Tannins: pharmacokinetics; intestine; metabolism; Models; Quercus; Seeds; Seeds: chemistry; Swine; Swine: metabolism; Tissue Distribution; urolithin

Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I.; Tomás-Barberán, Francisco a (Journal of Agricultural and Food Chemistry, 2007)
Ellagitannin-containing foods (strawberries, walnuts, pomegranate, raspberries, oak-aged wine, etc.) have attracted attention due to their cancer chemopreventive, cardioprotective, and antioxidant effects. Ellagitannins (ETs) are not absorbed as such but are metabolized by the intestinal flora to yield urolithins (hydroxydibenzopyran-6-one derivatives). In this study, Iberian pig is used as a model to clarify human ET metabolism. Pigs were fed either cereal fodder or acorns, a rich source of ETs. Plasma, urine, bile, lumen and intestinal tissues (jejunum and colon), feces, liver, kidney, heart, brain, lung, muscle, and subcutaneous fat tissue were analyzed. The results demonstrate that acorn ETs release ellagic acid (EA) in the jejunum, then the intestinal flora metabolizes EA sequentially to yield tetrahydroxy- (urolithin D), trihydroxy- (urolithin C), dihydroxy- (urolithin A), and monohydroxy- (urolithin B) dibenzopyran-6-one metabolites, which were absorbed preferentially when their lipophilicity increased. Thirty-one ET-derived metabolites were detected, including 25 urolithin and 6 EA derivatives. Twenty-six extensively conjugated metabolites were detected in bile, glucuronides and methyl glucuronides of EA and particularly urolithin A, C, and D derivatives, confirming a very active enterohepatic circulation. Urolithins A and B as well as dimethyl-EA-glucuronide were detected in peripheral plasma. The presence of EA metabolites in bile and in urine and its absence in intestinal tissues suggested its absorption in the stomach. Urolithin A was the only metabolite detected in feces and together with its glucuronide was the most abundant metabolite in urine. No metabolites accumulated in any organ analyzed. The whole metabolism of ETs is shown for the first time, confirming previous studies in humans and explaining the long persistency of urolithin metabolites in the body mediated by an active enterohepatic circulation.
From Duplicate 2 (Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I; Tomás-Barberán, Francisco A)From Duplicate 2 (Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I; Tomás-Barberán, Francisco A)The following values have no corresponding Zotero field: publisher: American Chemical Society accession-num: 17990850
Keywords: Animal; Animals; bile; bioavailability; Biological Availability; Body Fluids; Body Fluids: chemistry; Cereals; Cereals: chemistry; colon; diet; ellagic acid; Ellagitannin; gall bladder; Humans; Hydrolyzable Tannins; Hydrolyzable Tannins: metabolism; Hydrolyzable Tannins: pharmacokinetics; intestine; metabolism; Models; Quercus; Seeds; Seeds: chemistry; Swine; Swine: metabolism; Tissue Distribution; urolithin

Pattern recognition of acorns from different Quercus species based on oil content and fatty acid profile - Ferreira-Dias, Suzana; Valente, Dina G.; Abreu, José M.F. F (Grasas y Aceites, 2007)
The aim of this study was (i) to characterize different species of Quercus genus and (ii) to discriminate among them on the basis of the content and fatty acid composition of the oil in their fruits and/or their morphological aspects via pattern recognition techniques (Principal Component Analysis, PCA, Cluster Analysis, CA, and Discriminant Analysis, DA). Quercus rotundifolia Lam., Quercus suber L. and Quercus pyrenaica Willd., grown in the same stand in the centre of Portugal, were investigated. When oil content and respective fatty acid composition were used to characterize samples, well-separated groups corresponding to each of the species were observed by PCA and confirmed by CA and DA. The ‘‘width’’ and ‘‘length’’ of acorns exhibited a low discriminant power. Acorns from Q. rotundifolia showed the highest average oil content followed by Q. suber and Q. pyrenaica acorns (9.1, 5.2 and 3.8%, respectively). Fatty acid profiles of Q. rotundifolia and Q. suber oils are similar to olive oil while the oil from Q. pyrenaica acorns is more unsaturated
Keywords: acorn; cluster analysis; Discriminant analysis; Oil; Principal component analysis; Quercus

Pattern recognition of acorns from different Quercus species based on oil content and fatty acid profile - Ferreira-Dias, Suzana; Valente, Dina G.; Abreu, José M. F. F. (Grasas y Aceites, 2007)
The aim of this study was (i) to characterize different species of Quercus genus and (ii) to discriminate among them on the basis of the content and fatty acid composition of the oil in their fruits and/or their morphological aspects via pattern recognition techniques (Principal Component Analysis, PCA, Cluster Analysis, CA, and Discriminant Analysis, DA). Quercus rotundifolia Lam., Quercus suber L. and Quercus pyrenaica Willd., grown in the same stand in the centre of Portugal, were investigated. When oil content and respective fatty acid composition were used to characterize samples, well-separated groups corresponding to each of the species were observed by PCA and confirmed by CA and DA. The ‘‘width’’ and ‘‘length’’ of acorns exhibited a low discriminant power. Acorns from Q. rotundifolia showed the highest average oil content followed by Q. suber and Q. pyrenaica acorns (9.1, 5.2 and 3.8%, respectively). Fatty acid profiles of Q. rotundifolia and Q. suber oils are similar to olive oil while the oil from Q. pyrenaica acorns is more unsaturated
Keywords: acorn; cluster analysis; Discriminant analysis; Oil; Principal component analysis; Quercus

Predictive modelling of tree species distributions on the Iberian Peninsula during the Last Glacial Maximum and Mid-Holocene - Benito Garzón, Marta; Sánchez de Dios, Rut; Sainz Ollero, Helios (Ecography, 2007)
This paper reports a bioclimatic envelope model study of the potential distribution of 19 tree species in the Iberian Peninsula during the Last Glacial Maximum (LGM; 21 000 yr BP) and the Mid-Holocene (6000 yr BP). Current patterns of tree species richness and distributions are believed to have been strongly influenced by the climate during these periods. The modelling employed novel machine learning techniques, and its accuracy was evaluated using a threshold-independent method. Two atmospheric general circulation models, UGAMP and ECHAM3 (generated by the Palaeoclimate Modelling Intercomparison Project, PMIP), were used to provide climate scenarios under which the distributions of the 19 tree species were modelled. The results obtained for these scenarios were assessed by agreement measure analysis; they differed significantly for the LGM, but were more similar for the Mid-Holocene. The results for the LGM support the inferred importance of pines in the Iberian Peninsula at this time, and the presence of evergreen Quercus in the south. Important differences in the altitude at which the modelled species grew were also predicted. During the LGM, some normally higher mountain species potentially became re-established in the foothills of the Pyrenees. The warm Mid-Holocene climate is clearly reflected in the predicted expansion of broad-leaved forests during this period, including the colonization of the northern part of the Iberian Peninsula by evergreen Quercus species.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: climate scenarios; iberian peninsula; Pinus; Quercus; refugia (voyant); species distribution modelling

Predictive modelling of tree species distributions on the Iberian Peninsula during the Last Glacial Maximum and Mid-Holocene - Benito Garzón, Marta; Sánchez de Dios, Rut; Sainz Ollero, Helios (Ecography, 2007)
This paper reports a bioclimatic envelope model study of the potential distribution of 19 tree species in the Iberian Peninsula during the Last Glacial Maximum (LGM; 21 000 yr BP) and the Mid-Holocene (6000 yr BP). Current patterns of tree species richness and distributions are believed to have been strongly influenced by the climate during these periods. The modelling employed novel machine learning techniques, and its accuracy was evaluated using a threshold-independent method. Two atmospheric general circulation models, UGAMP and ECHAM3 (generated by the Palaeoclimate Modelling Intercomparison Project, PMIP), were used to provide climate scenarios under which the distributions of the 19 tree species were modelled. The results obtained for these scenarios were assessed by agreement measure analysis; they differed significantly for the LGM, but were more similar for the Mid-Holocene. The results for the LGM support the inferred importance of pines in the Iberian Peninsula at this time, and the presence of evergreen Quercus in the south. Important differences in the altitude at which the modelled species grew were also predicted. During the LGM, some normally higher mountain species potentially became re-established in the foothills of the Pyrenees. The warm Mid-Holocene climate is clearly reflected in the predicted expansion of broad-leaved forests during this period, including the colonization of the northern part of the Iberian Peninsula by evergreen Quercus species.
Keywords: climate scenarios; iberian peninsula; Pinus; Quercus; refugia (voyant); species distribution modelling

Producción de bellota en la dehesa: factores influyentes - Rodríguez-Estévez, V; García, A; Perea, J; Mata, C; Gómez, A G (Arch. Zootec, 2007)
This paper reviews the state-of-the- knowledge of acorn production in the South- Western Iberian dehesas. In the first part are briefly described the soil and climatic determining factors and phenology of most common trees of genus Quercus at the dehesa (Q. ilex, Q. suber and Q. faginea). In the second part, acorn production estimations are analyzed. Was established a mean acorn yield of 300 to 700 kg/ ha; with individual productions of 8-14 kg/tree for Q. ilex, 5-10 kg/tree for Q. suber and 1-11 kg/ tree for Q. faginea; with a highly variable production, both between and within years and individual trees. Finally we review the factors affecting acorn production, describing density of trees (estimated in 20-50 trees/ha), masting phenomenon (with cycles of 2-5,5 years and asynchrony between trees), individual cha- racteristics of trees (genetic potential, age, top surface, etc.), tree mass handling (with favourable effect of tilling, moderate pruning and sustainable grazing), meteorological conditions (mainly drought and meteorology during flowering) and sanitary status (Lymantria, Tortrix, Curculio, Cydia, Balaninus and Brenneria).
Keywords: Agro forestry system; evergreen oak; iberian pig; Mast-seeding; Montanera; Quercus

Producción de bellota en la dehesa: factores influyentes - Rodríguez-Estévez, V.; García, A.; Perea, J.; Mata, C.; Gómez, A. G. (Arch. Zootec, 2007)
This paper reviews the state-of-the- knowledge of acorn production in the South- Western Iberian dehesas. In the first part are briefly described the soil and climatic determining factors and phenology of most common trees of genus Quercus at the dehesa (Q. ilex, Q. suber and Q. faginea). In the second part, acorn production estimations are analyzed. Was established a mean acorn yield of 300 to 700 kg/ ha; with individual productions of 8-14 kg/tree for Q. ilex, 5-10 kg/tree for Q. suber and 1-11 kg/ tree for Q. faginea; with a highly variable production, both between and within years and individual trees. Finally we review the factors affecting acorn production, describing density of trees (estimated in 20-50 trees/ha), masting phenomenon (with cycles of 2-5,5 years and asynchrony between trees), individual cha- racteristics of trees (genetic potential, age, top surface, etc.), tree mass handling (with favourable effect of tilling, moderate pruning and sustainable grazing), meteorological conditions (mainly drought and meteorology during flowering) and sanitary status (Lymantria, Tortrix, Curculio, Cydia, Balaninus and Brenneria).
Keywords: Agro forestry system; evergreen oak; iberian pig; Mast-seeding; Montanera; Quercus

SEED - MASS EFFECTS IN FOUR MEDITERRANEAN QUERCUS SPECIES (FAGACEAE ) GROWING IN CONTRASTING LIGHT ENVIRONMENTS - Quero, José Luis; Villar, Rafael; Marañón, Teodoro; Zamora, Regino; Poorter, Lourens (American Journal of Botany 94(11):, 2007)
Three hypotheses have been proposed to explain the functional relationship between seed mass and seedling performance: the reserve effect (larger seeds retain a larger proportion of reserves after germinating), the metabolic effect (seedlings from larger seeds have slower relative growth rates), and the seedling-size effect (larger seeds produce larger seedlings). We tested these hypotheses by growing four Mediterranean Quercus species under different light conditions (3, 27, and 100% of available radiation). We found evidence for two of the three hypotheses, but none of the four species complied with all three hypotheses at the same time. The reserve effect was not found in any species, the metabolic effect was found in three species (Q. ilex, Q. pyrenaica, and Q. suber), and the seedling-size effect in all species. Light availability significantly affected the relationships between seed size and seedling traits. For Q. ilex and Q. canariensis, a seedling-size effect was found under all three light conditions, but only under the lowest light (3%) for Q. suber and Q. pyrenaica. In all species, the correlation between seed mass and seedling mass increased with a decrease in light, suggesting that seedlings growing in low light depend more upon their seed reserves. A causal model integrates the three hypotheses, suggesting that larger seeds generally produced larger seedlings.
From Duplicate 2 ( SEED - MASS EFFECTS IN FOUR MEDITERRANEAN QUERCUS SPECIES (FAGACEAE ) GROWING IN CONTRASTING LIGHT ENVIRONMENTS - Environments, Contrasting Light; Uero, L U I S Q; Illar, R Afael V; Aran, T Eodoro M; Oorter, L Ourens P; Ciencias, Facultad De; Granada, Universidad De; Ecologı, A De )
Keywords: acornmass; Fagaceae; light availability; mediterranean oaks; Quercus; RGR; Seed size; seed–seedling relationships

SEED - MASS EFFECTS IN FOUR MEDITERRANEAN QUERCUS SPECIES (FAGACEAE ) GROWING IN CONTRASTING LIGHT ENVIRONMENTS - Quero, José Luis; Villar, Rafael; Marañón, Teodoro; Zamora, Regino; Poorter, Lourens (American Journal of Botany 94(11):, 2007)
Three hypotheses have been proposed to explain the functional relationship between seed mass and seedling performance: the reserve effect (larger seeds retain a larger proportion of reserves after germinating), the metabolic effect (seedlings from larger seeds have slower relative growth rates), and the seedling-size effect (larger seeds produce larger seedlings). We tested these hypotheses by growing four Mediterranean Quercus species under different light conditions (3, 27, and 100% of available radiation). We found evidence for two of the three hypotheses, but none of the four species complied with all three hypotheses at the same time. The reserve effect was not found in any species, the metabolic effect was found in three species (Q. ilex, Q. pyrenaica, and Q. suber), and the seedling-size effect in all species. Light availability significantly affected the relationships between seed size and seedling traits. For Q. ilex and Q. canariensis, a seedling-size effect was found under all three light conditions, but only under the lowest light (3%) for Q. suber and Q. pyrenaica. In all species, the correlation between seed mass and seedling mass increased with a decrease in light, suggesting that seedlings growing in low light depend more upon their seed reserves. A causal model integrates the three hypotheses, suggesting that larger seeds generally produced larger seedlings.
From Duplicate 2 ( SEED - MASS EFFECTS IN FOUR MEDITERRANEAN QUERCUS SPECIES (FAGACEAE ) GROWING IN CONTRASTING LIGHT ENVIRONMENTS - Environments, Contrasting Light; Uero, L U I S Q; Illar, R Afael V; Aran, T Eodoro M; Oorter, L Ourens P; Ciencias, Facultad De; Granada, Universidad De; Ecologı, A De )From Duplicate 2 ( SEED - MASS EFFECTS IN FOUR MEDITERRANEAN QUERCUS SPECIES (FAGACEAE ) GROWING IN CONTRASTING LIGHT ENVIRONMENTS - Environments, Contrasting Light; Uero, L U I S Q; Illar, R Afael V; Aran, T Eodoro M; Oorter, L Ourens P; Ciencias, Facultad De; Granada, Universidad De; Ecologı, A De )
Keywords: acornmass; Fagaceae; light availability; mediterranean oaks; Quercus; RGR; Seed size; seed–seedling relationships

Sensitivity of volatile monoterpene emission to changes in canopy structure: a model-based exercise with a process-based emission model - Grote, Rüdiger (New Phytologist, 2007)
* • This paper investigates the dependence of monoterpene emissions at the canopy scale on total leaf area and leaf distribution. Simulations were carried out for a range of hypothetical but realistic forest canopies of the evergreen Quercus ilex (holm oak). * • Two emission models were applied that either did (SIM-BIM2) or did not (G93) account for cumulative responses to temperature and light. Both were embedded into a canopy model that considered spatial and temporal variations of foliage properties. This canopy model was coupled to a canopy climate model (CANOAK) to determine the micrometeorological conditions at the leaf scale. * • Structural properties considerably impacted monoterpene emission. The sensitivities to changes in total leaf area and to leaf area distribution were found to be of similar magnitude. The two different models performed similarly on a whole-year basis but showed clear differences during certain episodes. * • The analysis showed that structural indices have to be carefully evaluated for proper scaling of emission from leaves to canopy. Further research is encouraged on seasonal dynamics of emission potentials.
Keywords: Biological; biomass; foliage distribution; leaf area index; light; Models; monoterpene emission; Monoterpenes; Monoterpenes: metabolism; photosynthesis; Photosynthesis: radiation effects; Plant Leaves; Plant Leaves: metabolism; Plant Leaves: radiation effects; Quercus; Quercus ilex; Quercus: metabolism; Quercus: radiation effects; Scaling; stand density; Temperature; Time Factors; Volatilization

Use of Quercus ilex subsp. ballota phenological and pollen-production data for interpreting Quercus pollen curves - Jato, V; Rodríguez-Rajo, F J; Aira, M J (Aerobiologia, 2007)
Although aerobiological data are often used in phenological research as an indicator of ﬂowering, airborne pollen concentrations are inﬂuenced by a number of factors that could affect pollen curves. This paper reports on a study of various aspects of reproductive biology in Q. ilex subsp. ballota, together with environmental factors inﬂuencing pollen release and transport, with a view of achieving reliable interpretation of Quercus pollen curves in Ourense (NW Spain). Aerobiological data were recorded from 2002 to 2004 at two sites in the province of Ourense. From 1st February to the end of the ﬂowering period, phenological observations were carried out on 19 trees from the Q. ilex subsp. ballota population found in the Ourense area. Pollen production was calculated for the same trees. The chilling and heating requirements for triggering development were also calculated. The mean ﬂowering period lasted 11-15 days. Reduced pollen output per catkin and, especially, a reduced number of catkins per tree in 2003 and 2004, prompted a marked decline in overall pollen production. Major differences observed in Q. ilex subsp. ballota pollen curves were attributed to the considerable inﬂuence both of weather conditions during pollination and pollen production. In years with high pollen production and weather conditions favouring pollen release, Q. ilex subsp. ballota contributed almost 10% to the total Quercus pollen curve. Around 20% of the pollen trapped was captured before or after ﬂowering periods.
Keywords: airborne pollen; Phenology; pollen production; Quercus

Dynamics of the enhanced emissions of monoterpenes and methyl salicylate, and decreased uptake of formaldehyde, by Quercus ilex leaves after application of jasmonic acid - Filella, Iolanda; Penuelas, Josep; Llusia, Joan (New Phytologist, 2006)
* • Jasmonic acid (JA) is a signalling compound with a key role in both stress and development in plants, and is reported to elicit the emission of volatile organic compounds (VOCs). Here we studied the dynamics of such emissions and the linkage with photosynthetic rates and stomatal conductance. * • We sprayed JA on leaves of the Mediterranean tree species Quercus ilex and measured the photosynthetic rates, stomatal conductances, and emissions and uptake of VOCs using proton transfer reaction mass spectrometry and gas chromatography after a dark–light transition. * • Jasmonic acid treatment delayed the induction of photosynthesis and stomatal conductance by approx. 20 min, and decreased them 24 h after spraying. Indications were found of both stomatal and nonstomatal limitations of photosynthesis. Monoterpene emissions were enhanced (20–30%) after JA spraying. Jasmonic acid also increased methyl salicylate (MeSa) emissions (more than twofold) 1 h after treatment, although after 24 h this effect had disappeared. Formaldehyde foliar uptake decreased significantly 24 h after JA treatment. * • Both biotic and abiotic stresses can thus affect plant VOC emissions through their strong impact on JA levels. Jasmonic acid-mediated increases in monoterpene and MeSa emissions might have a protective role when confronting biotic and abiotic stresses.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd accession-num: 16390425
Keywords: Carbon dioxide; Carbon Dioxide: metabolism; Cyclopentanes; Cyclopentanes: pharmacology; Dehydration; Formaldehyde; Formaldehyde: metabolism; jasmonic acid (JA); light; methyl salicylate; Monoterpenes; Monoterpenes: metabolism; net photosynthetic rates; Oxylipins; photosynthesis; Plant Leaves; Plant Leaves: drug effects; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: drug effects; Quercus: metabolism; Salicylates; Salicylates: metabolism; Stomatal conductance; Temperature; VOC (volatile organic compound)

Dynamics of the enhanced emissions of monoterpenes and methyl salicylate, and decreased uptake of formaldehyde, by Quercus ilex leaves after application of jasmonic acid - Filella, Iolanda; Penuelas, Josep; Llusia, Joan (New Phytologist, 2006)
* • Jasmonic acid (JA) is a signalling compound with a key role in both stress and development in plants, and is reported to elicit the emission of volatile organic compounds (VOCs). Here we studied the dynamics of such emissions and the linkage with photosynthetic rates and stomatal conductance. * • We sprayed JA on leaves of the Mediterranean tree species Quercus ilex and measured the photosynthetic rates, stomatal conductances, and emissions and uptake of VOCs using proton transfer reaction mass spectrometry and gas chromatography after a dark–light transition. * • Jasmonic acid treatment delayed the induction of photosynthesis and stomatal conductance by approx. 20 min, and decreased them 24 h after spraying. Indications were found of both stomatal and nonstomatal limitations of photosynthesis. Monoterpene emissions were enhanced (20–30%) after JA spraying. Jasmonic acid also increased methyl salicylate (MeSa) emissions (more than twofold) 1 h after treatment, although after 24 h this effect had disappeared. Formaldehyde foliar uptake decreased significantly 24 h after JA treatment. * • Both biotic and abiotic stresses can thus affect plant VOC emissions through their strong impact on JA levels. Jasmonic acid-mediated increases in monoterpene and MeSa emissions might have a protective role when confronting biotic and abiotic stresses.
Keywords: Carbon dioxide; Carbon Dioxide: metabolism; Cyclopentanes; Cyclopentanes: pharmacology; Dehydration; Formaldehyde; Formaldehyde: metabolism; jasmonic acid (JA); light; methyl salicylate; Monoterpenes; Monoterpenes: metabolism; net photosynthetic rates; Oxylipins; photosynthesis; Plant Leaves; Plant Leaves: drug effects; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: drug effects; Quercus: metabolism; Salicylates; Salicylates: metabolism; Stomatal conductance; Temperature; VOC (volatile organic compound)

Evaluation of holm oak (Quercus ilex) wood as alternative source for cellulose pulp - Eugenio, M. E.; Alaejos, J.; Diaz, M. J.; López, F.; Vidal, T. (CELLULOSE CHEMISTRY AND TECHNOLOGY, 2006)
Preservation of forests and increasing environmental awareness have focused research on the exploration of alternative resources for papermaking, a possible source being holm oak wood. The paper reports on the influence of some independent variables in the soda pulping of holm, oak wood \{[\}viz., temperature (135-195 degrees C), operation time (30-90 min) and active alkali concentration (10-20\%)] on the yield, hollocelulose, alpha-cellulose and lignin content, brightness, viscosity and kappa index of the pulps considered. By using a central, composite, factorial design, equations relating each dependent variable to different independent variables were derived, reproducing the experimental results for the dependent variables with errors below 10%. High pulp yield values were obtained under low operating variable conditions. To obtain the best results in brightness, viscosity and kappa index, operation under high values of the independent variables, the kappa index excepted, is necessary. To obtain a suitable value for this parameter, operation at low temperature is recommended. By applying TCF bleaching (A(1)OA(2)ZRP) in pulps obtained under extreme and central conditions of the pulping process, better values for kappa index (3.4) and brightness (83.8 ISO) result for the pulp obtained under maximum operating conditions. Nevertheless, considerable viscosity losses occur under Such conditions.
The following values have no corresponding Zotero field: pub-location: CALEA 13 SEPTEMBRIE NR 13, SECTOR 5, BUCHAREST RO-76117, ROMANIA publisher: EDITURA ACADEMIEI ROMANE
Keywords: Forestry residues; pulp; Quercus; soda pulp; Wood

Evaluation of holm oak (Quercus ilex) wood as alternative source for cellulose pulp - Eugenio, M E; Alaejos, J; Diaz, M J; Lopez, F; Vidal, T (CELLULOSE CHEMISTRY AND TECHNOLOGY, 2006)
Preservation of forests and increasing environmental awareness have focused research on the exploration of alternative resources for papermaking, a possible source being holm oak wood. The paper reports on the influence of some independent variables in the soda pulping of holm, oak wood \{[\}viz., temperature (135-195 degrees C), operation time (30-90 min) and active alkali concentration (10-20\%)] on the yield, hollocelulose, alpha-cellulose and lignin content, brightness, viscosity and kappa index of the pulps considered. By using a central, composite, factorial design, equations relating each dependent variable to different independent variables were derived, reproducing the experimental results for the dependent variables with errors below 10%. High pulp yield values were obtained under low operating variable conditions. To obtain the best results in brightness, viscosity and kappa index, operation under high values of the independent variables, the kappa index excepted, is necessary. To obtain a suitable value for this parameter, operation at low temperature is recommended. By applying TCF bleaching (A(1)OA(2)ZRP) in pulps obtained under extreme and central conditions of the pulping process, better values for kappa index (3.4) and brightness (83.8 ISO) result for the pulp obtained under maximum operating conditions. Nevertheless, considerable viscosity losses occur under Such conditions.
Keywords: Forestry residues; pulp; Quercus; soda pulp; Wood

Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor (Tree Physiology, 2006)
Shade and irrigation are frequently used to increase the success of Mediterranean Quercus spp. plantations. However, there is controversy about the combined effects of these treatments on plant performance. We assessed the effects of two irradiances (full sunlight and moderate shade) and two summer watering regimes (high (daily) and low (alternate days)) on leaf and whole-plant traits of 1-year-old seedlings of Quercus coccifera, Q. ilex subsp. ballota and Q. faginea grown outdoors for 8.5 months. Leaf traits included measures of morphology, nitrogen concentration, gas exchange and photochemical efficiency, and measures of whole-plant traits included biomass allocation patterns, growth phenology, across-summer leaf area change and relative growth rate (RGR).Moderate shade reduced leaf mass per area, increased photochemical efficiency, maximum carbon assimilation rate (Amax) and allocation to leaves, and prolonged the growing period in one or more of the species. Daily watering in summer increased Amax of Q. ilex and prolonged the growing period of Q. ilex and Q. faginea. Both treatments tended to increase RGR. The effect of shade was greater in the low-watering regime than in the high-watering regime for two of the 15 studied traits, with treatment effects being independent for the remaining 13 traits. Leaf nitrogen and the ability to maintain leaf area after the arid period, rather than biomass allocation traits, explained the variation in seedling RGR. Trait responsiveness to the treatments was low and similar among species and between study scales, being unexpectedly low in Q. faginea leaves. This may be because selective pressures on leaf plasticity act differently in deciduous and evergreen species. We conclude that moderate shade and daily summer watering enhance the performance of Mediterranean Quercus seedlings through species-specific mechanisms.
From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)
Keywords: Agriculture; Agriculture: methods; Analysis of Variance; biomass allocation; carbon assimilation rate; fluorescence; Mediterranean Region; Phenology; Phenotype; Plant Leaves; Plant Leaves: growth & development; Plant Shoots; Plant Shoots: physiology; Quercus; Quercus: drug effects; Quercus: growth & development; Quercus: physiology; Relative growth rate; Seedling; Seedling: drug effects; Seedling: physiology; water; Water: metabolism; Water: pharmacology

Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G.; Maestro, Melchor (Tree Physiology, 2006)
Shade and irrigation are frequently used to increase the success of Mediterranean Quercus spp. plantations. However, there is controversy about the combined effects of these treatments on plant performance. We assessed the effects of two irradiances (full sunlight and moderate shade) and two summer watering regimes (high (daily) and low (alternate days)) on leaf and whole-plant traits of 1-year-old seedlings of Quercus coccifera, Q. ilex subsp. ballota and Q. faginea grown outdoors for 8.5 months. Leaf traits included measures of morphology, nitrogen concentration, gas exchange and photochemical efficiency, and measures of whole-plant traits included biomass allocation patterns, growth phenology, across-summer leaf area change and relative growth rate (RGR).Moderate shade reduced leaf mass per area, increased photochemical efficiency, maximum carbon assimilation rate (Amax) and allocation to leaves, and prolonged the growing period in one or more of the species. Daily watering in summer increased Amax of Q. ilex and prolonged the growing period of Q. ilex and Q. faginea. Both treatments tended to increase RGR. The effect of shade was greater in the low-watering regime than in the high-watering regime for two of the 15 studied traits, with treatment effects being independent for the remaining 13 traits. Leaf nitrogen and the ability to maintain leaf area after the arid period, rather than biomass allocation traits, explained the variation in seedling RGR. Trait responsiveness to the treatments was low and similar among species and between study scales, being unexpectedly low in Q. faginea leaves. This may be because selective pressures on leaf plasticity act differently in deciduous and evergreen species. We conclude that moderate shade and daily summer watering enhance the performance of Mediterranean Quercus seedlings through species-specific mechanisms.
From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)The following values have no corresponding Zotero field: accession-num: 16356909
Keywords: Agriculture; Agriculture: methods; Analysis of Variance; biomass allocation; carbon assimilation rate; fluorescence; Mediterranean Region; Phenology; Phenotype; Plant Leaves; Plant Leaves: growth & development; Plant Shoots; Plant Shoots: physiology; Quercus; Quercus: drug effects; Quercus: growth & development; Quercus: physiology; Relative growth rate; Seedling; Seedling: drug effects; Seedling: physiology; water; Water: metabolism; Water: pharmacology

Introduction of the factor of partitioning in the lithogenic enrichment factors of trace element bioaccumulation in plant tissues. - Sardans, Jordi; Penuelas, Josep (Environmental monitoring and assessment, 2006)
Bioindicators are widely used in the study of trace elements inputs into the environment and great efforts have been conducted to separate atmospheric from soil borne inputs on biomass accumulation. Many monitoring studies of trace element pollution take into account the dust particles located in the plant surface plus the contents of the plant tissues. However, it is usually only the trace element content in the plant tissues that is relevant on plant health. Enrichment factor equations take into account the trace element enrichment of biomasses with respect soil or bedrocks by comparing the ratios of the trace element in question to a lithogenic element, usually Al. However, the enrichment equations currently in use are inadequate because they do not take into account the fact that Al (or whichever reference element) and the element in question may have different solubility-absorption-retention levels depending on the rock and soil types involved. This constrain will become critical when results from different sites are compared and so in this article we propose that the solubility factors of each element are taken into account in order to overcome this constrain. We analysed Sb, Co, Ni, Cr, Pb, Cd, Mn, V, Zn, Cu, As, Hg, and Al concentration in different zones of Catalonia (NE Spain) using the evergreen oak Quercus ilex and the moss Hypnum cupressiforme as target species. We compared the results obtained in rural and non industrial areas with those from the Barcelona Metropolitan Area. We observed differences in Al concentrations of soils and bedrocks at each different site, together with the differences in solubility between Al and the element in question, and a weak correlation between total soil content and water extract content through different sites for most trace elements. All these findings show the unsuitability of the current enrichment factors for calculating lithospheric and atmospheric contributions to trace element concentrations in biomass tissues. The trace element enrichment factors were calculated by subtracting the part predicted by substrate composition (deduced from water extracts from soils and bedrock) from total concentrations. Results showed that for most of the trace elements analysed, trace elements enrichment factors were higher inside the Barcelona Metropolitan Area than outside, a finding that indicates that greater atmospheric inputs occur in urban areas. The results show that the most useful and correct way of establishing a reference for lithospheric and atmospheric inputs into the plant tissues is, first, to analyse samples of the same plant species collected from a number of sites possessing similar environmental conditions (climate, vegetation type, soil type) and, second, to use this new enrichment factor obtained by subtracting from the total concentration in plant tissue the predicted contribution of soil or bedrock extracts instead of that of total soil or bedrock concentrations.
The following values have no corresponding Zotero field: accession-num: 16648953
Keywords: biomass; Bryopsida; Bryopsida: chemistry; Bryopsida: growth & development; Environmental Monitoring; Environmental Monitoring: methods; Plant Leaves; Plant Leaves: chemistry; Plant Leaves: growth & development; Quercus; Quercus: chemistry; Quercus: growth & development; Soil Pollutants; Soil Pollutants: analysis; Spain; Trace Elements; Trace Elements: analysis

Introduction of the factor of partitioning in the lithogenic enrichment factors of trace element bioaccumulation in plant tissues. - Sardans, Jordi; Penuelas, Josep (Environmental monitoring and assessment, 2006)
Bioindicators are widely used in the study of trace elements inputs into the environment and great efforts have been conducted to separate atmospheric from soil borne inputs on biomass accumulation. Many monitoring studies of trace element pollution take into account the dust particles located in the plant surface plus the contents of the plant tissues. However, it is usually only the trace element content in the plant tissues that is relevant on plant health. Enrichment factor equations take into account the trace element enrichment of biomasses with respect soil or bedrocks by comparing the ratios of the trace element in question to a lithogenic element, usually Al. However, the enrichment equations currently in use are inadequate because they do not take into account the fact that Al (or whichever reference element) and the element in question may have different solubility-absorption-retention levels depending on the rock and soil types involved. This constrain will become critical when results from different sites are compared and so in this article we propose that the solubility factors of each element are taken into account in order to overcome this constrain. We analysed Sb, Co, Ni, Cr, Pb, Cd, Mn, V, Zn, Cu, As, Hg, and Al concentration in different zones of Catalonia (NE Spain) using the evergreen oak Quercus ilex and the moss Hypnum cupressiforme as target species. We compared the results obtained in rural and non industrial areas with those from the Barcelona Metropolitan Area. We observed differences in Al concentrations of soils and bedrocks at each different site, together with the differences in solubility between Al and the element in question, and a weak correlation between total soil content and water extract content through different sites for most trace elements. All these findings show the unsuitability of the current enrichment factors for calculating lithospheric and atmospheric contributions to trace element concentrations in biomass tissues. The trace element enrichment factors were calculated by subtracting the part predicted by substrate composition (deduced from water extracts from soils and bedrock) from total concentrations. Results showed that for most of the trace elements analysed, trace elements enrichment factors were higher inside the Barcelona Metropolitan Area than outside, a finding that indicates that greater atmospheric inputs occur in urban areas. The results show that the most useful and correct way of establishing a reference for lithospheric and atmospheric inputs into the plant tissues is, first, to analyse samples of the same plant species collected from a number of sites possessing similar environmental conditions (climate, vegetation type, soil type) and, second, to use this new enrichment factor obtained by subtracting from the total concentration in plant tissue the predicted contribution of soil or bedrock extracts instead of that of total soil or bedrock concentrations.
Keywords: biomass; Bryopsida; Bryopsida: chemistry; Bryopsida: growth & development; Environmental Monitoring; Environmental Monitoring: methods; Plant Leaves; Plant Leaves: chemistry; Plant Leaves: growth & development; Quercus; Quercus: chemistry; Quercus: growth & development; Soil Pollutants; Soil Pollutants: analysis; Spain; Trace Elements; Trace Elements: analysis

Long-time variations in leaf mass and area of Mediterranean evergreen broad-leaf and narrow-leaf maquis species - Gratani, L; Varone, L (Photosynthetica, 2006)
Morphological (dry mass, DM; surface area, LA; leaf mass per area, LMA), anatomical (leaf thickness, L), phenological (leaf life span, LL), and physiological (net photosynthetic rate, PN) leaf traits of the evergreen species co-occurring in the Mediterranean maquis developing at Castelporziano (Rome) were tested. The correlation analysis indicated that LMA variation was tightly associated with LL variations: Cistus incanus and Arbutus unedo had a short LL (4±1, summer leaves, and 11±1 months, respectively) and low LMA (153±19 g m –2 ) values, Quercus ilex, Phillyrea latifolia, and Pistacia lentiscus high LMA (204±7 g m –2 ) and long LL (22±3 months), Erica arborea, Erica multiflora, and Rosmarinus officinalis a short LL (9±2 months) and an either high (213±29 g m –2 , R. officinalis and E. multiflora) or low (115±17 g m –2 , E. arborea) LMA. LMA values were significantly (p≤0.05) correlated with PN (r≥0.68). In the tested species, LMA increased in response to the decrease of the total rainfall during the leaf expansion period. LMA variation was due to the unequal variation of DM and LA in the considered species. LMA is thus a good indicator of evergreen maquis species capability to respond to climate change, in particular to total rainfall decrease in the Mediterranean basin.
Keywords: dry mass; Erica; leaf life span; Leaf mass per area; Phillyrea; Pistacia; Quercus; RAINFALL; Rosmarinus.

Satiation of predispersal seed predators: the importance of considering both plant and seed levels - Bonal, Raul; Muñoz, Alberto; Díaz, Mario (Evolutionary Ecology, 2006)
Plants can reduce the ﬁtness costs of granivory by satiating seed predators. The most common satiation mechanism is the production of large crops, which ensures that a proportion of the seeds survive predation. Nevertheless, satiation of small granivores at the seed level may also exist. Larger seeds would satiate more efﬁciently, enhancing the probability of seed survival after having been attacked. However, a larger seed size could compromise the efﬁciency of satiation by means of large crops if there were a negative relationship between seed size and the number of seeds produced by an individual plant. We analyze both types of satiation in the interaction between the holm oak Quercus ilex and the chestnut weevil Curculio elephas. Both crop size and acorn size differed strongly in a sample of 32 trees. Larger crop sizes satiated weevils, and higher proportions of the seeds were not attacked as crop size increased. Larger seeds also satiated weevil larvae, as a larger acorn size increased the likelihood of embryo survival. Seedling size was strongly related to acorn size and was reduced by weevil attack, but seedlings coming from large weeviled acorns were still larger. The number and the size of the acorns produced by individual trees were negatively related. Larger proportions of the crop were infested in oaks producing less numerous crops of larger acorns. However, contrary to expectations, these trees did not satiate more effectively at the seed level either. Effective satiation by larger acorns was precluded by larger multi-infestation rates associated to smaller seed crops, in such a way that the proportion of attacked seeds that survived did not vary among trees with different acorn sizes. These results highlight the need of considering satiation by means of large crops and large seeds in studies of predispersal seed predation. Long-term monitoring on individual oaks will help to assess whether there is a trade-off between the number and the size of the acorns and, if it existed, how it could condition the ﬁtness consequences of both types of satiation
Keywords: Curculio; granivorous insects; Multi-infestation; Predispersal seed predation; Quercus; Satiation; Seed number; Seed size

Satiation of predispersal seed predators: the importance of considering both plant and seed levels - Bonal, Raul; Muñoz, Alberto; Díaz, Mario (Evolutionary Ecology, 2006)
Plants can reduce the ﬁtness costs of granivory by satiating seed predators. The most common satiation mechanism is the production of large crops, which ensures that a proportion of the seeds survive predation. Nevertheless, satiation of small granivores at the seed level may also exist. Larger seeds would satiate more efﬁciently, enhancing the probability of seed survival after having been attacked. However, a larger seed size could compromise the efﬁciency of satiation by means of large crops if there were a negative relationship between seed size and the number of seeds produced by an individual plant. We analyze both types of satiation in the interaction between the holm oak Quercus ilex and the chestnut weevil Curculio elephas. Both crop size and acorn size differed strongly in a sample of 32 trees. Larger crop sizes satiated weevils, and higher proportions of the seeds were not attacked as crop size increased. Larger seeds also satiated weevil larvae, as a larger acorn size increased the likelihood of embryo survival. Seedling size was strongly related to acorn size and was reduced by weevil attack, but seedlings coming from large weeviled acorns were still larger. The number and the size of the acorns produced by individual trees were negatively related. Larger proportions of the crop were infested in oaks producing less numerous crops of larger acorns. However, contrary to expectations, these trees did not satiate more effectively at the seed level either. Effective satiation by larger acorns was precluded by larger multi-infestation rates associated to smaller seed crops, in such a way that the proportion of attacked seeds that survived did not vary among trees with different acorn sizes. These results highlight the need of considering satiation by means of large crops and large seeds in studies of predispersal seed predation. Long-term monitoring on individual oaks will help to assess whether there is a trade-off between the number and the size of the acorns and, if it existed, how it could condition the ﬁtness consequences of both types of satiation
Keywords: Curculio; granivorous insects; Multi-infestation; Predispersal seed predation; Quercus; Satiation; Seed number; Seed size

Seed germination of Quercus robur, q. pyrenaica and q. ilex and the effects of smoke, heat, ash and charcoal - Reyes, Otilia; Casal, Mercedes (Ann. For. Sci., 2006)
This study is centred on Quercus robur, Q. pyrenaica and Q. ilex that have a distribution area covering all Europe. Fire is a frequent ecological factor in many ecosystems, especially in those with Mediterranean climates. Our working hypothesis is that fire affects the germination process. An experiment was carried out testing the following treatments: Control, Smoke-5 min, Smoke-10min, Smoke-15 min, 60 ºC-5 min, 60 °C-15 min, 90 ºC-5 min, 110 ºC-5 min, 150 ºC-5 min, Ash, Ash Dilution and Charcoal. The seed incubation was spread over a year. The germination rates of the Control are very high, especially in Q. ilex. Almost none of the treatments inhibit germination and only the Q. ilex seeds, when subjected to 150 ºC-5 min, show a marked inhibition. Q. robur and Q. pyrenaica take a year to complete their germination, while Q. ilex only takes 22 weeks. Probably, this reproductive behaviour is related to the climate characteristics to which the species have become adapted. Finally, fire does not determine the germination process, the recruitment of new individuals being independent of fire.
Keywords: fire; germination; Quercus; reproductive strategies; Seeds

Seed germination of Quercus robur, q. pyrenaica and q. ilex and the effects of smoke, heat, ash and charcoal - Reyes, Otilia; Casal, Mercedes (Ann. For. Sci., 2006)
This study is centred on Quercus robur, Q. pyrenaica and Q. ilex that have a distribution area covering all Europe. Fire is a frequent ecological factor in many ecosystems, especially in those with Mediterranean climates. Our working hypothesis is that fire affects the germination process. An experiment was carried out testing the following treatments: Control, Smoke-5 min, Smoke-10min, Smoke-15 min, 60 ºC-5 min, 60 °C-15 min, 90 ºC-5 min, 110 ºC-5 min, 150 ºC-5 min, Ash, Ash Dilution and Charcoal. The seed incubation was spread over a year. The germination rates of the Control are very high, especially in Q. ilex. Almost none of the treatments inhibit germination and only the Q. ilex seeds, when subjected to 150 ºC-5 min, show a marked inhibition. Q. robur and Q. pyrenaica take a year to complete their germination, while Q. ilex only takes 22 weeks. Probably, this reproductive behaviour is related to the climate characteristics to which the species have become adapted. Finally, fire does not determine the germination process, the recruitment of new individuals being independent of fire.
Keywords: fire; germination; Quercus; reproductive strategies; Seeds

Soda-anthraquinone, kraft and organosolv pulping of holm oak trimmings. - Alaejos, J.; López, F.; Eugenio, M. E.; Tapias, R. (Bioresource technology, 2006)
The operating conditions for an organosolv (ethyleneglycol) and two alkaline (soda-anthraquinone and kraft) processes for obtaining cellulose pulp and paper from holm oak (Quercus ilex) wood trimmings were optimized. A range of variation for each process variable (viz. temperature, cooking time and soda or ethyleneglycol concentration) was established and a central composite experimental design involving three independent variables at three different variation levels was applied. The results obtained with the three cooking processes used were compared and those provided by the kraft process were found to be the best. Thus, the tensile index values it provided (5.9-16.3 N m/g) were 23.7% and 41.5% better than those obtained with the soda-AQ and ethyleneglycol processes, respectively. Also, the kraft process provided the best burst index, brightness and kappa number values. Based on the optimum working ranges, the temperature and cooking time were the variables resulting in the most and least marked changes, respectively, in pulp properties.
The following values have no corresponding Zotero field: accession-num: 16269242
Keywords: Ethyleneglycol; Forestry residues; Holm oak trimmings; Paper; Quercus

Soda-anthraquinone, kraft and organosolv pulping of holm oak trimmings. - Alaejos, J; Lopez, F; Eugenio, M E; TAPIAS, R (Bioresource technology, 2006)
The operating conditions for an organosolv (ethyleneglycol) and two alkaline (soda-anthraquinone and kraft) processes for obtaining cellulose pulp and paper from holm oak (Quercus ilex) wood trimmings were optimized. A range of variation for each process variable (viz. temperature, cooking time and soda or ethyleneglycol concentration) was established and a central composite experimental design involving three independent variables at three different variation levels was applied. The results obtained with the three cooking processes used were compared and those provided by the kraft process were found to be the best. Thus, the tensile index values it provided (5.9-16.3 N m/g) were 23.7% and 41.5% better than those obtained with the soda-AQ and ethyleneglycol processes, respectively. Also, the kraft process provided the best burst index, brightness and kappa number values. Based on the optimum working ranges, the temperature and cooking time were the variables resulting in the most and least marked changes, respectively, in pulp properties.
Keywords: Ethyleneglycol; Forestry residues; Holm oak trimmings; Paper; Quercus

Variation in the holm oak leaf proteome at different plant developmental stages, between provenances and in response to drought stress. - Jorge, Inmaculada; Navarro, Rafael M; Lenz, Christof; Ariza, David; Jorrín, Jesús (Proteomics, 2006)
Major proteins of the holm oak leaf proteome have been previously identified using a combination of 2-DE, MS analysis and BLAST similarity search (Jorge et al., Proteomics 2005, 5, 222-234). That study, conducted with field samples from mature trees, revealed the existence of a great variability in the 2-DE protein map, with qualitative as well as quantitative changes, both analytical and biological. A similar study has been carried out with 2-year-old seedlings to analyze and study: (i) changes in the 2-DE protein profile at different tree developmental stages; (ii) the 2-DE protein map variability between three different Spanish provenances; and (iii) variations in the 2-DE protein profile in response to drought stress. Although the protein profile of leaves from seedlings and mature trees was fairly similar, the biological variance found was lower in the former. In the present study, new proteins have been identified. At least four different protein spots differentiated Spanish provenances, two of them identified as an ATP synthase alpha chain, and a 2,3-bisphosphoglycerate-independent phosphoglycerate mutase. Fourteen different protein spots were qualitatively variable between well-watered and drought-stressed seedlings, with some of them corresponding to enzymes of carbohydrate and protein metabolism. Data presented indicated the mobilization of storage proteins and carbohydrates, as well as photosynthesis inhibition under drought conditions.
Keywords: Dehydration; Dehydration: metabolism; Disasters; Electrophoresis, Gel, Two-Dimensional; Plant Leaves; Plant Leaves: metabolism; Proteome; Proteome: metabolism; Proteomics; Quercus; Quercus: embryology; Quercus: metabolism; Seedling; Seedling: metabolism

COMPORTAMIENTO DEL GANADO OVINO EN UNA FORESTACIÓN. CONSUMO DE LEÑOSAS Y DAÑOS A PLÁNTULAS DE ENCINA - Blázquez Carrasco, A; Fernández Rebollo, P; Carbonero Muñoz, M D; Navarro Cerrillo, R (IV Congreso Forestal Español, 2005)
Tradicionalmente la presencia de ganado en repoblaciones forestales se ha considerado únicamente por sus efectos antagónicos, sin embargo un pastoreo controlado podría ayudar a la disminución de la competencia de herbáceas. Este trabajo expone los resultados de un ensayo de pastoreo con ovejas, con una carga de 23 animales por hectárea, pastando libremente durante cuatro días, en una forestación de encinas de 12 años de edad y en la que se habían distribuido plántulas de encina de dos años. Se controló el tiempo dedicado por el ganado al consumo de herbáceas, consumo de leñosas, movimiento, rumia, sesteo y otros, en sesiones de diez horas mediante la técnica del scan sampling; además se estimaron el consumo de biomasa herbácea y los daños a las plántulas. Las ovejas dedicaron la mayor parte del tiempo al consumo de herbáceas, 61,4 %, 0,72 kilogramos de materia seca por oveja y día. Al consumo de leñosas dedicaron el 2,41 % y fue disminuyendo en el tiempo. Los daños a las plántulas se localizaron principalmente en brotes tiernos, eliminándolos totalmente en el 20 % de los casos y de forma parcial en el 17,5 %, en el 62,5 % de los casos no hubo daños. En encinas adultas además del consumo de ramas bajas se produjeron daños al tronco en nueve árboles
Keywords: pastoreo; Quercus; ramoneo; repoblaciones

COMPORTAMIENTO DEL GANADO OVINO EN UNA FORESTACIÓN. CONSUMO DE LEÑOSAS Y DAÑOS A PLÁNTULAS DE ENCINA - Blázquez Carrasco, A.; Fernández Rebollo, P.; Carbonero Muñoz, M. D.; Navarro Cerrillo, R. (IV Congreso Forestal Español, 2005)
Tradicionalmente la presencia de ganado en repoblaciones forestales se ha considerado únicamente por sus efectos antagónicos, sin embargo un pastoreo controlado podría ayudar a la disminución de la competencia de herbáceas. Este trabajo expone los resultados de un ensayo de pastoreo con ovejas, con una carga de 23 animales por hectárea, pastando libremente durante cuatro días, en una forestación de encinas de 12 años de edad y en la que se habían distribuido plántulas de encina de dos años. Se controló el tiempo dedicado por el ganado al consumo de herbáceas, consumo de leñosas, movimiento, rumia, sesteo y otros, en sesiones de diez horas mediante la técnica del scan sampling; además se estimaron el consumo de biomasa herbácea y los daños a las plántulas. Las ovejas dedicaron la mayor parte del tiempo al consumo de herbáceas, 61,4 %, 0,72 kilogramos de materia seca por oveja y día. Al consumo de leñosas dedicaron el 2,41 % y fue disminuyendo en el tiempo. Los daños a las plántulas se localizaron principalmente en brotes tiernos, eliminándolos totalmente en el 20 % de los casos y de forma parcial en el 17,5 %, en el 62,5 % de los casos no hubo daños. En encinas adultas además del consumo de ramas bajas se produjeron daños al tronco en nueve árboles
The following values have no corresponding Zotero field: periodical: IV Congreso Forestal Español
Keywords: pastoreo; Quercus; ramoneo; repoblaciones

ESTIMACIÓN DE LA COBERTURA ARBÓREA EN DEHESAS MEDIANTE MODELOS LINEALES DE MEZCLAS ESPECTRALES APLICADAS A IMÁGENES LANDSAT-TM - González Dugo, Mª Pat; Fernández Rebollo, P; Guerrero Ginel, J E; Giráldez, J V (IV Congreso Forestal Español, 2005)
La dehesa es un ecosistema característico del SW de España con un alto valor económico y ambiental pero frágil ante los cambios climáticos. En este trabajo se determina la cobertura ocupada por el arbolado en una zona de dehesa situada al norte de la provincia de Córdoba usando una imagen Landsat-TM y aplicando un modelo lineal de mezclas espectrales. Se han evaluado cinco métodos para encontrar los factores de referencia que mejor representan los componentes de dicho ecosistema, obteniendo mejor resultado al utilizar el algoritmo no supervisado IKSFA. Los valores de cobertura de vegetación verde estimada por el modelo se han validado midiendo de forma automática la cobertura ocupada por las copas de los árboles sobre fotografía aérea. Los resultados indican que el modelo sobreestima la cobertura arbórea con una desviación media del 4% y que el ajuste mejora al aumentar la cobertura arbórea de las parcelas de control.
Keywords: encina; Quercus; teledetección

EVOLUCIÓN DE LA DEFOLIACIÓN DE LA COPA DE ENCINAS EN DEHESAS ANDALUZAS DURANTE EL PERIODO 2000-2004. INFLUENCIA DE LAS PRÁCTICAS DE GESTIÓN - Fernández Rebollo, P; Carbonero Muñoz, M D; Blázquez Carrasco, A; R., Navarro Cerrillo (IV Congreso Forestal Español, 2005)
El arbolado de la dehesa atraviesa hoy por hoy una situación delicada, ya que a la ausencia de regenerado viable hay que sumar la pérdida de vigor del arbolado adulto propiciada por la sequía del periodo 1980-1995, el progresivo aumento de las temperaturas y la incidencia de determinadas plagas y enfermedades. En este trabajo se analiza la evolución que ha sufrido la defoliación de la copa de encinas en dehesas situadas en la comarca de Los Pedroches (Córdoba) durante el periodo 2000-2004, examinándose la influencia de prácticas de gestión que modifican el estado físico-químico del suelo. Se ha observado una disminución progresiva y lenta de la defoliación de la copa durante estos cinco años, debido a las abundantes lluvias acaecidas. El estado actual del arbolado así como la evolución de la defoliación ha sido mejor en aquellos suelos que presentaban mayores contenidos en materia orgánica oxidable, fósforo asimilable y menores contenidos en arena
Keywords: decaimiento; Nutrientes edáficos; Quercus; Recuperación

EVOLUCIÓN DE LA DEFOLIACIÓN DE LA COPA DE ENCINAS EN DEHESAS ANDALUZAS DURANTE EL PERIODO 2000-2004. INFLUENCIA DE LAS PRÁCTICAS DE GESTIÓN - Fernández Rebollo, P.; Carbonero Muñoz, M. D.; Blázquez Carrasco, A.; R., Navarro Cerrillo (IV Congreso Forestal Español, 2005)
El arbolado de la dehesa atraviesa hoy por hoy una situación delicada, ya que a la ausencia de regenerado viable hay que sumar la pérdida de vigor del arbolado adulto propiciada por la sequía del periodo 1980-1995, el progresivo aumento de las temperaturas y la incidencia de determinadas plagas y enfermedades. En este trabajo se analiza la evolución que ha sufrido la defoliación de la copa de encinas en dehesas situadas en la comarca de Los Pedroches (Córdoba) durante el periodo 2000-2004, examinándose la influencia de prácticas de gestión que modifican el estado físico-químico del suelo. Se ha observado una disminución progresiva y lenta de la defoliación de la copa durante estos cinco años, debido a las abundantes lluvias acaecidas. El estado actual del arbolado así como la evolución de la defoliación ha sido mejor en aquellos suelos que presentaban mayores contenidos en materia orgánica oxidable, fósforo asimilable y menores contenidos en arena
The following values have no corresponding Zotero field: periodical: IV Congreso Forestal Español pub-location: Zaragoza
Keywords: decaimiento; Nutrientes edáficos; Quercus; Recuperación

Temporal variations in PAH concentrations in Quercus ilex L. (holm oak) leaves in an urban area. - De Nicola, Flavia; Maisto, Giulia; Prati, Maria Vittoria; Alfani, Anna (Chemosphere, 2005)
Temporal variations of polycyclic aromatic hydrocarbon (PAH) concentrations in leaves of a Mediterranean evergreen oak, Quercus ilex L., were investigated in order to assess the suitability of this species to biomonitor PAH air contamination. Leaf samples were collected at six sites of the urban area of Naples (Italy) and at a control site in the Vesuvius National Park, in May and September 2001, and in January and May 2002. PAH extraction was conducted by sonication in dichloromethane-acetone and quantification by GC-MS. In winter, leaf total PAH concentrations showed, at all the urban sites, values 2-fold higher than in all the other samplings, reflecting the temporal trend reported for PAH air contamination in the Naples urban area. Moreover, leaf PAH concentrations showed, at all the urban sites, a decrease in May 2002 after the winter accumulation. At the control site leaf PAH concentrations showed lower values and smaller temporal variations than at the urban sites. The findings support the suitability of Q. ilex leaves to monitor temporal variations in PAH contamination. The highest winter concentrations of total PAHs were due to the medium molecular weight PAHs that increased with respect to both low and high molecular weight PAHs. The medium molecular weight PAHs showed the same temporal trend both at the urban and remote sites.
Keywords: Aromatic; Aromatic: analysis; Cities; Environmental Monitoring; Environmental Pollutants; Environmental Pollutants: analysis; Italy; Mediterranean evergreen oak; Naples (Italy); PAH biomonitoring; pah leaf accumulation; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus: chemistry; Seasonal trend; Seasons; Time Factors

Temporal variations in PAH concentrations in Quercus ilex L. (holm oak) leaves in an urban area. - De Nicola, Flavia; Maisto, Giulia; Prati, Maria Vittoria; Alfani, Anna (Chemosphere, 2005)
Temporal variations of polycyclic aromatic hydrocarbon (PAH) concentrations in leaves of a Mediterranean evergreen oak, Quercus ilex L., were investigated in order to assess the suitability of this species to biomonitor PAH air contamination. Leaf samples were collected at six sites of the urban area of Naples (Italy) and at a control site in the Vesuvius National Park, in May and September 2001, and in January and May 2002. PAH extraction was conducted by sonication in dichloromethane-acetone and quantification by GC-MS. In winter, leaf total PAH concentrations showed, at all the urban sites, values 2-fold higher than in all the other samplings, reflecting the temporal trend reported for PAH air contamination in the Naples urban area. Moreover, leaf PAH concentrations showed, at all the urban sites, a decrease in May 2002 after the winter accumulation. At the control site leaf PAH concentrations showed lower values and smaller temporal variations than at the urban sites. The findings support the suitability of Q. ilex leaves to monitor temporal variations in PAH contamination. The highest winter concentrations of total PAHs were due to the medium molecular weight PAHs that increased with respect to both low and high molecular weight PAHs. The medium molecular weight PAHs showed the same temporal trend both at the urban and remote sites.
The following values have no corresponding Zotero field: accession-num: 16182861
Keywords: Aromatic; Aromatic: analysis; Cities; Environmental Monitoring; Environmental Pollutants; Environmental Pollutants: analysis; Italy; Mediterranean evergreen oak; Naples (Italy); PAH biomonitoring; pah leaf accumulation; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus: chemistry; Seasonal trend; Seasons; Time Factors

Utility of ITS sequence data for phylogenetic reconstruction of Italian Quercus spp. - BELLAROSA, Rosanna; Simeone, Marco C.; Papini, Alessio; Schirone, Bartolomeo (Molecular phylogenetics and evolution, 2005)
Nuclear ribosomal DNA sequences encoding the 5.8S RNA and the flanking internal transcribed spacers (ITS1 and ITS2) were used to test the phylogenetic relationships within 12 Italian Quercus taxa (Fagaceae). Hypotheses of sequence orthology are tested by detailed inspection of some basic features of oak ITS sequences (i.e., general patterns of conserved domains, thermodynamic stability and predicted conformation of the secondary structure of transcripts) that also allowed more accurate sequence alignment. Analysis of ITS variation supported three monophyletic groups, corresponding to subg. Cerris, Schlerophyllodrys (=Ilex group sensu Nixon) and Quercus, as proposed by Schwarz [Feddes Rep., Sonderbeih. D, 1-200]. A derivation of the "Cerris group" from the "Ilex group" is suggested, with Q. cerris sister to the rest of the "Cerris group." Quercus pubescens was found to be sister to the rest of the "Quercus group." The status of hybrispecies of Q. crenata (Q. cerrisxQ. suber) and Q. morisii (Q. ilexxQ. suber) was evaluated and discussed. Finally, the phylogenetic position of the Italian species in a broader context of the genus is presented. The utility of the ITS marker to assess the molecular systematics of oaks is therefore confirmed. The importance of Italy as a region with a high degree of diversity at the population and genetic level is discussed.
The following values have no corresponding Zotero field: accession-num: 15619447
Keywords: ITS sequences; phylogeny; Quercus; Secondary structures

Utility of ITS sequence data for phylogenetic reconstruction of Italian Quercus spp. - BELLAROSA, Rosanna; Simeone, Marco C; Papini, Alessio; Schirone, Bartolomeo (Molecular phylogenetics and evolution, 2005)
Nuclear ribosomal DNA sequences encoding the 5.8S RNA and the flanking internal transcribed spacers (ITS1 and ITS2) were used to test the phylogenetic relationships within 12 Italian Quercus taxa (Fagaceae). Hypotheses of sequence orthology are tested by detailed inspection of some basic features of oak ITS sequences (i.e., general patterns of conserved domains, thermodynamic stability and predicted conformation of the secondary structure of transcripts) that also allowed more accurate sequence alignment. Analysis of ITS variation supported three monophyletic groups, corresponding to subg. Cerris, Schlerophyllodrys (=Ilex group sensu Nixon) and Quercus, as proposed by Schwarz [Feddes Rep., Sonderbeih. D, 1-200]. A derivation of the "Cerris group" from the "Ilex group" is suggested, with Q. cerris sister to the rest of the "Cerris group." Quercus pubescens was found to be sister to the rest of the "Quercus group." The status of hybrispecies of Q. crenata (Q. cerrisxQ. suber) and Q. morisii (Q. ilexxQ. suber) was evaluated and discussed. Finally, the phylogenetic position of the Italian species in a broader context of the genus is presented. The utility of the ITS marker to assess the molecular systematics of oaks is therefore confirmed. The importance of Italy as a region with a high degree of diversity at the population and genetic level is discussed.
Keywords: ITS sequences; phylogeny; Quercus; Secondary structures

Adaptive photosynthetic strategies of the Mediterranean maquis species according to their origin - Gratani, L; Varone, L (Photosynthetica, 2004)
In consideration of their origin the adaptive strategies of the evergreen species of the Mediterranean maquis were analysed. Rosmarinus officinalis L., Erica arborea L., and Erica multiflora L. had the lowest net photosynthetic rate (PN) in the favourable period [7.8±0.6 µmol(CO2) m -2 s -1 , mean value], the highest PN decrease (on an average 86 % of the maximum) but the highest recovery capacity (>70 % of the maximum) at the first rainfall in September. Cistus incanus L. and Arbutus unedo L. had the highest PN during the favourable period [15.5±5.2 µmol(CO2) m -2 s -1 , mean value], 79 % decrease during drought, and a lower recovery capacity (on an average 54 %). Quercus ilex L., Phillyrea latifolia L., and Pistacia lentiscus L. had an intermediate PN in the favourable period [9.2±1.3 µmol(CO2) m -2 s -1 , mean value], a lower reduction during drought (on an average 63 %), and a range from 62 % (Q. ilex and P. latifolia) to 39 % (P. lentiscus) of recovery capacity. The Mediterranean species had higher decrease in PN and stomatal conductance during drought and a higher recovery capacity than the pre-Mediterranean species. Among the pre-Mediterranean species, P. latifolia had the best adaptation to long drought periods also by its higher leaf mass per area (LMA) which lowered leaf temperature thus decreasing transpiration rate during drought. Moreover, its leaf longevity determined a more stable leaf biomass during the year. Among the Mediteranean species, R. officinalis was the best adapted species to short drought periods by its ability to rapidly recover. Nevertheless, R. officinalis had the lowest tolerance to high temperatures by its PN dropping below half its maximum value when leaf temperature was over 33.6 °C. R. officinalis may be used as a bioindicator species of global change.
Keywords: arbutus; cistus; drought period; Erica; Phillyrea; Pistacia; Quercus; recovery capacity; Rosmarinus; Stomatal conductance

Changes in pectins and MAPKs related to cell development during early microspore embryogenesis in Quercus suber L. - Ramírez, Carmen; Testillano, Pilar S.; Pintos, Beatriz; Moreno-Risueño, Miguel a; Bueno, María a; Risueño, María C. (European journal of cell biology, 2004)
The occurrence and significance of changes in cell wall components and signalling molecules has been investigated during early microspore embryogenesis in cork oak (Quercus suber L.) in relation to cell proliferation and cell differentiation. Microspore embryogenesis has been induced in in vitro anther cultures of Q. suber by the application of a stress treatment of 33 degrees C. After the treatment, microspores at the responsive developmental stage of vacuolate microspore switched towards proliferation and the embryogenesis pathway to further produce haploid plantlets. Ultrastructural and immunocytochemical analysis revealed changes in cell organisation after induction at different developmental stages, the cellular features displayed being in relation to the activation of proliferative activity and the beginning of differentiation in young and late proembryos. Immunogold labelling with JIM5 and JIM7 antibodies showed a different presence of pectin and level of its esterification in cell walls at different developmental stages. Non-esterified pectins were found in higher proportions in cells of late proembryos, suggesting that pectin de-esterification could be related to the beginning of differentiation. The presence and subcellular distribution of Erk 1/2 MAPK homologues have been investigated by immunoblotting, immunofluorescence and immunogold labelling. The results showed an increase in the expression of these proteins with a high presence in the nucleus, during early microspore proembryos development. The reported changes during early microspore embryogenesis are modulated in relation to proliferation and differentiation events. These findings provided new evidences for a role of MAPK signalling pathways in early microspore embryogenesis, specifically in proliferation, and would confer information for the cell fate and the direction of the cell development.
The following values have no corresponding Zotero field: accession-num: 15346811
Keywords: Cell Differentiation; Cell Differentiation: physiology; Electron; MAPKs; Microscopy; microspore embryogenesis; Mitogen-Activated Protein Kinase 1; Mitogen-Activated Protein Kinase 1: metabolism; Mitogen-Activated Protein Kinase 3; Mitogen-Activated Protein Kinase 3: metabolism; Mitogen-Activated Protein Kinases; Mitogen-Activated Protein Kinases: metabolism; Pectins; Pectins: metabolism; Proliferation; Quercus; Quercus: embryology; Quercus: enzymology; Quercus: metabolism; Seeds; Seeds: cytology; Seeds: ultrastructure

Changes in pectins and MAPKs related to cell development during early microspore embryogenesis in Quercus suber L. - Ramírez, Carmen; Testillano, Pilar S; Pintos, Beatriz; Moreno-Risueño, Miguel a; Bueno, María a; Risueño, María C (European journal of cell biology, 2004)
The occurrence and significance of changes in cell wall components and signalling molecules has been investigated during early microspore embryogenesis in cork oak (Quercus suber L.) in relation to cell proliferation and cell differentiation. Microspore embryogenesis has been induced in in vitro anther cultures of Q. suber by the application of a stress treatment of 33 degrees C. After the treatment, microspores at the responsive developmental stage of vacuolate microspore switched towards proliferation and the embryogenesis pathway to further produce haploid plantlets. Ultrastructural and immunocytochemical analysis revealed changes in cell organisation after induction at different developmental stages, the cellular features displayed being in relation to the activation of proliferative activity and the beginning of differentiation in young and late proembryos. Immunogold labelling with JIM5 and JIM7 antibodies showed a different presence of pectin and level of its esterification in cell walls at different developmental stages. Non-esterified pectins were found in higher proportions in cells of late proembryos, suggesting that pectin de-esterification could be related to the beginning of differentiation. The presence and subcellular distribution of Erk 1/2 MAPK homologues have been investigated by immunoblotting, immunofluorescence and immunogold labelling. The results showed an increase in the expression of these proteins with a high presence in the nucleus, during early microspore proembryos development. The reported changes during early microspore embryogenesis are modulated in relation to proliferation and differentiation events. These findings provided new evidences for a role of MAPK signalling pathways in early microspore embryogenesis, specifically in proliferation, and would confer information for the cell fate and the direction of the cell development.
Keywords: Cell Differentiation; Cell Differentiation: physiology; Electron; MAPKs; Microscopy; microspore embryogenesis; Mitogen-Activated Protein Kinase 1; Mitogen-Activated Protein Kinase 1: metabolism; Mitogen-Activated Protein Kinase 3; Mitogen-Activated Protein Kinase 3: metabolism; Mitogen-Activated Protein Kinases; Mitogen-Activated Protein Kinases: metabolism; Pectins; Pectins: metabolism; Proliferation; Quercus; Quercus: embryology; Quercus: enzymology; Quercus: metabolism; Seeds; Seeds: cytology; Seeds: ultrastructure

EXPERIENCIA DE REGENERACIÓN DE ENCINAR EN LA SIERRA DE HUELVA Studies on holm oak regeneration in North Sevilla mountains - Porras Tejeiro, C J; Brun Esquiliche, P; Copete Gutiérrez, J; Pérez Méndez, R (Cuad. Soc. Esp. Cien. For Actas de la III Reunión sobre Repoblaciones Forestales, 2004)
We have described an oak regeneration research without prohibit the grazing. Three implantation types and seven protections types have been tested. Several parameters have been measured to the seven, fifteen and twenty three months since the seeding or planting
Keywords: Dehesa; Grazing; implantación; Implantation; pastoreo; protección; Protection; Quercus

EXPERIENCIA DE REGENERACIÓN DE ENCINAR EN LA SIERRA DE HUELVA Studies on holm oak regeneration in North Sevilla mountains - Porras Tejeiro, C. J.; Brun Esquiliche, P.; Copete Gutiérrez, J.; Pérez Méndez, R. (Cuad. Soc. Esp. Cien. For Actas de la III Reunión sobre Repoblaciones Forestales, 2004)
We have described an oak regeneration research without prohibit the grazing. Three implantation types and seven protections types have been tested. Several parameters have been measured to the seven, fifteen and twenty three months since the seeding or planting
Keywords: Dehesa; Grazing; implantación; Implantation; pastoreo; protección; Protection; Quercus

Frost resistance of seeds in Mediterranean oaks and the role of litter - Esteso-Martínez, Jordán; Gil-Pelegrín, Eustaquio (Ann. For. Sci., 2004)
The endogenous frost resistance of the seeds of four Mediterranean oaks (Quercus coccifera, Q. faginea, Q. ilex and Q. pyrenaica) with different leaf abscission phenology was tested. Thermal analysis and polyelectrolytes leakage methodologies were employed to establish lethal temperature thresholds. Results showed a higher frost resistance for evergreen species and lower for deciduous species in this decreasing order: Q. coccifera, Q. ilex, Q. faginea and Q. pyrenaica. The cover of leaf litter generated by deciduous species could be an isolating element which allowed seed survival under cold winter conditions to that species with a lower frost resistance. Differences in temperature above and below a leaf litter cover along a winter season were measured in a Q. faginea stand, in this sense the kind effect of leaf litter from a thermal point of view was proved.
Keywords: frost resistance; leaf litter; polyelectrolytic leakage; Quercus; thermal analysis

Frost resistance of seeds in Mediterranean oaks and the role of litter - Esteso-Martínez, Jordán; Gil-Pelegrín, Eustaquio (Ann. For. Sci., 2004)
The endogenous frost resistance of the seeds of four Mediterranean oaks (Quercus coccifera, Q. faginea, Q. ilex and Q. pyrenaica) with different leaf abscission phenology was tested. Thermal analysis and polyelectrolytes leakage methodologies were employed to establish lethal temperature thresholds. Results showed a higher frost resistance for evergreen species and lower for deciduous species in this decreasing order: Q. coccifera, Q. ilex, Q. faginea and Q. pyrenaica. The cover of leaf litter generated by deciduous species could be an isolating element which allowed seed survival under cold winter conditions to that species with a lower frost resistance. Differences in temperature above and below a leaf litter cover along a winter season were measured in a Q. faginea stand, in this sense the kind effect of leaf litter from a thermal point of view was proved.
Keywords: frost resistance; leaf litter; polyelectrolytic leakage; Quercus; thermal analysis

Habitat quality as a predictor of spatial variation in blue tit reproductive performance: a multi-plot analysis in a heterogeneous landscape - Lambrechts, MarcelM; Caro, Samuel; Charmantier, Anne; Gross, Nicolas; Galan, Marie-Jo; Perret, Philippe; Cartan-Son, Mireille; Dias, PaulaC; Blondel, Jacques; Thomas, DonaldW (Oecologia, 2004)
Vertebrate studies have rarely investigated the influence of spatial variation in habitat richness on both short-term (breeding) and long-term (offspring recruitment) reproductive performance using simultaneously multi-patch, multi-habitat type and multi-year approaches at landscape level. Here we present results of such an approach using the influence of two oak tree (Quercus ilex, Q. humilis) species on reproductive performance in Corsican blue tits (Parus caeruleus ogliastrae) as a model system. We found that blue tits breeding in rich broadleaved deciduous patches consistently laid eggs earlier in the season, and produced larger clutches and more fledglings of higher quality, than those breeding in poor evergreen patches. Also, parents, especially males, were in better physical condition in the broad-leaved deciduous than in the evergreen patches. Surprisingly, estimates of long-term effects of reproduction, such as recruitment rates of locally born offspring, did not differ between the two habitat types. Our results suggest that short-term breeding performance and phenotypic quality of both chicks and parents do not necessarily provide reliable information about contributions to following generations at a scale larger than that of the local study plot. Differences in reproductive performance between the two oak habitat types could not be attributed to densitydependent effects, differences in levels of nest predation, or differences in age structure of the birds. We suggest that habitats that are optimal for breeding are not necessarily optimal for survival after the breeding season.
The following values have no corresponding Zotero field: publisher: Springer-Verlag
Keywords: Habitat quality; Parus caeruleus; Predation; Quercus; reproduction

Habitat quality as a predictor of spatial variation in blue tit reproductive performance: a multi-plot analysis in a heterogeneous landscape - Lambrechts, MarcelM.; Caro, Samuel; Charmantier, Anne; Gross, Nicolas; Galan, Marie-Jo; Perret, Philippe; Cartan-Son, Mireille; Dias, PaulaC.; Blondel, Jacques; Thomas, DonaldW. (Oecologia, 2004)
Vertebrate studies have rarely investigated the influence of spatial variation in habitat richness on both short-term (breeding) and long-term (offspring recruitment) reproductive performance using simultaneously multi-patch, multi-habitat type and multi-year approaches at landscape level. Here we present results of such an approach using the influence of two oak tree (Quercus ilex, Q. humilis) species on reproductive performance in Corsican blue tits (Parus caeruleus ogliastrae) as a model system. We found that blue tits breeding in rich broadleaved deciduous patches consistently laid eggs earlier in the season, and produced larger clutches and more fledglings of higher quality, than those breeding in poor evergreen patches. Also, parents, especially males, were in better physical condition in the broad-leaved deciduous than in the evergreen patches. Surprisingly, estimates of long-term effects of reproduction, such as recruitment rates of locally born offspring, did not differ between the two habitat types. Our results suggest that short-term breeding performance and phenotypic quality of both chicks and parents do not necessarily provide reliable information about contributions to following generations at a scale larger than that of the local study plot. Differences in reproductive performance between the two oak habitat types could not be attributed to densitydependent effects, differences in levels of nest predation, or differences in age structure of the birds. We suggest that habitats that are optimal for breeding are not necessarily optimal for survival after the breeding season.
Keywords: Habitat quality; Parus caeruleus; Predation; Quercus; reproduction

La diversitá cloroplastica delle querce italiane: evidenze di una maggiore ricchezza genetica nelle popolazioni meridionali e insulari - Fineschi, S; Vendramin, G G (iForest - Biogeosciences and Forestry, 2004)
Results of the analysis of non-coding regions of the chloroplast genome in Italian population of deciduous oaks (subgenus Quercus) and holm oak (subgenus Scleropyllodris) are reported. Deciduous oak revealed the occurrence of six chloroplast haplotypes, differently distributed in the single geographic areas (northern, central, and southern Italy, and major islands). Moreover, most of the present Italian oak populations seems to derive from two major refugia, located in Sicily and in the Balkans, respectively. The most likely migration dynamics from the refugia towards the central and northern part of the peninsula are discussed. Migration pathways resulted to have been different in the various geographic areas. The presence of an endemic haplotype in Sardinia and Corsica was considered of particular interest. In Italian holm oak populations eight haplotypes were detected, six of them in Sicily. Five out of six Sicilian haplotypes resulted to be endemic. The Italian peninsula was colonized by two major haplotypes, one of them originating from Sicily. Results on deciduous oaks and holm oak in Italy highlight the important role played by the populations from the south and from the major islands in the colonization the Italian peninsula after the last ice age.
Keywords: Chloroplastic Diversity; colonization; conservation; glacial refugia; phylogeography; Quercus

La diversitá cloroplastica delle querce italiane: evidenze di una maggiore ricchezza genetica nelle popolazioni meridionali e insulari - Fineschi, S.; Vendramin, G. G. (iForest - Biogeosciences and Forestry, 2004)
Results of the analysis of non-coding regions of the chloroplast genome in Italian population of deciduous oaks (subgenus Quercus) and holm oak (subgenus Scleropyllodris) are reported. Deciduous oak revealed the occurrence of six chloroplast haplotypes, differently distributed in the single geographic areas (northern, central, and southern Italy, and major islands). Moreover, most of the present Italian oak populations seems to derive from two major refugia, located in Sicily and in the Balkans, respectively. The most likely migration dynamics from the refugia towards the central and northern part of the peninsula are discussed. Migration pathways resulted to have been different in the various geographic areas. The presence of an endemic haplotype in Sardinia and Corsica was considered of particular interest. In Italian holm oak populations eight haplotypes were detected, six of them in Sicily. Five out of six Sicilian haplotypes resulted to be endemic. The Italian peninsula was colonized by two major haplotypes, one of them originating from Sicily. Results on deciduous oaks and holm oak in Italy highlight the important role played by the populations from the south and from the major islands in the colonization the Italian peninsula after the last ice age.
The following values have no corresponding Zotero field: pub-location: (1) CNR Istituto per la Protezione delle Piante, via Madonna del Piano, Edificio E, 50019 Sesto Fiorentino, Firenze; (2) CNR Istituto di Genetica Vegetale, sezione di Firenze, via Madonna del Piano, Edificio D, 50019 Sesto Fiorentino, Firenze publisher: SISEF - Italian Society of Silviculture and Forest Ecology
Keywords: Chloroplastic Diversity; colonization; conservation; glacial refugia; phylogeography; Quercus

The role of disturbance in the co-existence of the evergreen Quercus ilex and the deciduous Quercus cerrioides - Bonfil, Consuelo; Cortés, Pilar; Espelta, Josep Maria; Retana, Javier (Journal of Vegetation Science, 2004)
Question: Which is the response of the evergreen Quercus ilex and the deciduous Q. cerrioides to repeated disturbances? Location: central Catalonia (northeastern Spain), in the areas affected by two of the largest historically recorded wildfires in NE Spain: the Bages-Berguedà fire (24 300 ha forested area burned in July 1994), and the Solsonès fire (14 300 ha burned in 1998). Methods: Survival and growth of individuals of Quercus ilex and Q. cerrioides were evaluated in plants subjected to different fire histories and experimental disturbances (burning, cutting or clipping) applied either before or after summer. Results: Survival was high (> 99%), with both species showing a similar high resistance to disturbances. Growth after experimental disturbance was positively related to the size of the individual before the latest forest fire occurred. Fire history had a large effect on resprout growth, as the repeated incidence of disturbances lowered the capacity of individuals to grow. The type and season of experimental disturbance experienced by plants had a large effect. Individuals that experienced total above-ground loss had lower growth rates than those with partial loss. A similar pattern was observed in individuals disturbed after the summer in relation to those disturbed before summer. Conclusions: The larger growth rates recorded in Q. cerrioides across all fire histories and experimental treatments, and the higher vulnerability of Q. ilex to increased fire frequency, intensity of experimental disturbance, and disturbance season, provide evidence for the relatively high susceptibility of the latter to repeated disturbances. This view disagrees with the larger resilience of this species compared to co-existing deciduous oaks, as reported.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Burning; clipping; fire; Growth; Mediterranean Region; Quercus; resilience; resprouting; Survival

The role of disturbance in the co-existence of the evergreen Quercus ilex and the deciduous Quercus cerrioides - Bonfil, Consuelo; Cortés, Pilar; Espelta, Josep Maria; Retana, Javier (Journal of Vegetation Science, 2004)
Question: Which is the response of the evergreen Quercus ilex and the deciduous Q. cerrioides to repeated disturbances? Location: central Catalonia (northeastern Spain), in the areas affected by two of the largest historically recorded wildfires in NE Spain: the Bages-Berguedà fire (24 300 ha forested area burned in July 1994), and the Solsonès fire (14 300 ha burned in 1998). Methods: Survival and growth of individuals of Quercus ilex and Q. cerrioides were evaluated in plants subjected to different fire histories and experimental disturbances (burning, cutting or clipping) applied either before or after summer. Results: Survival was high (> 99%), with both species showing a similar high resistance to disturbances. Growth after experimental disturbance was positively related to the size of the individual before the latest forest fire occurred. Fire history had a large effect on resprout growth, as the repeated incidence of disturbances lowered the capacity of individuals to grow. The type and season of experimental disturbance experienced by plants had a large effect. Individuals that experienced total above-ground loss had lower growth rates than those with partial loss. A similar pattern was observed in individuals disturbed after the summer in relation to those disturbed before summer. Conclusions: The larger growth rates recorded in Q. cerrioides across all fire histories and experimental treatments, and the higher vulnerability of Q. ilex to increased fire frequency, intensity of experimental disturbance, and disturbance season, provide evidence for the relatively high susceptibility of the latter to repeated disturbances. This view disagrees with the larger resilience of this species compared to co-existing deciduous oaks, as reported.
Keywords: Burning; clipping; fire; Growth; Mediterranean Region; Quercus; resilience; resprouting; Survival

Winter photoinhibition in the field involves different processes in four co-occurring Mediterranean tree species - Martínez-Ferri, E; Manrique, E; Valladares, F; Balaguer, L (Tree Physiology, 2004)
Photoinhibition was examined in four co-occurring Mediterranean evergreen tree species during two consecutive winters. In response to low temperatures and saturating light, Juniperus phoenicea L., Pinus halepensis Mill., Quercus coccifera L. and Q. ilex ssp. ballota (Desf.) Samp. exhibited marked chronic photoinhibition, indicated by low predawn maximal photochemical efficiency of photosystem II (PSII) (Fv/Fm). Low Fv/Fm values were correlated with high concentrations of xanthophyll cycle components (VAZ) and with the maintenance of high concentrations of zeaxanthin overnight (DPSpd). In all species, however, chronic photoinhibition was enhanced as the winter progressed in the absence of changes in DPSpd, suggesting cumulative damage toward the end of winter.Photoinhibition differed among species: P. halepensis always displayed significantly higher Fv/Fm values; and Q. coccifera had the lowest Fv/Fm values, showing a high sensitivity to the combination of high light and low temperatures. Differences among species were not fully explained by differences in the xanthophyll pool or its de-epoxidation state. Chronic photoinhibition overlapped with a dynamic photoinhibition as shown by the low values of photochemical efficiency of the open reaction centers of PSII at midday. Winter photoprotective strategies differed among species and may involve photoprotective mechanisms in addition to those associated with xanthophylls. The observed species-specific differences matched results obtained for the same species in summer; however, comparison of the two seasons suggests that the higher VAZ concentration observed in winter has an additional structural photoprotective role.
From Duplicate 2 (Winter photoinhibition in the field involves different processes in four co-occurring Mediterranean tree species - Martínez-Ferri, E; Manrique, E; Valladares, F; Balaguer, L)
Keywords: chlorophyll; Chlorophyll: physiology; Juniperus; Juniperus: physiology; photoprotection; Pinus; Pinus: physiology; Plant Leaves; Plant Leaves: physiology; Quercus; Quercus: physiology; Seasons; Sunlight; Trees; Trees: physiology; xanthophyll cycle

A 10-kDa class-CI sHsp protects E-coli from oxidative and high-temperature stress - Jofre, A; Molinas, M; Pla, M (PLANTA, 2003)
We report on a new cDNA clone (Qshsp10.4-CI) of a Quercus suber L. class-CI small heat-shock protein (sHsp) obtained from cork (phellem), a highly oxidatively stressed plant tissue. The deduced gene product lacks the C-terminal extension and the consensus I region of the alpha-crystallin domain, being the most C-terminally truncated sHsp reported to date. In an attempt to prove that a protective function is possible for such a truncated sHsp, we overexpressed in Escherichia coli three recombinant sHsp-CIs, one (rQsHsp10.4-CI) showing the same truncation as Qshsp10.4-CI, a second (rN49) lacking the whole alpha-crystallin domain, and a third (rN153) consisting of a full-length sHsp-CI. The overexpression of rN153 and, remarkably, rQsHsp10.4-CI but not rN49 enhanced cell viability under high temperature and, interestingly, under oxidative stress. These results show that the C-terminal extension and the consensus I region of the alpha-crystallin domain are dispensable, but amino acids 1-41 of the alpha-crystallin domain (including the consensus II region) are essential for the protective activity of sHsp-CIs. On the other hand, two-dimensional immunodetection patterns showed accumulation of ca. 10-kDa sHsp-CI immunorelated polypeptides in cork and other oxidatively stressed tissues but not in control and heat-stressed tissues. We discuss the possible role of highly truncated sHsps in relation to oxidative stress.
Keywords: chaperone activity; heat stress; Oxidative stress; Quercus; small heat-shock protein

Comparison between ethanol and hexane for oil extraction from Quercus suber L. fruits - Ferreira-Dias, Suzana; Valente, Dina G.; Abreu, José M. F. (Grasas y Aceites, 2003)
The aim of this study was to (i) evaluate the feasibility of replacing n -hexane with ethanol for the extraction of oil from Quercus suber fruits and (ii) optimize, at lab scale, sample preparation and extraction time for both solvents used ( n -hexane vs . anhydrous ethanol). For both solvents, the effect of the conditioning process on extraction yield was evaluated. Therefore, a full factorial design was used as a function of four variables: dehulling (with vs . without husks), and thermal treatment of the crushed material (40ºC vs . 75ºC), at different times (5 min vs . 120 min) and pressures (10 kPa vs. 100 kPa). Higher oil yields were obtained with n -hexane when dehulled fruits were conditioned under atmospheric pressure. Better yields were obtained with n -hexane, when dehulled material was treated at 75ºC for 90 min. Ethanol was not adequate for oil extraction from Quercus fruits, since other materials rather than oil were also extracted.
Keywords: acorns; Ethanol; Extraction; Hexane; Oil; Quercus

Comparison between ethanol and hexane for oil extraction from Quercus suber L. fruits - Ferreira-Dias, Suzana; Valente, Dina G; Abreu, José M F (Grasas y Aceites, 2003)
The aim of this study was to (i) evaluate the feasibility of replacing n -hexane with ethanol for the extraction of oil from Quercus suber fruits and (ii) optimize, at lab scale, sample preparation and extraction time for both solvents used ( n -hexane vs . anhydrous ethanol). For both solvents, the effect of the conditioning process on extraction yield was evaluated. Therefore, a full factorial design was used as a function of four variables: dehulling (with vs . without husks), and thermal treatment of the crushed material (40ºC vs . 75ºC), at different times (5 min vs . 120 min) and pressures (10 kPa vs. 100 kPa). Higher oil yields were obtained with n -hexane when dehulled fruits were conditioned under atmospheric pressure. Better yields were obtained with n -hexane, when dehulled material was treated at 75ºC for 90 min. Ethanol was not adequate for oil extraction from Quercus fruits, since other materials rather than oil were also extracted.
Keywords: acorns; Ethanol; Extraction; Hexane; Oil; Quercus

Effect of Tannins from Quercus suber and Quercus coccifera Leaves on Ethanol-Induced Gastric Lesions in Mice - Khennouf, Seddik; Benabdallah, Hassiba; Gharzouli, Kamel; Amira, Smain; Ito, Hideyuki; Kim, Tae-Hoon; Yoshida, Takashi; Gharzouli, Akila (Journal of Agricultural and Food Chemistry, 2003)
The gastroprotective effects of 70% acetone extracts of Quercus suber and Quercus coccifera leaves and of tannins (pedunculagin, castalagin, phillyraeoidin A, and acutissimin B) purified from these extracts were examined in the mouse using the ethanol-induced gastric ulcer model. Both extracts (25, 50, and 100 mg/kg), given orally, prevented the formation of ethanol-induced lesions in the stomach. The percent protection varied between 68 and 91%. Purified tannins (50 mg/kg) were also effective in protecting the stomach against ethanol, and the percent protection varied from 66 to 83%. Castalagin was the most potent. Both extracts and all of the tannins tested (10, 25, and 50 ?g/mL) strongly inhibited (55?65%) the lipid peroxidation of rabbit brain homogenate. These results suggest that the gastroprotective effects of extracts of Q. suber and Q. coccifera leaves and the purified tannins in this experimental model are related to their anti-lipoperoxidant properties. Keywords: Experimental gastric ulcer; lipid peroxidation; medicinal plants; Quercus sp.; tannins; castalagin
From Duplicate 2 (Effect of Tannins from Quercus suber and Quercus coccifera Leaves on Ethanol-Induced Gastric Lesions in Mice - Khennouf, Seddik; Benabdallah, Hassiba; Gharzouli, Kamel; Amira, Smain; Ito, Hideyuki; Kim, Tae-Hoon; Yoshida, Takashi; Gharzouli, Akila)
Keywords: Acetone; Animals; Biphenyl Compounds; castalagin; Catechols; Catechols: therapeutic use; Ethanol; Experimental gastric ulcer; Hydrolyzable Tannins; lipid peroxidation; Lipid Peroxidation: drug effects; Male; Medicinal plants; Mice; Plant Extracts; Plant Extracts: chemistry; Plant Extracts: therapeutic use; Plant Leaves; Plant Leaves: chemistry; Quercus; Quercus sp.; Quercus: chemistry; Rabbits; Stomach Ulcer; Stomach Ulcer: chemically induced; Stomach Ulcer: prevention & control; Tannins; Tannins: pharmacology; Tannins: therapeutic use

Climatic changes since the Late-glacial/Holocene transition in La Mancha Plain (South-central Iberian Peninsula, Spain) and their incidence on Las Tablas de Daimiel - Dorado, Miriam; Rodr, Ana Valdeolmillos; Zapata, M Blanca Ruiz; Jos, M; Garc, Gil; Bustamante, Irene De (Quaternary International, 2002)
A palynological and lithological continuous record from La Mancha Plain (South-central Iberian Peninsula, Spain) is presented. The obtained results have permitted the reconstruction of the climatic evolution in the area since the Late-glacial/Holocene transition. The end of the Late-glacial was characterized by a cold and arid climate and it concluded at about 98907180 yr BP. In the Early Holocene a slight climatic amelioration began, being interrupted by a more arid phase around 8500 yr BP. The Holocene Climatic Optimum started from ca. 8000 yr BP and was characterized by higher temperatures and more humidity. During the MidHolocene–Late Holocene times a stage of marked aridity occurred towards 5000 yr BP that preceded the development of a dry mediterranean climate. Under this new climate a short-time arid phase took place around 2500 yr BP after which the mediterranean conditions became accentuated, with an increasing dry climate. This climatic evolution has affected the characteristics of the marshlands of Las Tablas de Daimiel National Park, originating changes in the sedimentary environment. This environment was mainly ﬂuvial until the end of the Holocene Climatic Optimum and became lacustrine–palustrine from the beginning of the more arid conditions.
Keywords: arid phase; Climatic conditions; Evergreen and deciduous species (voyant); Holocene; Pollen analysis; Quercus; Spain

Climatic changes since the Late-glacial/Holocene transition in La Mancha Plain (South-central Iberian Peninsula, Spain) and their incidence on Las Tablas de Daimiel - Dorado, Miriam; Rodr, Ana Valdeolmillos; Zapata, M. Blanca Ruiz; Jos, M.; Garc, Gil; Bustamante, Irene De (Quaternary International, 2002)
A palynological and lithological continuous record from La Mancha Plain (South-central Iberian Peninsula, Spain) is presented. The obtained results have permitted the reconstruction of the climatic evolution in the area since the Late-glacial/Holocene transition. The end of the Late-glacial was characterized by a cold and arid climate and it concluded at about 98907180 yr BP. In the Early Holocene a slight climatic amelioration began, being interrupted by a more arid phase around 8500 yr BP. The Holocene Climatic Optimum started from ca. 8000 yr BP and was characterized by higher temperatures and more humidity. During the MidHolocene–Late Holocene times a stage of marked aridity occurred towards 5000 yr BP that preceded the development of a dry mediterranean climate. Under this new climate a short-time arid phase took place around 2500 yr BP after which the mediterranean conditions became accentuated, with an increasing dry climate. This climatic evolution has affected the characteristics of the marshlands of Las Tablas de Daimiel National Park, originating changes in the sedimentary environment. This environment was mainly ﬂuvial until the end of the Holocene Climatic Optimum and became lacustrine–palustrine from the beginning of the more arid conditions.
Keywords: arid phase; Climatic conditions; Evergreen and deciduous species (voyant); Holocene; Pollen analysis; Quercus; Spain

Cryopreservation of Quercus suber and Quercus ilex embryonic axes: in vitro culture, desiccation and cooling factors. - Gonzalez-Benito, M Elena; Prieto, Roberto-Moreno; Herradon, Esther; Martin, Carmen (Cryo letters, 2002)
This study examines different factors included in the cryopreservation protocols for Quercus ilex and Q. suber embryonic axes. In vitro incubation temperature played an important role in the appropriate development of Q. ilex axes, as 15 degrees C was superior to 25 degrees C. Q. suber axes proved to be more sensitive to desiccation and cooling. Poor survival (35%) was observed when axes were included into cryovials and then in liquid nitrogen, and none when immersed in sub-cooled liquid nitrogen (-210 degrees C). Q. ilex axes showed poorly organised development in vitro (c. 50% of non-cooled axes showed shoot development). However, c. 80% survival was observed after cryopreservation (either in liquid nitrogen or sub-cooled liquid nitrogen at 0.34 g water / g dry weight), of which c. 15% showed shoot development.
Keywords: Cryopreservation; Cryopreservation: methods; Cryoprotective Agents; Cryoprotective Agents: pharmacology; Culture Techniques; Culture Techniques: methods; Desiccation; Desiccation: methods; embryonic axes; germination; germination temperature; Germination: drug effects; liquid nitrogen; plantlet development; Quercus; Quercus: embryology; Seeds; Seeds: chemistry; Seeds: embryology; Survival Rate; Temperature; water; Water: analysis

Evaluation of the disposal of firewood of ilex pruning (Quercus ilex) in Andalusia and its characterization for the manufacture of wood cellulose pulp. - Gutierrez, J A; Alcaide, L J; Carmona, J A; Blanco, M J D; Ot, I P; Baldovin, F L (AFINIDAD, 2002)
In this work, it is analyzed the production of firewood of the ilex pruning in Andalusia, its real disposa and future forecast. Chemical characteristics are studied, in comparison with otherr wood species: Pine (Pinus pinaster) and Eucalyptus (Eucalyptus globulus), in order to obtain wood cellulosic pulp for paper. The average firewood production of the ilex pruning corresponding to 1975-78 in Andalusia was of 78.000 T/year, with a practically uniform trend. A statistical analysis with ARMA pattern let us estimate a yearly averge production of ilex pruning firewood around 72.500 T/year for the 1999-2006 period, which could have an upward correction if the exploitation in all hoamoak woods was total. For the manufacture of cellulosic pulp from ilex pruning wood, it would be necessary to separte the cortex due to a lower content of holocellulose and alpha-cellulose and a higher content of soluble substances and lignin. The content of lignin of ilex pruning wood is lower than the one of other wood species like Pinus Pinaster (76,7%), Eucalyptus globulus (56,4%) and olive grove pruning (8%).
Keywords: Firewood; forest residues; ilex; Quercus; Wood

Measurement and characterization of cellulase activity in sclerophyllous forest litter. - Criquet, Stéven (Journal of microbiological methods, 2002)
Cellulases are enzymatic proteins which hydrolyze cellulose polymers to smaller oligosaccharides, cellobiose and glucose. They consist in three major types of enzymes: endoglucanases (EC 3.2.1.4), cellobiohydrolases (EC 3.2.1.91) and beta-glucosidases (EC 3.2.1.21) which play an essential role in carbon turnover of forest ecosystem. The aim of this study was firstly to determine the parameters (i.e. buffer type, pH, temperature, quantity of litter, incubation time and reagent type) which affect the measurement of cellulase activity in a sclerophyllous forest litter, and secondly to compare two methods for measuring cellulase activity: a direct method and an extraction method. In the direct method, the litter was directly incubated with a buffered solution containing the enzyme substrate, whereas in the extraction method, the cellulases were firstly extracted before measuring their activity. The results were compared with other studies about soil cellulase activity, and it appeared that several parameters (buffer type, pH, temperature and sample quantity) which influence the measurement of cellulase activity differ according to whether a soil or a litter is considered. Concerning the procedure used for the measurement of cellulase activity, results showed that the activity values were higher when using an extraction procedure than when using a direct procedure. The extraction procedure, combined with a concentration stage of the extract, also allowed electrophoretic analysis (PAGE) of the cellulases extracted from the litter. The electrophoretic pattern revealed two cellulase isoenzymes which may be related to the occurrence of two pH-activity peaks of these enzymes when citrate buffer was used for the measurement of cellulase activity in the litter.
The following values have no corresponding Zotero field: accession-num: 11997167
Keywords: Buffers; Cellulase; Cellulase: analysis; Cellulase: isolation & purification; Cellulose; Cellulose: metabolism; Endoglucanase; Extraction; Hydrogen-Ion Concentration; Isoenzyme; Isoenzymes; Isoenzymes: analysis; litter; Plant Leaves; Plant Leaves: enzymology; Quercus; Quercus: enzymology; Temperature; Trees

Measurement and characterization of cellulase activity in sclerophyllous forest litter. - Criquet, Stéven (Journal of microbiological methods, 2002)
Cellulases are enzymatic proteins which hydrolyze cellulose polymers to smaller oligosaccharides, cellobiose and glucose. They consist in three major types of enzymes: endoglucanases (EC 3.2.1.4), cellobiohydrolases (EC 3.2.1.91) and beta-glucosidases (EC 3.2.1.21) which play an essential role in carbon turnover of forest ecosystem. The aim of this study was firstly to determine the parameters (i.e. buffer type, pH, temperature, quantity of litter, incubation time and reagent type) which affect the measurement of cellulase activity in a sclerophyllous forest litter, and secondly to compare two methods for measuring cellulase activity: a direct method and an extraction method. In the direct method, the litter was directly incubated with a buffered solution containing the enzyme substrate, whereas in the extraction method, the cellulases were firstly extracted before measuring their activity. The results were compared with other studies about soil cellulase activity, and it appeared that several parameters (buffer type, pH, temperature and sample quantity) which influence the measurement of cellulase activity differ according to whether a soil or a litter is considered. Concerning the procedure used for the measurement of cellulase activity, results showed that the activity values were higher when using an extraction procedure than when using a direct procedure. The extraction procedure, combined with a concentration stage of the extract, also allowed electrophoretic analysis (PAGE) of the cellulases extracted from the litter. The electrophoretic pattern revealed two cellulase isoenzymes which may be related to the occurrence of two pH-activity peaks of these enzymes when citrate buffer was used for the measurement of cellulase activity in the litter.
Keywords: Buffers; Cellulase; Cellulase: analysis; Cellulase: isolation & purification; Cellulose; Cellulose: metabolism; Endoglucanase; Extraction; Hydrogen-Ion Concentration; Isoenzyme; Isoenzymes; Isoenzymes: analysis; litter; Plant Leaves; Plant Leaves: enzymology; Quercus; Quercus: enzymology; Temperature; Trees

Photosynthetic responses to water deficit in six Mediterranean sclerophyll species: possible factors explaining the declining distribution of Rhamnus ludovici-salvatoris, an endemic Balearic species. - Gulías, J; Flexas, J; Abadía, A; Madrano, H (Tree Physiology, 2002)
We sought to explain the declining distribution in the Balearic Islands of the endemic shrub Rhamnus ludovici-salvatoris R. Chodat, by comparing its photosynthetic response to drought with that of several widely distributed, competing Mediterranean species (R. alaternus L., Quercus ilex L., Pistacia lentiscus L., Q. humilis Mill. and P. terebinthus L.). [ABSTRACT FROM PUBLISHER]
Keywords: chlorophyll fluorescence; deciduous; Drought; evergreen; Gas exchange; leaf mass area; nitrogen; Pistacia; Quercus; Rhamnus; xanthophyll cycle

Trichomes and photosynthetic pigment composition changes: responses of Quercus ilex subsp. ballota (Desf.) Samp. and Quercus coccifera L. to Mediterranean stress conditions - Morales, F; Abadía, A; Abadia, J; Montserrat, G; Gil-Pelegrín, E (Trees, 2002)
Sun and shade leaves of two Mediterranean Quercus species, Quercus ilex subsp. ballota (Desf.) Samp. and Quercus coccifera L., were compared by measuring leaf optical properties, photosynthetic pigment composition and photosystem II efficiency. The presence of trichomes in the adaxial (upper) leaf surface of Q. ilex subsp. ballota seems to constitute an important morphological mechanism that allows this species to maintain a good photosystem II efficiency during the summer. Q. coccifera has almost no trichomes and seems instead to develop other physiological responses, including a smaller light-harvesting antenna size, higher concentrations of violaxanthin cycle pigments and a higher (zeaxanthin + antheraxanthin)/(violaxanthin + antheraxanthin + zeaxanthin) ratio. Q. coccifera was not able to maintain a good photosystem II efficiency up to the end of the summer. In Q. ilex subsp. ballota leaves, natural loss or mechanical removal of adaxial-face leaf trichomes induced short-term decreases in photosystem II efficiency. These changes were accompanied by deepoxidation of violaxanthin cycle pigments, suggesting that the absence of trichomes would trigger physiological responses in this species. Our data have revealed different patterns of response of Q. ilex subsp. ballota and Q. coccifera facing the stress conditions prevailing in the Mediterranean area.
Keywords: adaxial epidermis; photoprotection; Quercus; Trichomes

Trichomes and photosynthetic pigment composition changes: responses of Quercus ilex subsp. ballota (Desf.) Samp. and Quercus coccifera L. to Mediterranean stress conditions - Morales, F.; Abadia, A.; Abadía, J.; Montserrat, G.; GIL-PELEGRÍN, E. (Trees, 2002)
Sun and shade leaves of two Mediterranean Quercus species, Quercus ilex subsp. ballota (Desf.) Samp. and Quercus coccifera L., were compared by measuring leaf optical properties, photosynthetic pigment composition and photosystem II efficiency. The presence of trichomes in the adaxial (upper) leaf surface of Q. ilex subsp. ballota seems to constitute an important morphological mechanism that allows this species to maintain a good photosystem II efficiency during the summer. Q. coccifera has almost no trichomes and seems instead to develop other physiological responses, including a smaller light-harvesting antenna size, higher concentrations of violaxanthin cycle pigments and a higher (zeaxanthin + antheraxanthin)/(violaxanthin + antheraxanthin + zeaxanthin) ratio. Q. coccifera was not able to maintain a good photosystem II efficiency up to the end of the summer. In Q. ilex subsp. ballota leaves, natural loss or mechanical removal of adaxial-face leaf trichomes induced short-term decreases in photosystem II efficiency. These changes were accompanied by deepoxidation of violaxanthin cycle pigments, suggesting that the absence of trichomes would trigger physiological responses in this species. Our data have revealed different patterns of response of Q. ilex subsp. ballota and Q. coccifera facing the stress conditions prevailing in the Mediterranean area.
Keywords: adaxial epidermis; photoprotection; Quercus; Trichomes

Análisis de la variabilidad de adn de cloroplastos en Quercus ilex L., Q. suber L. Y Q. coccifera L.. - COLLADA, C; Jimenez, P; Gil, L (III Congreso Forestal Español, 2001)
Chloroplast (Cp) and mitochondrial (mt) DNA variation have been studied by PCR-RFLP in 14 location (13 with Q. suber, 12 with Q. ilex and 6 with Q. coccifera) along the natural distribution area of these species in the Iberian Peninsula. Five chloroplast DNA primers pairs and one mitochondrial DNA primer pair have been used, each one in combination with a restriction enzyme. 29 different haplotypes have been detected, In the case of Q. suber a characteristic haplotype, very divergent of the remaining ones has been described. Usually, species don’t share haplotypes within the same populations. The distribution of haplotypes suggests a geographical structuring. The levels of genetic differentiation are similar to those obtained in oaks.hS is significantly higher in Q. ilex (hS=0,262). Differentiation coefficients (Gst) are similar in the three species and indicate a high typical structuring of maternal markers.
Keywords: chloroplast DNA; differentiation; geographic distribution; Haplotypes; phylogeny; Quercus

Análisis de la variabilidad de adn de cloroplastos en Quercus ilex L., Q. suber L. Y Q. coccifera L.. - COLLADA, C.; JIMÉNEZ, P.; Gil, L. (III Congreso Forestal Español, 2001)
Chloroplast (Cp) and mitochondrial (mt) DNA variation have been studied by PCR-RFLP in 14 location (13 with Q. suber, 12 with Q. ilex and 6 with Q. coccifera) along the natural distribution area of these species in the Iberian Peninsula. Five chloroplast DNA primers pairs and one mitochondrial DNA primer pair have been used, each one in combination with a restriction enzyme. 29 different haplotypes have been detected, In the case of Q. suber a characteristic haplotype, very divergent of the remaining ones has been described. Usually, species don’t share haplotypes within the same populations. The distribution of haplotypes suggests a geographical structuring. The levels of genetic differentiation are similar to those obtained in oaks.hS is significantly higher in Q. ilex (hS=0,262). Differentiation coefficients (Gst) are similar in the three species and indicate a high typical structuring of maternal markers.
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español pub-location: Granada
Keywords: chloroplast DNA; differentiation; geographic distribution; Haplotypes; phylogeny; Quercus

Frequent cytoplasmic exchanges between oak species that are not closely related: Quercus suber and Q. ilex in Morocco - Belahbib, N; Pemonge, M.-H. H; Ouassou, A; Sbay, H; Kremer, A; Petit, R J (Molecular Ecology, 2001)
Chloroplast (cp) and mitochondrial (mt) DNA variation were studied in 97 populations of cork oak (Quercus suber) in Morocco; in 31 of these populations, holm oak (Quercus ilex), a clearly distinct species, also occurred and was compared with Q. suber. Three cpDNA and one mtDNA primer pairs were used in the survey, each in combination with one restriction enzyme. Six haplotypes belonging to two very divergent lineages were detected; one lineage predominates in each species, and is probably ancestral, as inferred from comparisons with other oak species. In the mixed-species populations, cytoplasmic genomes were frequently shared across species, as indicated by an introgression ratio of 0.63. This index is a new measure of the propensity of species to share locally genetic markers, varying from zero (complete differentiation) to one (no differentiation). By contrast, more closely related deciduous oak species (Q. robur, Q. petraea and Q. pubescens) have introgression ratios varying from 0.82 to 0.97. The introgression events appear to have been more frequent in the direction Q. ilex (female) × Q. suber (male), a finding which seems attributable to the flowering phenology of these two species. This asymmetry may have favoured immigration of Q. suber beyond its main range, in regions already colonized by Q. ilex. There, rare hybridization and further introgression through long distance pollen flow have established populations that are morphologically indistinguishable from Q. suber but that have cytoplasmic genomes originating from the local Q. ilex populations.
Keywords: Chloroplast; Chloroplast: genetics; cpDNA; DNA; Evolution; Genetic; Genetic Markers; Genetic Variation; Genetic: genetics; geographical structure; Haplotypes; Hybridization; introgression; Mitochondrial; Mitochondrial: genetics; Models; Molecular; Morocco; mtDNA; PCR–RFLP; Quercus; Quercus: genetics; Trees; Trees: genetics

Frequent cytoplasmic exchanges between oak species that are not closely related: Quercus suber and Q. ilex in Morocco - Belahbib, N.; Pemonge, M.-H. H.; Ouassou, A.; Sbay, H.; Kremer, A.; Petit, R. J. (Molecular Ecology, 2001)
Chloroplast (cp) and mitochondrial (mt) DNA variation were studied in 97 populations of cork oak (Quercus suber) in Morocco; in 31 of these populations, holm oak (Quercus ilex), a clearly distinct species, also occurred and was compared with Q. suber. Three cpDNA and one mtDNA primer pairs were used in the survey, each in combination with one restriction enzyme. Six haplotypes belonging to two very divergent lineages were detected; one lineage predominates in each species, and is probably ancestral, as inferred from comparisons with other oak species. In the mixed-species populations, cytoplasmic genomes were frequently shared across species, as indicated by an introgression ratio of 0.63. This index is a new measure of the propensity of species to share locally genetic markers, varying from zero (complete differentiation) to one (no differentiation). By contrast, more closely related deciduous oak species (Q. robur, Q. petraea and Q. pubescens) have introgression ratios varying from 0.82 to 0.97. The introgression events appear to have been more frequent in the direction Q. ilex (female) × Q. suber (male), a finding which seems attributable to the flowering phenology of these two species. This asymmetry may have favoured immigration of Q. suber beyond its main range, in regions already colonized by Q. ilex. There, rare hybridization and further introgression through long distance pollen flow have established populations that are morphologically indistinguishable from Q. suber but that have cytoplasmic genomes originating from the local Q. ilex populations.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd accession-num: 11555243
Keywords: Chloroplast; Chloroplast: genetics; cpDNA; DNA; Evolution; Genetic; Genetic Markers; Genetic Variation; Genetic: genetics; geographical structure; Haplotypes; Hybridization; introgression; Mitochondrial; Mitochondrial: genetics; Models; Molecular; Morocco; mtDNA; PCR–RFLP; Quercus; Quercus: genetics; Trees; Trees: genetics

Water stress responses of seedlings of four Mediterranean oak species - Fotelli, M N; Radoglou, K M; Constantinidou, H.-I. A (Tree Physiology, 2000)
Effects of water stress on phenology, growth, stomatal activity and water status were assessed from April to November 1996 in 2-year-old seedlings of Quercus frainetto Ten. (Quercus conferta Kit.), Quercus pubescens Willd., Quercus macrolepis Kotschy (Quercus aegilops auct.) and Quercus ilex L. growing in containers in northern Greece. All four species developed more than 50% of their total leaf area before the beginning of June—an adaptation to arid climates. Well-irrigated plants tended to develop greater individual leaf area, number of leaves per plant, total plant leaf area, height and root:shoot ratios than water-stressed plants, but the difference between treatments was not significant for any parameter in any species. Quercus macrolepis appeared to be the most drought-tolerant of the four species. It maintained the highest number of leaves of the smallest size and increased the proportion of fine roots during drought. In all species, drought caused significant decreases in stomatal conductance and predawn and midday water potentials from mid-July until the end of August, when the lowest soil water content and highest mean daily air temperatures and midday leaf temperatures occurred; however, the responses were species-specific. Among the four species, Quercus macrolepis sustained the highest stomatal conductance despite very low water potentials, thus overcoming drought by means of desiccation tolerance. Quercus ilex decreased stomatal conductance even before severe water stress occurred, thereby avoiding dessication during drought. Quercus pubescens had the highest water potential despite a high stomatal conductance, indicating that its leaf water status was independent of stomatal activity. Quercus frainetto was the least drought-resistant of the four species. During drought it developed very low water potentials despite markedly reduced stomatal aperture.
10.1093/treephys/20.16.1065
Keywords: Growth; Phenology; Quercus; Stomatal conductance; water potential

Biodiversity of woody species in oak woodlands of southern Spain and northern Morocco - MARAÑÓN, T; Ajbilou, R; Ojeda, F; Arroyo, J (Forest Ecology and Management, 1999)
Three biodiversity parameters ± species richness, endemic species richness and taxonomic singularity ± have been evaluated for the woody understorey of oak woodlands on sandstone-derived substrates, on both sides of the Strait of Gibraltar. There is a similarity in ¯oristic composition and ecological distribution of woody plant communities across the Strait. Nevertheless, we have detected signi®cant differences. These include a general reduction in species richness, number of endemic species and taxonomic singularity (at the community level), and a greater abundance of widespread, generalist species, on the southern side (Moroccan) communities, as compared to the north (Spanish ones). We interpret these differences as partly caused by the contrasting management of woodlands, with higher slashing and browsing pressure in Morocco.
Keywords: Cork oak; diversity; Mediterranean woodlands; Quercus; Species richness; strait of gibraltar

The development of a protocol for the encapsulation-desiccation and in vitro culture of embryonic axes of Quercus suber L-and Q-ilex L. - Gonzalez-Benito, M E; Herradon, E; Martin, C (SILVAE GENETICA, 1999)
Quercus species have seeds recalcitrant against long-term storage. Cryopreservation of embryonic axes could be a feasible way of preserving their genetic diversity. Several cryopreserva- tion protocols are based on desiccation, among them the so- called encapsulation-dehydration. However, it is previously necessary to establish an adequate in vitro culture develop- ment of desiccated axes. Embryonic axes of Q. suber and Q. ilex were aseptically excised, encapsulated in alginate beads, cultur- ed in a sucrose-rich liquid medium, desiccated for different periods in a flow bench and cultured on basal WPM medium. Moisture content of encapsulated axes dropped from 74% to 71% (fresh weigh basis) to 24.5% to 21% after 6 h desiccation, respectively for the two species. Germination decreased to 20% in both species. Germination and shoot elongation of encapsu- lated embryos (non-desiccated or desiccated for 4 h) was stud- ied for both species after culture on WPM medium supplemented with different concentrations of BAP and IBA. Medium with 0.1 mgl-1 BAP resulted in a high percentage of germina- tion and development of shoots in both species
Keywords: aliginate bead; Dehydration; in vitro culture; oak; Quercus; recalcitrant seed

Egg development and diapause: ecophysiological and genetic basis of phenological polymorphism and adaptation to varied hosts in the green oak tortrix, Tortrix viridana L-(Lepidoptera : Tortricidae) - Du Merle, P (JOURNAL OF INSECT PHYSIOLOGY, 1999)
Experiments concerned 8 tortrix populations associated with varied oak species. They showed that the egg development included a phase of diapause. Completion of embryogenesis at 20 degrees C was used as a criterion for whether diapause was completed. Under semi-natural conditions diapause terminated in late autumn or early winter, then eggs developed continuously, without postdiapause winter quiescence, even in severe cold. The eggs from the populations associated with helm or cork oak completed diapause then hatched later than those from the populations associated with sessile or pubescent oak. Reciprocal crossbreedings confirmed that this phenological polymorphism was genetically determined. Under constant temperatures the physiological state of diapausing eggs, assessed by measuring their cold requirements to complete diapause by exposure to 8 degrees C, varied gradually with increasing age. This diapause development was strongly temperature-dependent. Cold requirements of diapausing eggs were much higher in a late-hatching than in an early-hatching population. This explains the phenological polymorphism of the tortrix: the more eggs need cold, the later they complete diapause in autumn, and the later they hatch in spring. Egg cold requirements varied widely within populations too, which resulted in large variations in the date of diapause end among individuals. The dare of egg hatch was influenced by the temperatures occurring during diapause and postdiapause, but apparently not by photoperiod. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: diapause; egg development; phenological polymorphism; Quercus; Tortrix viridana

Molecular-cytogenetic studies of ribosomal genes and heterochromatin reveal conserved genome organization among 11 Quercus species - Zoldos, V; Papes, D; Cerbah, M; Panaud, O; Besendorfer, V; Siljak-Yakovlev, S (TAG Theoretical and Applied Genetics, 1999)
Genomes of 11 Quercus species were characterized using cytogenetic (Giemsa C-banding, fluorochrome banding), molecular-cytogenetic (fluorescence in situ hybridization, FISH, to ribosomal genes) and molecular (dot-blot for ribosomal gene-copy number assessment) techniques. Ribosomal genes are the first DNA sequences to be physically mapped in oaks, and the copy number of the 18S-5.8S-26 S rRNA genes is estimated for the first time. Oak karyotypes were analysed on the basis of DAPI banding and FISH patterns; five marker chromosomes were found. In addition, chromosomal organization of ribosomal genes with respect to AT- and GC-differentiated heterochromatin was studied. Fluorochrome staining produced very similar CMA/DAPI banding patterns, and the position and number of ribosomal loci were identical for all the species studied. The 18S-5.8S-26 S rRNA genes in oak complements were represented by a major locus at the subterminal secondary constriction (SC) of the only subtelocentric chromosome pair and a minor locus at paracentromeric SC of one metacentric pair. The only 5 S rDNA locus was revealed at the paracentromeric region of the second largest metacentric pair. A striking karyotypic similarity, shown by both fluorochrome banding and FISH patterns, implies close genome relationships among oak species no matter their geographic origin (European or American) or their ecophysiology (deciduous or evergreens). Dot-blot analysis gave preliminary evidence for different copy numbers of 18S-5.8S-26 S rRNA genes in diploid genomes of Q. cerris, Q. ilex, Q. petraea, Q. pubescens and Q. robur (2700, 1300, 2200, 4000 and 2200 copies, respectively) that was correlated with the size polymorphism of the major locus.
Keywords: 18S-5.8S-26 S and 5 S rRNA genes; FISH; Fluorochrome banding; Heterochromatin; karyotype; Quercus

Root and shoot hydraulic conductance of seven Quercus species - Nardini, Andrea; Tyree T., Melvin (Ann. For. Sci., 1999)
The root (KR) and shoot (KS) hydraulic conductances of seven different Quercus species, as well as the leaf blade hydraulic resistance (RLL), were measured in potted plants with the aim of understanding whether a relationship exists between the hydraulic architecture and the general ecological behaviour of different species of this genus. The KR values were scaled by dividing by root surface area (KRR) and by leaf surface area (KRL) and the KS values were scaled by dividing by leaf surface area (KSL). The likely drought-adapted species (Quercus suber, Q. pubescens, Q. petraea) showed lower KRL and KRR, lower KSL and higher RLL with respect to the known water-demanding species (Q. alba, Q. cerris, Q. robur, Q. rubra). The possible physiological and ecological significance of such differences are discussed.
Keywords: high pressure flow meter; leaf blade resistance; Quercus; Root hydraulic conductance; shoot hydraulic conductance

Terpenoid emissions of Mediterranean oaks and their relation to taxonomy - Csiky, O; Seufert, G (ECOLOGICAL APPLICATIONS, 1999)
This paper presents results of a laboratory screening study of biogenic emissions from Mediterranean oak species. The experiment aimed at improving our understanding of oak contributions to overall emissions of volatile organic compounds and to the atmospheric chemistry in the Mediterranean area. We measured type and amount of terpenoid emissions (isoprene, mono- and sesquiterpenes) under standard conditions of light and temperature from 14 different Quercus species of Mediterranean and American origin. Tree saplings were exposed in a controlled environment chamber, and leaf-level trace-gas exchange was analyzed with a minicuvette system and gas chromatography, to study the relation between the emission types and emission spectra found and the taxonomy of Quercus. The holarctic group Lepidobalanus and the North American groups Erythrobalanus and Protobalanus were found to be strong isoprene emitters. The Eurasian oak group Sclerophyllodrys emits monoterpenes; Cerris include mostly non-emitters, but also an isoprene and a monoterpene emitter has been found in this group. Results are discussed with respect to their implications for presently used emission scenarios.
Keywords: atmospheric chemistry; BEMA (Biogenic Emissions in the Mediterranean Area; Biogenic emission; chemo-taxonomy; isoprene; Mediterranean Region; Monoterpenes; oak taxonomy; oaks; Quercus; terpenoid emissions; trace-gas exchange; volatile organic compounds (VOCs)

Terpenoid emissions of Mediterranean oaks and their relation to taxonomy - Csiky, O.; Seufert, G. (ECOLOGICAL APPLICATIONS, 1999)
This paper presents results of a laboratory screening study of biogenic emissions from Mediterranean oak species. The experiment aimed at improving our understanding of oak contributions to overall emissions of volatile organic compounds and to the atmospheric chemistry in the Mediterranean area. We measured type and amount of terpenoid emissions (isoprene, mono- and sesquiterpenes) under standard conditions of light and temperature from 14 different Quercus species of Mediterranean and American origin. Tree saplings were exposed in a controlled environment chamber, and leaf-level trace-gas exchange was analyzed with a minicuvette system and gas chromatography, to study the relation between the emission types and emission spectra found and the taxonomy of Quercus. The holarctic group Lepidobalanus and the North American groups Erythrobalanus and Protobalanus were found to be strong isoprene emitters. The Eurasian oak group Sclerophyllodrys emits monoterpenes; Cerris include mostly non-emitters, but also an isoprene and a monoterpene emitter has been found in this group. Results are discussed with respect to their implications for presently used emission scenarios.
The following values have no corresponding Zotero field: pub-location: 1707 H ST NW, STE 400, WASHINGTON, DC 20006-3915 USA publisher: ECOLOGICAL SOC AMER
Keywords: atmospheric chemistry; BEMA (Biogenic Emissions in the Mediterranean Area; Biogenic emission; chemo-taxonomy; isoprene; Mediterranean Region; Monoterpenes; oak taxonomy; oaks; Quercus; terpenoid emissions; trace-gas exchange; volatile organic compounds (VOCs)

Genome size and base composition of seven Quercus species: inter- and intra-population variation - Zoldo, V; Pape, D; Brown, S C; Panaud, O; Zoldos, V; Papes, D; Siljak-Yakovlev, S (Genome, 1998)
Seven Quercus species, four deciduous (Q. cerris, Q. petraea, Q. pubescens, andQ. robur) and three evergreen (Q. coccifera, Q. ilex, andQ. suber), were assessed for DNA content. Their genome sizes ranged from 1.88 to 2.00 pg/2C, namely an interspecific DNA content variation of 6%. In addition, the DNA content of several populations of Q. petraea andQ. robur with different geographical origins, French and Croatian, was estimated. DNA content did not vary among four populations of Q. robur, but did differ between two populations of Q. petraea, the French population having a higher 2C DNA value than the Croatian. The genome size of this French population showed important dispersion among 10 measured individuals. This was in accordance with subsequent cytogenetic data that revealed extra chromosomes in some individuals from this population. The percent GC varied little between the species; a GC content of 39.9% is established as typical for oak.Key words: Quercus, flow cytometry, genome size, GC percent, DNA content variations, extra chromosomes.
Keywords: DNA content variations; extra chromosomes; flow cytometry; GC percent; genome size; Quercus

Hydrological influences on the resilience of Quercus spp. dominated geoecosystems in central Spain - Bergkamp, Ger (Geomorphology, 1998)
Differences in vegetation cover within a landscape having a similar land use history, can be used to identify differences in recovery following disturbance according to landscape position. The objective of this study was to determine the resilience of oak-dominated communities at different landscape positions in a research area in central Spain as indicated by the relative recovery of Quercus ilex and Q. coccifera, and to relate this to the most important hydrological processes and properties at the slope sections scale. The results indicate that the geoecosystems on slope sections on north-facing slopes are more resilient than those on south-facing slopes. On the more degraded shrubland sites, the higher values of vegetation cover on the lower slope sections indicate the systems on these slope sections to be more resilient than those on the slope sections located higher up the slope. The hydrological factors that could possibly explain differences in vegetation type and cover were found to be distance to water resources at greater depths and incoming radiation controlling evapotranspiration. A conceptual model is presented that links the resilience of these systems to the hydrological conditions. On the basis of the presented model, it is postulated that recovery of the system is determined partly by access to deep water resources. It is suggested that differences in or degree of access to such water resources may cause these comparably looking systems to react differently to degradation and recovery
Keywords: Mediterranean; Quercus; resilience; Shrubland; water balance

Hydrological influences on the resilience of Quercus spp. dominated geoecosystems in central Spain - Bergkamp, Ger (Geomorphology, 1998)
Differences in vegetation cover within a landscape having a similar land use history, can be used to identify differences in recovery following disturbance according to landscape position. The objective of this study was to determine the resilience of oak-dominated communities at different landscape positions in a research area in central Spain as indicated by the relative recovery of Quercus ilex and Q. coccifera, and to relate this to the most important hydrological processes and properties at the slope sections scale. The results indicate that the geoecosystems on slope sections on north-facing slopes are more resilient than those on south-facing slopes. On the more degraded shrubland sites, the higher values of vegetation cover on the lower slope sections indicate the systems on these slope sections to be more resilient than those on the slope sections located higher up the slope. The hydrological factors that could possibly explain differences in vegetation type and cover were found to be distance to water resources at greater depths and incoming radiation controlling evapotranspiration. A conceptual model is presented that links the resilience of these systems to the hydrological conditions. On the basis of the presented model, it is postulated that recovery of the system is determined partly by access to deep water resources. It is suggested that differences in or degree of access to such water resources may cause these comparably looking systems to react differently to degradation and recovery
Keywords: Mediterranean; Quercus; resilience; Shrubland; water balance

A hypothesis on the evolution of isoprenoid emission by oaks based on the correlation between emission type and Quercus taxonomy - Loreto, Francesco; Ciccioli, Paolo; Brancaleoni, Enzo; Valentini, Riccardo; De Lillis, Manuela; Csiky, Olav; Seufert, Guenther (Oecologia, 1998)
We show that Mediterranean oaks that emit isoprene, monoterpenes or no isoprenoids belong to dierent subgenera as indicated by morpho-taxonomy and molecular genetics. On the other hand, oaks from North America and Asia that are taxonomically similar to the Mediterranean monoterpene emitter Q. ilex emit isoprene only. We surmise that isoprene emission is a genetic character which evolved ancestrally in the oak genus since this is the prevalent emission type in oaks widespread around the world and adapted to dierent environments. This ancestral character may have been either lost or modi®ed in more recent clades such as those originating the Mediterranean oaks. If our hy- pothesis is correct then the taxonomy of European oaks is validated by this independent trait. Isoprenoid emis- sion could serve as a chemo-taxonomical marker and could be used to reconstruct the phylogeny of oaks in association with molecular markers.
Keywords: chemo-taxonomy; Evolution; isoprenoid emission; Quercus

ITS sequences from nuclear rDNA suggest unexpected phylogenetic relationships between Euro-Mediterranean, East Asiatic and North American taxa ofQuercus ( - Samuel, Rosabelle; Bachmair, Andreas (Plant systematics and …, 1998)
Nucleotide sequences from the internal transcribed spacer (ITS) regions of the 18S-26S nuclear ribosomal DNA have been studied from ten species of Quercus (representing four subgenera), Castanea sativa and Fagus sylvatica, as a preliminary molecular contribution to the still poorly understood systematics and evolution of Fagaceae. The resulting matrix has been used to calculate pair-wise sequence divergence indices and to construct a maximum parsimony tree for Quercus coding indels as a fifth state. Divergence is greater for Quercus vs. Fagus than for Quercus vs. Castanea. The tree for the Quercus taxa studied reveals two clearly divergent clades. In clade I the evergreen W Mediterranean Q. suber appears in a basal position as sister to more distal deciduous taxa, i.e. the E Mediterranean Q. macrolepis and the E Asiatic Q. acutissima (all formerly united as different sections under the apparently polyphyletic subg. Cerris), and Q. rubra (a representative of the N American subg. Erythrobalanus), forming a pair with Q. acutissima. In clade II the evergreen southeastem N American Q. virginiana is basal and sister to the remaining three branches, i.e. a pair of evergreen Mediterranean taxa with Q. ilex and Q. coccifera (subg. Sclerophyllodrys), the deciduous but otherwise plesiomorphic SE European/SW Asiatic Q. cerris (type species of subg. Cerris), and the related but more apomorphic European pair Q. petraea and Q. robur (subg. Quercus). These results partly conflict with current taxonomic classification but a_re supported by some anatomical and morphological characters. They document polyphyletic lines from evergreen to deciduous taxa and suggest Tertiary transcontinental connections within the genus.
Keywords: Castanea; Fagaceae; Fagus. - Nuclear rDNA; ITS; molecular phylogeny; molecular systematics; N Hemisphere; Phytogeography; Quercus

Response of foliar metabolism in mature trees of Quercus pubescens and Quercus ilex to long-term elevated CO 2 - Tognetti, Roberto; Johnson, J. D. (Environmental and Experimental Botany, 1998)
Long-term effects on and adaptations of the carbon physiology of long-lived trees exposed to increasing atmospheric levels of CO2 are unknown. We compared two indigenous Quercus species, Q. ilex and Q. pubescens, growing in a natural CO2 spring located in central Italy and at a nearby control site. In May, 1995 photosynthetic rate at least doubled when measured with supplemental CO2 in both species and sites. Dark respiration was much higher at the CO2 spring site in both species. Foliar sugar and starch concentrations in Q. ilex exhibited signiﬁcant site and diurnal differences (May and September). In July, 1995 there was little difference in the water potential values of the measured trees at the different sites over the diurnal period. Photosynthetic rate was higher for both species in the CO2 spring, particularly in the early morning and late afternoon. Mid-day stomatal closure reduced photosynthesis to similar levels. In the morning leaf conductance and transpiration were generally lower in the CO2 spring trees, contributing to higher instantaneous water use efﬁciency for both species. Isoprene emission rates were higher in Q. pubescens trees growing in the CO2 spring. The maximum difference between control and CO2 spring trees occurred in late afternoon. In contrast, Q. ilex exhibited isoprene emission near background level. Foliage and branch carbon and nitrogen status showed increased concentrations of starch and tannins in Q. ilex and of soluble sugars in Q. pubescens in the elevated CO2 environment, while nitrogen concentration decreased in both species. Wood gravity increased 6 and 3% in Q. ilex and Q. pubescens, respectively, growing in the CO2 spring. Q. ilex exhibited afternoon recovery of water potential compared to Q. pubescens which had better night-time recovery. Q. ilex and Q. pubescens exposed to elevated CO2 for prolonged periods exhibit different mechanisms for dealing with additional reduced carbon and do maintain an altered carbon physiology, even in midst of the region’s characteristic summer drought
Keywords: Elevated CO2; Gas exchange; natural CO2 springs; Quercus; Secondary compounds

Response of foliar metabolism in mature trees of Quercus pubescens and Quercus ilex to long-term elevated CO 2 - Tognetti, Roberto; Johnson, J D (Environmental and Experimental Botany, 1998)
Long-term effects on and adaptations of the carbon physiology of long-lived trees exposed to increasing atmospheric levels of CO2 are unknown. We compared two indigenous Quercus species, Q. ilex and Q. pubescens, growing in a natural CO2 spring located in central Italy and at a nearby control site. In May, 1995 photosynthetic rate at least doubled when measured with supplemental CO2 in both species and sites. Dark respiration was much higher at the CO2 spring site in both species. Foliar sugar and starch concentrations in Q. ilex exhibited signiﬁcant site and diurnal differences (May and September). In July, 1995 there was little difference in the water potential values of the measured trees at the different sites over the diurnal period. Photosynthetic rate was higher for both species in the CO2 spring, particularly in the early morning and late afternoon. Mid-day stomatal closure reduced photosynthesis to similar levels. In the morning leaf conductance and transpiration were generally lower in the CO2 spring trees, contributing to higher instantaneous water use efﬁciency for both species. Isoprene emission rates were higher in Q. pubescens trees growing in the CO2 spring. The maximum difference between control and CO2 spring trees occurred in late afternoon. In contrast, Q. ilex exhibited isoprene emission near background level. Foliage and branch carbon and nitrogen status showed increased concentrations of starch and tannins in Q. ilex and of soluble sugars in Q. pubescens in the elevated CO2 environment, while nitrogen concentration decreased in both species. Wood gravity increased 6 and 3% in Q. ilex and Q. pubescens, respectively, growing in the CO2 spring. Q. ilex exhibited afternoon recovery of water potential compared to Q. pubescens which had better night-time recovery. Q. ilex and Q. pubescens exposed to elevated CO2 for prolonged periods exhibit different mechanisms for dealing with additional reduced carbon and do maintain an altered carbon physiology, even in midst of the region’s characteristic summer drought
Keywords: Elevated CO2; Gas exchange; natural CO2 springs; Quercus; Secondary compounds

Seasonal and annual changes in leaf δ13C in two co-occurring Mediterranean oaks: relations to leaf growth and drought progression - Damesin, C; Rambal, S; Joffre, R (Functional Ecology, 1998)
1. Changes of δ13C and its relation to leaf development, biochemical content and water stress were monitored over a 2 year period in two co-occurring Mediterranean oak species: the deciduous Quercus pubescens and the evergreen Quercus ilex. 2. The time course of leaf δ13C showed different patterns in the two species. Young Q. pubescens leaves had a high δ13C and a marked decrease occurred during leaf growth. In contrast, leaves at budburst and maturity did not differ significantly in the case of Q. ilex. We suggest that the difference between δ13C of young leaves was linked to differential use of reserves of carbon compounds in the two species. 3.δ13C values of mature leaves were negatively correlated with minimum seasonal values of predawn water potential, suggesting that a functional adjustment to water resources occurred. 4. There was a significant correlation between individual δ13C values for two successive years. This interannual dependence showed that δ13C rankings between trees were constant through time.
Keywords: Biochemical content; isotope composition; leaf development; Quercus; water constraint

Anatomical changes and evolutionary trends in the foliar epidermis of extant and fossil Euro-Mediterranean oaks (Fagaceae) - Uzunova, K; Palamarev, E; Ehrendorfer, F (Plant systematics and Evolution, 1997)
The differentiation of foliar epidermis structures, cuticles, stomata, and indumen- turn of most of the extant Euro-Mediterranean taxa of Quercus have been studied by light and scanning electron microscopy, and compared with other genera and fossil material. Results allow the recognition of the subgg. Sclerophyllodrys, Cerris and Quercus, and of various sections and even individual species. The cyclocytic stomata type, regarded as plesiomorphic, is found in the geologically oldest representatives of the familiy (DryophylIum, resp. Eotrigonobalanus) and in the relatively old, evergreen to semi-evergreen species of Quercus subgg. Sclerophyllodrys and Cerris. These taxa also have relatively thick and smooth cuticles. Anomocytic stomata, thinner cuticles and the presence of crystalline wax flakes are regarded as apomorphic features and characterize the deciduous taxa ofsubg. Quercus. These changes are interpreted as ecological adaptations to the changing climates from the Tertiary to the present. An analysis of the various character combinations found in macrofossils and the often poor species separation i n Quercus suggest that hybridization has played a major role in the evolution of the Euro-Mediterranean oaks.
Keywords: epidermis characters; evolutionary trends; Fagaceae; fossil and extant taxa; Quercus

Anatomical changes and evolutionary trends in the foliar epidermis of extant and fossil Euro-Mediterranean oaks (Fagaceae) - Uzunova, K.; Palamarev, E.; Ehrendorfer, F. (Plant systematics and Evolution, 1997)
The differentiation of foliar epidermis structures, cuticles, stomata, and indumen- turn of most of the extant Euro-Mediterranean taxa of Quercus have been studied by light and scanning electron microscopy, and compared with other genera and fossil material. Results allow the recognition of the subgg. Sclerophyllodrys, Cerris and Quercus, and of various sections and even individual species. The cyclocytic stomata type, regarded as plesiomorphic, is found in the geologically oldest representatives of the familiy (DryophylIum, resp. Eotrigonobalanus) and in the relatively old, evergreen to semi-evergreen species of Quercus subgg. Sclerophyllodrys and Cerris. These taxa also have relatively thick and smooth cuticles. Anomocytic stomata, thinner cuticles and the presence of crystalline wax flakes are regarded as apomorphic features and characterize the deciduous taxa ofsubg. Quercus. These changes are interpreted as ecological adaptations to the changing climates from the Tertiary to the present. An analysis of the various character combinations found in macrofossils and the often poor species separation i n Quercus suggest that hybridization has played a major role in the evolution of the Euro-Mediterranean oaks.
Keywords: epidermis characters; evolutionary trends; Fagaceae; fossil and extant taxa; Quercus

EFECTO DE DISTINTOS TIPOS DE ENVASE, SUSTRATO y GRADOS DE ENDURECIMIENTO EN LA PRODUCCIÓN DE PLANTA DE QUERCUS SUBER L. y QUERCUS ROTUNDIFOLIA LAM. - SUÁREZ, Ma ANGELES; ÁZQUEZ, FRANCISCO V; Baselga, Pilar (II Congreso Forestal Español, 1997)
Different treatments about olm oak (Quercus rotundifolia Lam.) and cork oak (Quercus suber L.) plants' production are comparied. It has been worked with two kinds of containers, three kinds of substratums and two degrees of plants' protection during the cultivation
Keywords: Cork oak; Nursery; Olm oak; Plant's production; Quercus

EFECTOS DE DISTINTOS TRATAMIENTOS EN VIVERO EN EL ARRAIGO Y PRIMER DESARROLLO EN CAMPO DE PLANTAS DE QUERCUS SUBER L. y QUERCUS ROTUNDIFOLIA LAM .. EFECTO DEL PROTECTOR. - Suarez, M Ángeles; VÁzquez, Francisco; Baselga, Pilar; Torres, Enrique; CUEVAS, SERAFÍN (II Congreso Forestal Español, 1997)
The rootting ability and the first developes of cork oak and olm oak seedlings cultivated on different substratums and containers, as well as different harding degrees are comparied. The individual protector's effect is also analyzed.
Keywords: Cork oak; Nursery; Olm oak; Plant's production; Quercus; Reforestation

FORESTACIÓN CON CUATRO ESPECIES (Quercus coccifera L., Q.faginea Lam., Q. rotundifolia y Q. suber L.) DE FRONDOSAS EN EXTREMADURA P.M. - Vázquez, F M; Suárez, M A; TORRES, E; CUEVAS, S (II Congreso Forestal Español, 1997)
The principal species of interest in order to form forests of mediterranean type (not of riverside) in the South half of the Iberian Peninsula are the genus Quercus L ones. In this work the outputs contrasted of development are introduced, 1 root and systems of protection utilized in a mixed afforestation with four species of the cited genus (Q. coccifera L., Q. faginea Lam., Q. rotundifolia Lam., Q. suber L.), in Extremadura (Spain). The analysis of the data offers different strategies in sylviculture for the forest recuperation of the zone in function of the species that utilize
Keywords: Afforestation; coccifera; Extremadura; faginea; Quercus; rotundifolia; suber; sylvicuIture

Isoprenoid emission of oak species typical for the Mediterranean area: Source strength and controlling variables - Steinbrecher, Rainer; Hauff, Karin; Rabong, Richard; Steinbrecher, Jutta (Atmospheric Environment, 1997)
easurements of isoprenoid emission on five Mediterranean oak species in the field revealed that Quercu.s frainetto, Quercus petraea and Quercus pubescens are strong emitters of isoprene. In contrast Quercus cerris and Quercus suber emitted no significant amounts of isoprene and monoterpenes. For Q. pubenscens and Q. frainetto median emission factors of 16.68 nmoIm-2s-1 (86.06 pgg-’ dw h-‘) and 30.72 nmolrn-2s-1 (133.95 pgg-’ dw h-l) were calculated, respectively. The 25 to 75 percentiles span of the emission factor data sets ranged from - 53% to + 56% of the median values. Light and temperature are the main controlling factors for isoprene emission. The influence of other environmental and plant physiological parameters on the isoprene emission is discussed. The “Guenther” emission algorithm is able to predict the daily maximum of the isoprene emission within the plant specific uncertainty range. However, the morning increase and the afternoon drop in the isoprene emission is not well parameterized. On the basis of process oriented models for the synthesis of isoprene in plants, a further reduction in the uncertainty may be achieved resulting in a more reliable prediction of short-time variation in isoprene emission
Keywords: biogenic voc; Emission factors; isoprene; Monoterpene; Quercus

Isoprenoid emission of oak species typical for the Mediterranean area: Source strength and controlling variables - Steinbrecher, Rainer; Hauff, Karin; Rabong, Richard; Steinbrecher, Jutta (Atmospheric Environment, 1997)
easurements of isoprenoid emission on five Mediterranean oak species in the field revealed that Quercu.s frainetto, Quercus petraea and Quercus pubescens are strong emitters of isoprene. In contrast Quercus cerris and Quercus suber emitted no significant amounts of isoprene and monoterpenes. For Q. pubenscens and Q. frainetto median emission factors of 16.68 nmoIm-2s-1 (86.06 pgg-’ dw h-‘) and 30.72 nmolrn-2s-1 (133.95 pgg-’ dw h-l) were calculated, respectively. The 25 to 75 percentiles span of the emission factor data sets ranged from - 53% to + 56% of the median values. Light and temperature are the main controlling factors for isoprene emission. The influence of other environmental and plant physiological parameters on the isoprene emission is discussed. The “Guenther” emission algorithm is able to predict the daily maximum of the isoprene emission within the plant specific uncertainty range. However, the morning increase and the afternoon drop in the isoprene emission is not well parameterized. On the basis of process oriented models for the synthesis of isoprene in plants, a further reduction in the uncertainty may be achieved resulting in a more reliable prediction of short-time variation in isoprene emission
Keywords: biogenic voc; Emission factors; isoprene; Monoterpene; Quercus

SEGUIMIENTO MEDIANTE IMAGENES LANDSAT -TM DE LOS DAÑOS PRODUCIDOS POR UN PERIODO PROLONGADO DE SEQUÍA SOBRE ENCINARES EN SIERRA MORENA ( CÓRDOBA ): PRIMEROS RESULTADOS - NAVARRO, R M; FERNÁNDEZ, P; CHANFREUT, M R; GONZÁLEZ, M P (II Congreso Forestal Español, 1997)
NDVI (Normalized Difference Vegetation Index) images generated from LANDSAT- TM data were recently used to monitor large scale drought patterns and their climatic impact on vegetation. The purpose of this study is to use of the NDVI and SA VI to assess regional drought impacts. A temporal data for the period of July 1991 to September 1995 were used to produce NDVI and SA VI images of region in north Córdoba. Drought areas were delineated with certain threshold values of those indexes. Drought patterns delinated by the NDVI and SA VI reflected anomalies because of vegetation cover. It is suggested that NDVI may be used to construct a large scale drouhgt control model, but a further research should be carry out to analyze temporal and spatial evolution of regional drought.
Keywords: Draught; Quercus; Remote sensing

Vegetative compatibility and pathogenicity of Diplodia mutila isolates on oak - Ragazzi, A. (European journal of forest pathology, 1997)
Forty isolates of Diplodia mutila, a dieback agent on oaks were characterized by their capacity to produce heterokaryons, by their vegetative compatibility, and by their pathogenicity tests on Quercus cerris. The forty isolates were collected from Quercus cerris, Quercus frainetto, Quercus ilex, Quercus pubescens, Quercus robur and Quercus suber in different regions in Italy. Three nit mutants (nit,, nit, and nit,) were identified with different nitrogen sources: sodium nitrite, sodium nitrate, uric acid, ammonium tartrate and hypoxanthine. O n the two nutrient media employed, a potato dextrose agar (PDA) medium with chlorate (PDC), and a minimal agar medium with chlorate (MMC), isolates obtained from Q. cerris Felded the greatest number of mutants: 254 on PDC (out of a total of 583) and 190 on MMC (out o a total of 440). Nine vegetative compatibility grou s (VCGs) were identified. There was a strong association between these VCGs and host species. Alfisolates tested except one from Q. cerris were pathogenic.
Keywords: diplodia mutila; disease (voyant); nit mutants; Pathogenicity; Quercus; vegetative compatibility

Drought and photosystem II activity in two Mediterranean oaks - Méthy, M; Damesin, C; Rambal, S (Ann. For. Sci., 1996)
The responses of photosystem II (PS II) to drought were analysed on two Mediterranean oak species, Quercus ilex and Q pubescens, using the chlorophyll fluorescence pulse-amplitude-modulation technique. The maximal PS II photochemical efficiency (Fv/Fm) of the evergreen Q ilex and the deciduous Q pubescens oaks was only affected when leaf predawn water potential was lower than -4 MPa. This value is rarely observed on mature trees growing in the field, but can be undergone by young seedlings during drought periods, hence confirming the stability of PS II. Whatever the irradiance, drought resulted, in both species, in lower values of PS II photochemical efficiency in a light-adapted state (ΔF/F m'), due to stomatal closure and/or a direct inhibition of the dark reactions of photosynthesis. Diurnal decreases of Fv/Fm of 30 min dark-adapted leaves were greater for lower predawn water potential; a recovery was observed in the late afternoon. The reversible decreases in the diurnal time-courses of maximal fluorescence led us to assume the onset of protective mechanisms from permanent photodamages in Q ilex and, to a lesser extent, in Q pubescens.
Keywords: fluorescence; photoinhibition; Photosystem II; Quercus; water stress

An overview of ecology and silviculture of indigenous oaks in France - Timbal, J; AUSSENAC, G (Ann. For. Sci., 1996)
There are nine species of oaks in French forests: Quercus petraea, Q robur, Q pubescens, Q pyrenaica, Q ilex, Q rubra, Q suber, Q coccifera and Q cerris. Among them, five are of major economic and ecological importance, either because of the quality and value of their wood or because of their geographic extension, or both. Two of these species are widespread in the hills and plains of the Atlantic and of the mid-European domains: Q petraea (sessile oak), and Q robur (pedunculate oak). Four are present in the Mediterranean region: Q pubescens (pubescent oak), Q ilex (holm oak), Q suber (cork oak) and Q coccifera (kermes oak). Pubescent oak is also present in the Atlantic and mid-European regions provided the local soil and climate conditions are favorable. The last species is of very limited extent and will not be considered further in this review. First, we will analyze the distributions of these species in France, as they result from the vegetation dynamics in Europe and the long-lasting action of man. Second, their synecology will be described, based on the empirical knowledge accumulated by botanists and phytoecologists. We will then describe the vegetation series to which they are related. We will next consider the results of ecophysiologal studies of the species, carried out in many laboratories in France and in other European countries. Finally, we will review the sylvicultural practices applied to oak forests, their productivity under different local conditions and the diverse products they yield.
Keywords: ecology; ecophysiology; France; oak; Quercus; Sylviculture; taxonomy

Effects of oak ( Quercus ilex) tannins on digestion and nitrogen balance in sheep and goats - Narjisse, H; Elhonsali, M A; Olsen, J D (Small Ruminant Research, 1995)
Sheep and goats exhibited different levels of tolerance to the effects of tannins extracted from oak leaves (Quercus ilex) Feed intake, N balance, and rumen ammonia concentrations decreased by 8%, 159% and 50%, respectively, in sheep infused intraruminally with tannins (P <0.05). Similar measurements were not depressed (P> 0.05) in goats although mean rumen ammonia content was 39% less. In vivo DM digestibility was not significantly different for either sheep or goats. Averaged in vitro fermentation capacity was depressed 10% by tannin (8-12% concentration) in the rumen fluid from non-infused sheep given the same diet, but was improved by 9% for goats. Finally, tannin-infused goats lost in urine only 17% of the N ingested, while tannin-infused sheep excreted as much as 44%. The superiority of goats in dealing with tannin might result from the greater ability of their microbial population to degrade tannins, and/or their higher urea recycling and salivary secretion capabilities. Results derived from this study indicate that goats may be more suitable for grazing in oak woodland, especially during the season when alternative forage availability is scarce.
Keywords: digestibility; Feed intake; Goats; Quercus; Sheep; tannin

CRECIMIENTO DE LAS POBLACIONES DE INSECTOS DEL GRUPO <;ERAMBYX CERDO EN LA DEHESA ARBOLADA EXTREMEÑA - del Moral de la Vega, J.; Casado Ponce, D.; Gallego Girón, M. (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
This comunication gives the results of a study cat.:fied out on the damages caused by the Cerambyx cerdo beetles on the cork oaks Quercus suber, Quercus rotundifolia, in the oak forest of Estremadura (Southwest Spain), mainly in the Badajoz province. These species were taxonomicaly identified and their population examined in relation to different variable agrosystems. K.W.:
The following values have no corresponding Zotero field: periodical: Congreso Forestal Español, Lourizán - Pontevedra. 1993
Keywords: Cerambyx cerdo; Estremadura; Quercus; Spain

CRECIMIENTO DE LAS POBLACIONES DE INSECTOS DEL GRUPO <;ERAMBYX CERDO EN LA DEHESA ARBOLADA EXTREMEÑA - del Moral de la Vega, J; Casado Ponce, D; Gallego Girón, M (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
This comunication gives the results of a study cat.:fied out on the damages caused by the Cerambyx cerdo beetles on the cork oaks Quercus suber, Quercus rotundifolia, in the oak forest of Estremadura (Southwest Spain), mainly in the Badajoz province. These species were taxonomicaly identified and their population examined in relation to different variable agrosystems. K.W.:
Keywords: Cerambyx cerdo; Estremadura; Quercus; Spain

ECOLOGIA DE LOS BOSQUES DE QUERCUS DEL PARQUE NATURAL DE LOS ALCORNOCALES (CADIZ) - Jurado Doña, V; Ojeda Rivera, J F (Congreso Forestal Español, 14 e 18 Junho de 1993, Lourizán, 1993)
The floral importance of the most southern mountains of Europe is determined by several orographic, climatic and edaphic factors. This article deals with the ecologic and phitogeographic study of the forests of Quercus of this area that still have a remarkable degree of conservation and that reflects an ancient forest exploitation according to the data of the historie files.
Keywords: Cádiz; conservation; ecology; Quercus

Ecological aspects of the floral phenology of the cork-oak (Q suber L): why do annual and biennial biotypes appear? - Elena-Rossello, J. A.; de Rio, J. M.; Valdecantos Garcia, J. L.; Santamaria, I. G. (Ann. For. Sci., 1993)
Phenological observations (periods of flowering and pollination, floral structures, etc) were made over a 3-year period in natural populations of Q suber. We demonstrated the existence of 2 different types of seed cycles in the cork-oak. The 'annual biotype', requires only 1 season to complete its reproductive cycle (ie, similar to that of the Lepidobalanus group), whereas the 'biennial biotype' requires 2 full years (similar to Erythrobalanus). The variability observed in the cork-oak, during the reproductive cycle, and the meaning of the existence of 2 different reproductive strategies in the same species, are discussed
Keywords: annual and biennial biotypes; cork-oak; ecological variability; floral phenology; Quercus; reproductive strategies

Ecological aspects of the floral phenology of the cork-oak (Q suber L): why do annual and biennial biotypes appear? - Elena-Rossello, J A; de Rio, J M; Valdecantos Garcia, J L; Santamaria, I G (Ann. For. Sci., 1993)
Phenological observations (periods of flowering and pollination, floral structures, etc) were made over a 3-year period in natural populations of Q suber. We demonstrated the existence of 2 different types of seed cycles in the cork-oak. The 'annual biotype', requires only 1 season to complete its reproductive cycle (ie, similar to that of the Lepidobalanus group), whereas the 'biennial biotype' requires 2 full years (similar to Erythrobalanus). The variability observed in the cork-oak, during the reproductive cycle, and the meaning of the existence of 2 different reproductive strategies in the same species, are discussed
Keywords: annual and biennial biotypes; cork-oak; ecological variability; floral phenology; Quercus; reproductive strategies

Intraspecific variation of growth and adaptive traits in European oak species - Kleinschmit, J (Ann. For. Sci., 1993)
According to various reports, 200-450 oak species including hybrid populations exist worldwide, with 24 of these - including 3 hybrid forms - having their natural range within Europe. They all belong to the subgenus Lepidobalanus. The most important section is robur with 21 species. The European species belong to both deciduous (15 species) and evergreen (9 species) oaks. Some difficulties in clear morphological and physiological definition of the species involved is caused by hybridization. Most studies into intraspecific variation exist for the species Quercus robur L and Quercus petraea (Matt) Liebl. Some information is available for Quercus cerris L, Quercus virginiana Ten (= Q dalechampii Wenz), Quercus ilex L and Quercus suber L, based on comparative plantations. In addition, a considerable number of morphological, physiological and biochemical studies based on natural populations exist which are not completely covered in this review paper. For most characters observed, oaks exhibit a wide variation. This is not only the case for morphological traits of pollen, seed, wood and plants but also for physiological traits and phenology which have great adaptive importance. Provenance experiments and progeny tests started as early as 1877. Most of these were only of local importance. This is partly due to the fact that acorns can only be stored for a limited period and flowering is irregular. However, the results available show that the choice of provenance can be important for the successful economic management of plantations. Variability of leaves, phenology, form, growth, wood and bark, roots, seed and flowering has been discussed separately. Improvement via selection and testing seems to be promising due to the considerable between-population and within-provenance variation. Vegetative propagation has been developed for some species by grafting, cutting propagation and in vitro propagation. Tree breeding approaches have also been discussed.
Keywords: intraspecific variation; morphology; progeny test; provenance; Quercus; vegetative propagation

PRODUCCION DE BELLOTA EN QUERCUS ROTUNDIFQLIA LAM.: VARIABILIDAD ANUAL E IMPORTANCIA ECONOMICA - Esparrago, F.; Vázquez, F. M.; Burzaco, A.; Perez, M. C. (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
The acorn production on Q. rotundifolia Lam. has been analyzed from 1989 through 1992 in Extremadura. The efects of different areas, each tree, and the interaction between areas/years are significatives. Genetic, pruning, environment and phytosanitary factors are the possible causes of these differences. Finally, the econornic efects of acorn production on iberian pig feeding (Montanera) has been studied. This is the rnain factor for high quality products.
The following values have no corresponding Zotero field: periodical: Congreso Forestal Español, Lourizán - Pontevedra. 1993
Keywords: acorn; Econorny; evergreen oak; feeding; iberian pig; production; Quercus

PRODUCCION DE BELLOTA EN QUERCUS ROTUNDIFQLIA LAM.: VARIABILIDAD ANUAL E IMPORTANCIA ECONOMICA - Esparrago, F; Vázquez, F M; Burzaco, A; Perez, M C (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
The acorn production on Q. rotundifolia Lam. has been analyzed from 1989 through 1992 in Extremadura. The efects of different areas, each tree, and the interaction between areas/years are significatives. Genetic, pruning, environment and phytosanitary factors are the possible causes of these differences. Finally, the econornic efects of acorn production on iberian pig feeding (Montanera) has been studied. This is the rnain factor for high quality products.
Keywords: acorn; Econorny; evergreen oak; feeding; iberian pig; production; Quercus

Comparative water relations of four Mediterranean oak species - Acherar, M.; Rambal, S. (Plant Ecology, 1992)
The water relations and responses of two evergreen (Quercus ilex L. and Q. suber L.) and two decidu- ous (S. afares Pomel. and Q. faginea Will.) Quercus species were studied under experimental conditions. Two-year old seedlings grown in 30 1. pots were subjected to a drying period during which stomatal conductance, pre-dawn potential and minimum foliar potential were measured. The results shows that, for all species, the daily course of stomatal conductance agrees with the patterns proposed by Hinckley et al. (1978 & 1983). Concurrent with the species responses to short-term variation in water availability, it was found that pre-dawn leaf water potential controlled the maximum daily leaf conductance. There was a strong correlation between pre-dawn leaf potential and maximum daily conductance as described by the reciprocal function g ........ = ( -0.47 + 2.61.~bp) 1 for the evergreen oaks and g ......... (-1.94+7.39.~bp) 1 for the deciduous species. These differences between the two groups may partialy explain their geograhic distributions, and suggest general questions concerning the mechanisms which optimize water-use efficiency in Mediterranean oak species.
Keywords: mediterranean species; Quercus; Stomatal conductance; water-potential; water-stress

Evidence for hybridization between sympatric holm-oak and cork-oak in Spain based on diagnostic enzyme markers - Elena-Rossello, J. A.; Lumaret, R.; Cabrera, E.; Michaud, H. (Plant Ecology, 1992)
Hybridization has been detected in mixed populations of juvenile cork-oak and holm-oak individuals using three diagnostic enzyme loci coding for esterases, leucine amino peptidases and acid phosphatases respectively. Among the 35 studied individuals, 29, 5 and 1 were identified as holm-oak, cork-oak and hybrid respectively. Such diagnostic markers are likely to be useful to detect and remove hybrids at the juvenile stage in areas where the holm-oak is grown for acorn production and the cork-oak is cultivated for cork. This is necessary since hybrid adults produce neither cork nor acorns of high quality.
Keywords: cork-oak; enzyme markers; holm-oak; Hybridization; Quercus

Stomatal patchiness in Mediterranean evergreen sclerophylls Phenomenology and consequences for the interpretation of the midday depression in photosynthesis and transpiration - Beyschlag, Wolfram; Pfanz, Hardy; Ryel, Ronald J.; Botanik, Lehrstuhl; Universitfit, I. I.; Dallenbergweg, Mittlerer; Republic, Federal; Science, Range (Planta, 1992)
Midday depression of net photosynthesis and transpiration in the Mediterranean sclerophylls Arbutus unedo L. and Quercus suber L. occurs with a depression of mesophyll photosynthetic activity as indicated by cal- culated carboxylation efficiency (CE) and constant diur- nal calculated leaf intercellular partial pressure of CO 2 (Ci). This work examines the hypothesis that this midday depression can be explained by the distribution of patches of either wide-open or closed stomata on the leaf surface, independent of a coupling mechanism between stomata and mesophyll that results in a midday depres- sion of photosynthetic activity of the mesophyll. Pressure infiltration of four liquids differing in their surface ten- sion was used as a method to show the occurrence of stomatal patchiness and to determine the status of sto- matal aperture within the patches. Liquids were selected such that the threshold leaf conductance necessary for infiltration through the stomatal pores covered the ex- pected diurnal range of calculated leaf conductance (g) for these species. Infiltration experiments were carried out with leaves of potted plants under simulated Mediterranean summer conditions in a growth chamber. For all four liquids, leaves of both species were found to be fully infiltratable in the morning and in the late after- noon while during the periods leading up to and away from midday the leaves showed a pronounced patchy distribution of infiltratable and non-infiltratable areas. Similar linear relationships between the amount of liquid infiltrated and g (measured by porometry prior to de- tachment and infiltration) for all liquids clearly revealed the existence of pneumatically isolated patches containing only wide-open or closed stomata. The good correspon- dence between the midday depression of CE, calculated * Dedicated to Professor Otto L. Lange on the occasion of his 65th birthday ** To whom correspondence should be addressed Abbreviations: A = net photosynthesis rate; Ci = actual leaf internal CO2 partial pressure; Ci *=apparent leaf internal CO2 partial pressure; CE = actual carboxylation efficiency; CE* = apparent car- boxylation efficiency; E = transpiration rate; g = leaf conductance under the assumption of no stomatal patchiness, and the diurnal changes in non-infiltratable leaf area strongly indicates that the apparent reduction in mesophyll activ- ity results from assuming no stomatal patchiness. It is suggested that simultaneous responses of stomata and mesophyll activity reported for other species may also be attributed to the occurrence of stomatal patchiness. In Quercus coccifera L., where the lack of constant diurnal calculated C i and major depression of measured CE at noontime indicates different stomatal behavior, non- linear and dissimilar relationships between g and the infiltratable quantities of the four liquids were found. This indicates a wide distribution of stomatal aperture on the leaf surface rather than only wide-open or closed stomata.
Keywords: arbutus; Mediterranean; Quercus; Sclerophyll; stomate (control-patchiness)

Évolution du potentiel hydrique foliaire et de la conductance stomatique de quatre chênes méditerranéens lors d'une période de dessèchement - Acherar, M; Rambal, S; Lepart, J (Ann. For. Sci., 1991)
Influence of soil drying on leaf water potential and stomatal conductance in four Mediterranean oak species. The water relations and the responses of 2 evergreen Quercus species (Quercus ilex L and Q suber L) and 2 deciduous species (Q afares Pomel and Q faginea Willd) were studied under experimental conditions. Two-yr old seedlings grown in 30-1 pots were subjected to a drying period where stomatal conductance, pre-dawn leaf water potential and minimum leaf water potential were measured. The results show that, for all species, the daily course of stomatal conductance agrees with the patterns proposed by Hinckley et al (1978, 1983). Concurrent with the species responses to short-term variation in water availability, it was found that pre-dawn leaf water potential controlled the maximum daily leaf conductance. There was a strong correlation between pre-dawn leaf potential and maximum daily conductance (gsr max) as described by the reciprocal function gsr max = (-0.47 + 2.61 ψb)-1 for the evergreen oaks and gsr max = (-1.94 + 7.39 ψb)-1 for the deciduous ones. The differences between the 2 groups may partially explain their geographic distributions, and also lead to general questions concerning the mechanisms of water use in the Mediterranean oak species.
Keywords: deciduous; evergreen; mediterranean species; Quercus; Stomatal conductance; water potential; water stress

SEED STORAGE PROTEINS IN FAGACEAE - SIMILARITY BETWEEN CASTANEA GLOBULINS AND QUERCUS GLUTELINS - COLLADA, C; CABALLERO, R G; CASADO, R; ARAGONCILLO, C (PLANT SCIENCE, 1991)
Castanea sativa Mill. and C. crenata Lieb. and Zucc. store 11S globulins as major seed proteins while Quercus ilex L. and Q. robur L., also members of the Fagaceae family, accumulate glutelins. The structure of the 11S Castanea globulins, which is similar to the accepted model for this class of proteins, has been studied by different two-dimensional electrophoretic methods. The oligomer has a M(r) of 240 000-260 000, and the pairs of acidic-basic subunits, which form it, show great heterogeneity. The Quercus glutelins are made up of dimers linked by disulphide bridges, and their characteristics indicate a similarity to the subunits of 11S Castanea globulins. We suggest that, as in the case of rice glutelins, Quercus glutelins can also be considered legumin-like proteins.
Keywords: 11S GLOBULINS; Castanea; GLUTELINS; Quercus

Ribosomal RNA genes inQuercus spp.(Fagaceae) - Bellarosa, R; Delre, V; Schirone, B; Maggini, F (Plant Systematics and …, 1990)
The taxonomy of the genus Quercus is still unclear. In order to elucidate the taxonomy of Mediterranean oaks we have analyzed ribosomal RNA genes of Quercus cerris, Q. coccifera, Q. trojana, Q. ilex, Q. suber, and Q. macrolepis by means of Southern blot hybridization. Oak nuclear DNA was extracted from root tips of 300 acorns and from catkins of single plants. EcoRI and BamHI restriction endonucleases were used. DNA electrophoresis and rRNA/DNA hybridization were performed using Vicia faba rRNA 18 S and 25 S as probes. The rRNA genes of all the species studied have an identical restriction mapping in the 18 S and 25 S regions, while differences in length are present in the intergenic regions. Q. cerris possesses at least four types of genes of 12.1, 11.5, 8.5, and 8.3 kb; Q. coccifera at least three types of 12.4, 10.4, and 10.1 kb; Q. trojana possesses the same rRNA genes as Q. cerris plus another gene type 12.0 kb long, with EcoRI and BamHI restriction sites in the intergenic spacer; Q. ilex at least three types of 12.4, 10.85, and 9.5 kb; Q. suber at least five types of 11.5, 11.0, 8.6, 8.5, and 8.3 kb; Q. macrolepis, finally, at least seven types of 11.5, 11.0, 10.2, 8.6, 8.5, 8.3, and 8.15kb. Q. coccifera and Q. ilex rDNA appears quite different respect to other species examined, while high similarity seems to exist between Q. cerris, Q. trojana, Q. suber, and Q. macrolepis. These results are in agreement with the taxonomic model proposed by SCnWARZ for the genus Quercus.
Keywords: Angiosperms; Fagaceae; Gene mapping; Quercus; ribosomal RNA genes; rRNA/DNA hybridization; taxonomy

Ribosomal RNA genes inQuercus spp.(Fagaceae) - Bellarosa, R.; Delre, V.; Schirone, B.; Maggini, F. (Plant Systematics and …, 1990)
The taxonomy of the genus Quercus is still unclear. In order to elucidate the taxonomy of Mediterranean oaks we have analyzed ribosomal RNA genes of Quercus cerris, Q. coccifera, Q. trojana, Q. ilex, Q. suber, and Q. macrolepis by means of Southern blot hybridization. Oak nuclear DNA was extracted from root tips of 300 acorns and from catkins of single plants. EcoRI and BamHI restriction endonucleases were used. DNA electrophoresis and rRNA/DNA hybridization were performed using Vicia faba rRNA 18 S and 25 S as probes. The rRNA genes of all the species studied have an identical restriction mapping in the 18 S and 25 S regions, while differences in length are present in the intergenic regions. Q. cerris possesses at least four types of genes of 12.1, 11.5, 8.5, and 8.3 kb; Q. coccifera at least three types of 12.4, 10.4, and 10.1 kb; Q. trojana possesses the same rRNA genes as Q. cerris plus another gene type 12.0 kb long, with EcoRI and BamHI restriction sites in the intergenic spacer; Q. ilex at least three types of 12.4, 10.85, and 9.5 kb; Q. suber at least five types of 11.5, 11.0, 8.6, 8.5, and 8.3 kb; Q. macrolepis, finally, at least seven types of 11.5, 11.0, 10.2, 8.6, 8.5, 8.3, and 8.15kb. Q. coccifera and Q. ilex rDNA appears quite different respect to other species examined, while high similarity seems to exist between Q. cerris, Q. trojana, Q. suber, and Q. macrolepis. These results are in agreement with the taxonomic model proposed by SCnWARZ for the genus Quercus.
Keywords: Angiosperms; Fagaceae; Gene mapping; Quercus; ribosomal RNA genes; rRNA/DNA hybridization; taxonomy

An evaluation of the differences in the composition of humic acids in soils under oak and pine forest by GC-MS after mild degradation - González-Vila, F L; Almendros, G; Martin, F (Plant and soil, 1987)
Significant differences were found in the products released after eight samples of humic acids (HA's) isolated from soils under mediterranean pine and oak forests underwent mild degradation. A number of compounds, including typical degradation products of lignins, were found exclusively in the HA's from the soils under pine forests. The aliphatic constituents were more firmly retained in the HA's under oak, which presented mean values for aromatic acids lower than the humic samples from pine forests. Different types of diterpene resin acids were also found amongst the mild degradation products of HA's from the studied areas.
Keywords: Forest soils; humic acids; Lipids; mild degradation; Pinus; Quercus; resin acids

Changes in photosynthetic capacity, carboxylation efficiency, and CO 2 compensation point associated with midday stomatal closure and midday depression of net - Tenhunen, J D; Lange, O L; Gebel, J (Planta, 1984)
The carbon-dioxide response of photo- synthesis of leaves of Quercus suber, a sclerophyl- lous species of the European Mediterranean re- gion, was studied as a function of time of day at the end of the summer dry season in the natural habitat. To examine the response experimentally, a "standard" time course for temperature and hu- midity, which resembled natural conditions, was imposed on the leaves, and the CO 2 pressure exter- nal to the leaves on subsequent days was varied. The particular temperature and humidity condi- tions chosen were those which elicited a strong sto- matal closure at midday and the simultaneous de- pression of net CO 2 uptake. Midday depression of CO 2 uptake is the result of i) a decrease in CO2- saturated photosynthetic capacity after light satu- ration is reached in the early morning, ii) a de- crease in the initial slope of the CO 2 response curve (carboxylation efficiency), and iii) a substantial in- crease in the CO 2 compensation point caused by an increase in leaf temperature and a decrease in humidity. As a consequence of the changes in pho- tosynthesis, the internal leaf CO 2 pressure re- mained essentially constant despite stomatal clo- sure. The effects on capacity, slope, and compensa- tion point were reversed by lowering the tempera- ture and increasing the humidity in the afternoon. Constant internal CO 2 may aid in minimizing photoinhibition during stomatal closure at midday. The results are discussed in terms of possible tem- perature, humidity, and hormonal effects on pho- tosynthesis.
Keywords: Carboxylation efficiency; Compensation point (CO2); Photosynthesis (temperature- humidity); Quercus; Sclerophyll

Pollen grain morphology supports the taxonomical discrimination of Mediterranean oaks (Quercus, Fagaceae) - Colombo, P M; Lorenzoni, F C; Grigoletto, F (Plant Systematics and Evolution, 1983)
The exine architecture and some quantitative parameters (polar and equatorial axes and their ratio) of pollen grains allow a clear discrimination between groups of Mediterranean oak species. For the differentiation of species within groups only the quoted parameters prove useful.
Keywords: Angiosperms; Fagaceae; Pollen exine architecture; pollen grain size and form; Quercus